Sesamol-loaded PLGA nanoparticles attenuate HFD-induced MASLD by modulating Nrf2/HO-1, mitochondria cascade, and TLR4/NF-κB signaling pathways in rats - Elsayed S.I. Mohammed; Mohamed Shawky El Sayed; Tahani Ahmad Al-Matrafi; Roshmon ‎Thomas Mathew; Mohamed Ashour; Mohammed Tariq Saud Albaloushi; Hailah M. Almohaimeed; El-Sayed Hemdan Eissa; Sameh A. Abdelnour (Tissue and Cell, 2027)

Histochemical and ultrastructural characterization of the gills in tiger shark, Galeocerdo cuvier (Péron & Lesueur, 1822): Structural strategies for functional adaptation - Fatma A. Madkour; Elsayed S.I. Mohammed; Mohammed Al-Rasheed; Eman E. El-Nahass; Mona M. Elwan; Mohamed Ashour; Roshmon Thomas Mathew; Fatma Abdelhakeem (Tissue and Cell, 2027)

Dietary banana peels modulate waterborne oxyfluorfen-induced hepatotoxicity in Nile tilapia (Oreochromis niloticus) via regulation of redox homeostasis and ER stress signaling - Afaf N. Abdel Rahman; Gehad E. Elshopakey; Abdallah Tageldein Mansour; Hesham A. Hassanien; Ahmed Abbas; Mohamed Ashour; Roshmon Thomas Mathew; Tarek Khamis; Rowida E. Ibrahim; Rasha M.M. Ezz-Eldin (Veterinary Research Communications, 2026)

Development and characterization of powdered waste glass-aluminum particles hybrid reinforced epoxy composite for durable and lightweight applications in transportation and energy industries - Isiaka Oluwole Oladele; Mathew Adekunle Ajayi; Abigail Oluwapamilerinayo Adekunle; Dennis O. Bichang’a (Next Research, 2026)

Barbados aloe as a water-administered therapeutic against Pseudomonas aeruginosa infection in Clarias gariepinus: Effects on hemato-biochemical profiles, electrolyte homeostasis, antioxidant capacity, and tissue histology - Afaf N. Abdel Rahman; Heba H. Mahboub; Abdallah Tageldein Mansour; Ahmed Saud Alsaqufi; Yousef Ahmed Alkhamis; Mohamed Ashour; Roshmon Thomas Mathew; Mahmoud I.M. Darwish; Ahmed Abdou Elnegiry; Yasmin A. Reyad (Veterinary Research Communications, 2026)

Hesperidin dietary intervention mitigates ammonia stress-evoked biochemical and metabolic disruption and restores the tlr-5–nf-κβ/mapk gene expression in Oreochromis niloticus - Rowida E. Ibrahim; Nehal A. Younis; Abdallah Tageldein Mansour; Hesham A. Hassanien; Haytham H. Abdelwahid; Ahmed Abbas; Mohamed Ashour; Roshmon Thomas Mathew; Tarek Khamis; Mohamed Fouad Mansour; Afaf N. Abdel Rahman; Sara T. Elazab (Fish Physiology and Biochemistry, 2026)

Connecting ambient toxicity testing with community-level responses of benthic macroinvertebrates in an impacted stream in East Tennessee, USA - Louise M. Stevenson; Paul G. Matson; Peyton C. Marcum; Nikki J. Jones; Scott C. Brooks; Trystan Bordeau; Allison M. Fortner; Natalie A. Griffiths; Christopher R. DeRolph; R. Trent Jett; Michael W. Jones; Peijia Ku; et al. (Journal of Environmental Management, 2026)

Heritage Stones Through Ages and Civilizations: A Comparative Study of Western Ghats Laterite (India) and Tezontle Volcanic Scoria (Mexico) - Bobby P. Mathew; Carles Canet; Elizabeth Lozada-Amador; Gurmeet Kaur; Raymond A. Duraiswami; Elizabeth Castañeda-Bastida; Francisco O. Lagarda-García (Geoheritage, 2026)
A comparison is made between two IUGS Heritage Stones designated in 2024, Western Ghats Laterite (India) and Tezontle volcanic scoria (Mexico), to highlight their cultural impact across millennia and analyze a possible convergence in their use and symbolism. These stones originate from contrasting cultural settings and were generated through distinct geological processes and timescales. In both cases, they exhibit extensive, long-standing use in cultural heritage and are deeply rooted in local identity. Laterite is a residual product formed in situ through prolonged chemical weathering under humid tropical conditions, whereas tezontle is a highly vesicular volcanic scoria generated by Strombolian eruptions. From an aesthetic perspective, there is a significant coincidence based on their predominant reddish coloration and rough, matte surfaces. However, their resemblance in terms of mechanical properties, such as compressive strength and density, is notably lower; consequently, their technical applications differ in each case. A striking convergence exists in how architectural practices in both regions leveraged the favorable workability and aesthetic properties of these stones to achieve comparable results; both stones were paired with lighter materials to achieve visual contrast in intricate ornamentation set against the sober, dominant reddish-dark hue of the façades. This was particularly prominent during the Baroque period (16th–18th centuries), imprinting a distinct identity upon both regions through shared elements arising from the confluence of colonialism and deep-rooted indigenous cultures. Consequently, the use of these respective stones serves as an element of material continuity, acting as a tangible bridge between colonial influence and native heritage. The designation as an IUGS Heritage Stone is strengthened by the prior recognition of World Heritage properties featuring these stones, creating a synergy that enhances the connections between cultural and geoheritage. This joint recognition should foster cohesive conservation policies prioritizing original restoration materials, the protection of historical quarries, and the development of geotourism.

The protective effects of chrysin-loaded casein nanoparticles on rabbit sperm following cryopreservation: Antioxidant and anti-apoptotic insights - Elsayed S.I. Mohammed; Mohamed Shawky El Sayed; Mohamed Ashour; Michelyn Haroun; Roshmon Thomas Mathew; Ramya Ahmad Sindi; Nawal Al-Hoshani; Sameh A. Abdelnour; Asmaa Sheiha (Tissue and Cell, 2026)

Dietary yeast-derived nucleotides enhance reproductive efficiency, blood metabolic profile, antioxidant status, and immune function in rabbit does - Noura H. Gouda; Sameh A. Abdelnour; Elsayed S. I. Mohammed; Mohamed Shawky El Sayed; Mohamed Ashour; Roshmon Thomas Mathew; Mohammed Tariq Saud Albaloushi; Hailah M. Almohaimeed; Ehab El-Haroun; Mahmoud S. Abd-Allah (Veterinary Research Communications, 2026)

Seaweed Liquid Extract Improves Growth, Immunity, and Gene Expression in Nile Tilapia (Oreochromis niloticus) - Mohamed Ashour; Einar Ringø; Fawzia S. Ali; Ahmed Mamoon; Othman F. Abdelzaher; Roshmon Thomas Mathew; Abdallah Tageldein Mansour; Yousef Ahmed Alkhamis; Elsayed S. I. Mohammed; Hesham S. Hassanien; Mohamed A. Elokaby; Mohamed M. Mabrouk (Journal of Applied Phycology, 2026)

Evaluating synthetic substitutes to reduce illegal harvesting and support species recovery - Aditya Shekhar Malgaonkar; Gareth Whittington‐Jones; Tristan Dickerson; Maswabi Lishandu; Sarah Davies; Zoe Woodgate; Xia Stevens; Choolwe Mulenga; Gift Mulenga; Mathew Phiri; Lucky Mulenga; Manyando Mukela; et al. (Conservation Biology, 2026)
Providing synthetic substitutes is a widely promoted strategy to shift consumer demand away from wildlife products derived from threatened species. Yet, there is little evidence on whether product substitution prevents illegal or unsustainable harvesting and contributes to the recovery of threatened populations. Drawing on the Furs for Life Zambia initiative, which supplied synthetic furs known as heritage furs to replace leopard furs traditionally worn during Lozi royal ceremonies in western Zambia, we devised a way to test the effects and causal mechanisms of substitution. Guided by the EMMIE (effect, mechanisms, moderators, implementation, and economic cost) framework commonly used in crime prevention evaluations, we triangulated data from semistructured questionnaires, law enforcement patrols, court records, camera‐trap monitoring of leopards ( Panthera pardus ), and stakeholder interviews conducted from 2018 to 2024. We used qualitative analyses and the general elimination method to assess plausible alternative explanations for leopard recovery. By 2024, adoption of synthetic furs among leopard fur users exceeded 80%, and self‐reported ownership of authentic leopard furs declined by 78%. Patrol detections of leopard poaching incidents decreased, and camera‐trap density estimates increased from an average of 2.7 to 3.8 leopards per 100 km 2 across the focal landscape. An integrated mechanism of change, derived from stakeholder perspectives, indicated that reduced demand from substitution was reinforced by concurrent counter‐poaching and counter‐trafficking operations. Our results provide the first empirical link between a demand‐reduction initiative based on synthetic substitutes and measurable population recovery of species.

Efficacy of dietary Artemisia annua against chronic carbendazim exposure in Nile tilapia: growth, antioxidant capacity, intestinal morphology, inflammatory/apoptotic genes - Rowida E. Ibrahim; Abdallah Tageldein Mansour; Ahmed Saud Alsaqufi; Yousef Ahmed Alkhamis; Mohamed Ashour; Roshmon Thomas Mathew; Tarek Khamis; Afaf N. Abdel Rahman; Abdelhakeem El-Murr; Mai A. M. El-son (Aquaculture International, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Dietary Crataegus sinaica leaves enhance growth performance, antioxidant status, intestinal integrity, and regulate inflammation-related genes in Nile tilapia under melamine exposure - Walaa El-Houseiny; Abdallah Tageldein Mansour; Amany Behairy; Ahmed Saud Alsaqufi; Yousef Ahmed Alkhamis; Yasmina M. Abd-Elhakim; Mohamed Ashour; Roshmon Thomas Mathew; Ahmed O. Abbas; Bayan A. Hassan; Engy M. M. Mohamed; Yasmina K. Mahmoud (Frontiers in Marine Science, 2026)
Introduction Dietary exposure to melamine (MELA) adversely affects growth performance and intestinal health in Nile tilapia. This study evaluated the protective effects of Crataegus sinaica leaf extract (CSL) against MELA-induced toxicity. Methods In this study, a total of 240 fish (26.39 ± 0.22) were randomly assigned to four groups (60 fish/group; four replicates of 15 fish each). The control group received a basal diet, the CSL group received 1% CSL, the MELA group received 10 g/kg MELA, and the CSL+MELA group received both CSL (1%) and MELA (10 g/kg) for 60 days. Results MELA exposure significantly reduced growth performance, including final body weight (−26.78%), weight gain (−50.59%), specific growth rate (−41.41%), and feed intake (−20.50%) compared to the control, and increased feed conversion ratio (FCR). Conversely, CSL supplementation enhanced growth parameters, with increases in weight gain (33.88%), specific growth rate (21.88%), and FCR reduced by (20.57%). Co-administration of CSL with MELA partially restored growth, with final body weight, weight gain, and FCR approaching control values. MELA also suppressed digestive enzyme activities (lipase −21.38%, α-amylase −34.72%, protease −32.42%) and impaired intestinal antioxidant defenses (SOD −43.73%, CAT −37.88%, GPx −38.01%, GST −50%; MDA increased by 128.58%). CSL supplementation increased antioxidant enzyme activities (SOD + 17.20%, CAT + 57.58%, GPx +13.43%, GST + 28.95%) and restored digestive enzyme activity (lipase: +10.11%, α- amylase: +11.50%, and protease: +8.82%). At the molecular level, MELA significantly upregulated inflammatory genes ( tnf-α : 5.22 ± 0.35, tlr-4 : 3.01 ± 0.34, il-6 : 2.66 ± 0.11, il-8 : 2.65 ± 0.15) while CSL co-administration downregulated these genes and normalized il-10 expression (2.67 ± 0.15). Histopathological analysis confirmed that CSL mitigated MELA-induced intestinal damage, including epithelial denudation, inflammatory infiltration, hemorrhage, and goblet cell hyperplasia. Conclusion These findings showed that dietary CSL markedly promotes growth, enhances antioxidant defenses, modulates inflammatory responses, and protects intestinal integrity, demonstrating its potential as a natural dietary strategy to counteract MELA toxicity in Oreochromis niloticus .

High-resolution carbon isotope record from Svalbard reveals elevated atmospheric CO2 during the Middle Devonian Taghanic crisis - Annique van der Boon; Brian A. Schubert; William M. Hagopian; Mathew Domeier; A. Hope Jahren (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Paleodirections and paleointensity of the Zimbros dikes (South Brazil): Evidence for ultralow fields and hints of a dipole in the mid-Ediacaran - Camila R. Tomé; Jairo F. Savian; Wellington P. de Oliveira; Gelvam A. Hartmann; João A.S. Fontoura; Mathew Domeier; Filipe A. Temporim; Ruth Hinrichs; Ricardo I.F. Trindade; Maria de Fátima Bitencourt (Earth and Planetary Science Letters, 2026)

Context-of-use–Guided Development and Validation of a Transthyretin Immunoassay: A Framework for Biomarker Assay Design - Tanya Watanabe; John Canfield; Erin Anderson; Leighla Tayefeh; John L. Allinson; Nicholas J. Viney; Joel A. Mathews (The AAPS Journal, 2026)

Modulation of growth, blood physiology, disease resistance, molecular immune-antioxidant gene expression, and tissue integrity in european seabass (Dicentrarchus labrax) fed Moringa oleifera flower-enriched diets - Roshmon Thomas Mathew; Mohamed Ashour; Ehab El-Haroun; Abdallah Tageldein Mansour; Ahmed Saud Alsaqufi; Yousef Ahmed Alkhamis; Hailah M. Almohaimeed; Nehal A. Younis; Moaheda E.H. Eissa; El‐Sayed Hemdan Eissa (Frontiers in Marine Science, 2026)
Herbal-based additives are now recognized as effective tools of growth and immunity in aquaculture. Seeking these botanical alternatives is a practical necessity for sustainable farming and chemical reduction. Moringa oleifera flowers (MOF), in particular, offer significant potential due to their established history in treating inflammation and respiratory conditions. However, the potential of these additives to enhance growth, physiological status, and tissue health in European seabass ( Dicentrarchus labrax ) has not yet been evaluated. A 70-day feeding trial was conducted to evaluate the effects of graded dietary levels of M. oleifera flower (MOF) on the growth performance, immune- and antioxidant-related genes, physio-metabolic profile, and redox homeostasis of European seabass and resistance to Vibrio alginolyticus challenge. Fish were allocated to four experimental groups and fed either a basal diet (control, MOF0) or the basal diet supplemented with MOF at concentrations of 1 (MOF1), 2 (MOF2), and 3 (MOF3) g/kg. Dietary MOF supplementation significantly enhanced growth indices and the whole-body proximate composition of D. labrax compared to the control group (P< 0.05). Furthermore, fish fed MOF-enriched diets exhibited significant elevations in hematological parameters, including (hemoglobin, RBCs, MCH, MCHC, and WBC) counts (P< 0.05). Metabolic and antioxidant profiles were similarly improved, characterized by a significant increase in total serum protein and a concomitant reduction in glucose, cholesterol, and hepatic enzyme activities (AST, ALT, and ALP) (P< 0.05). Dietary MOF inclusion mitigated oxidative damage by decreasing MDA levels while simultaneously enhancing the enzymatic antioxidant defense system (SOD, CAT, and GPx) (P< 0.05). These biochemical improvements were supported by molecular data showing a significant upregulation of growth genes ( IGF-I and GH ), pro-inflammatory and complement system genes (IL-1β and C3 ), and antioxidant enzymes ( SOD and GPx ) (P< 0.05). MOF inclusion in the diets of D. labrax supported systemic tissue health by improving the structural integrity of the intestinal mucosa and preventing degenerative changes in the hepatic parenchyma and muscle fibers. These findings underscore the multi-tissue cytoprotective efficacy of MOF in D. labrax . Following the V. alginolyticus challenge, fish in the MOF2 and MOF3 groups exhibited significantly higher survival rates and enhanced pathogen resistance compared to the MOF0 and MOF1 cohorts (P< 0.05). Consequently, our data suggest that a dietary inclusion of 2 g/kg of M. oleifera flowers represents an effective strategy for optimizing growth performance, immunocompetence, and antioxidant capacity in European seabass.

Comparative efficacy of silver nanoparticles from agro-industrial waste of cumin, anise, and banana peel against Fusarium oxysporum on common bean (Phaseolus vulgaris) - Reham Oraby; Amera N. Alqahtani; Laila A. AL-Essa; Hanan AlOmari; Merfat O. Aljhdli; Mari Sumayli; Ramadan Taha; Ahmed M. Saad; Lamia Elmaghraby; Taha F. Taha; Mohamed A. Taha; Walid F. A. Mosa; et al. (European Journal of Plant Pathology, 2026)
Fusarium oxysporum , the causal agent of root rot and vascular wilt in common bean ( Phaseolus vulgaris ), represents a substantial risk to legume cultivation. The current study offers a comparative examination of the antifungal efficacy of agro-industrial wastes from cumin ( Cuminum cyminum ), anise ( Pimpinella anisum ), and banana peel ( Musa paradisiaca ), and their green-synthesized silver nanoparticles (AgNPs), against F. oxysporum infecting P. vulgaris . The biosynthesized AgNPs were found to be spherical with tiny sizes ranging from 20, 25, and 35 nm for cumin-AgNPs, anise-AgNPs, and banana peel-AgNPs, respectively. The agro-industrial waste extracts revealed a diverse range of bioactive compounds that served as reducing agents. In vitro antifungal activity revealed a dose-dependent suppression of F. oxysporum mycelial proliferation. The half-maximal effective concentrations (EC 50 ) for the crude extracts ranged from 125 to 200 µg/mL. AgNPs showed markedly improved EC 50 values, ranging from 62.5 µg/mL in cumin-AgNPs to 100 µg/mL in banana-AgNPs. In vivo greenhouse experiments on infected P. vulgaris demonstrated that all treatments significantly decreased disease severity. Soil drench application of agro-industrial waste extracts reduced disease severity to 59.64% (cumin waste), 66.52% (anise waste), and 74.86% (banana peel), compared with 85.14% in the infected control. The AgNPs fabricated from agro-industrial wastes offered enhanced protection, decreased disease severity to 36.17% (cumin-AgNPs), 43.30% (anise-AgNPs), and 51.52% (banana peel-AgNPs). The applications significantly alleviated the physiological and oxidative stress caused by F. oxysporum . The cumin-AgNPs treatment significantly restored chlorophyll a and chlorophyll b content to 2.45 and 0.92 mg/g, respectively, comparable to the healthy control (2.50 and 0.95 mg/g) and much higher than the infected control (1.10 and 0.40 mg/g). Moreover, it triggered a defense response, markedly enhancing the activities of antioxidant enzymes, including peroxidase and polyphenol oxidase, in the treated plant compared with the infected control. The current findings clearly indicate that AgNPs synthesized from agro-industrial wastes could serve as effective, sustainable nanobiopesticides, surpassing the use of a single agro-industrial waste for the integrated management of Fusarium root rot and vascular wilt in common beans.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Spatial variability in the carbon stocks of different seagrass meadows of southern Palk Bay, India: Influence of species composition, sediment characteristics and restoration efforts - N. Gladwin Gnana Asir; G. Mathews; K. Diraviya Raj; P. Dinesh Kumar; A. Arasamuthu; R.L. Laju; Bakan Jagdish Sudhakar; J.K. Patterson Edward (Marine Pollution Bulletin, 2026)

The Impact of Mangrove Degradation and Restoration on Total Ecosystem Carbon Stocks - Kavindi Dilshara Kandauda; Rupesh Kumar Bhomia; Hiranya Kelum Wijenayake; Richard MacKenzie; Susantha Udagedara; Waruni Tissera; Thilina Kumarasiri; Manjula Amararathna; Priyal Buddhika Upananda; Mathew A. Vanderklift; Sevvandi Jayakody (Wetlands, 2026)

Antioxidant protection by vanillin aldehyde against chronic pymetrozine-induced hepatic, renal, and DNA damage in African catfish - Afaf N. Abdel Rahman; Mohamed Fouad Mansour; Abdallah Tageldein Mansour; Hesham A. Hassanien; Ahmed Abbas; Mohamed Ashour; Roshmon Thomas Mathew; Sara T. Elazab; Eman Wagih; Rowida E. Ibrahim (Veterinary Research Communications, 2026)

Development and Pre-clinical Feasibility of a Catheter-Based Platform for Interventional Phase−0 Drug Response Measurements - Sharath K. Bhagavatula; Ellen Maloney; Hidde Ploeger; Sebastian W. Ahn; Samantha Martin; Santhosh A. Mathew; Sajanlal Panikkanvalappil; Guigen Liu; Oliver Jonas (Annals of Biomedical Engineering, 2026)

Guava leaf (Psidium guajava) byproducts in animal and fish diets: a review of health benefits, immunomodulation, and sustainable applications - Khaled M. Al-Marakby; Islam G. Abdelghani; Ehab El-Haroun; Zeinab Mahasneh; Roshmon Thomas Mathew; Asmaa M. Sheiha; Mohamed F. Abo El-Maati; El-Sayed Hemdan Eissa; Md Altafur Rahman; Sameh A. Abdelnour (Tropical Animal Health and Production, 2026)

Improving growth traits in rabbits: a comparative study of Gabali, New Zealand White, and their hybrids using 18S rDNA sequencing - Hairul Islam Mohamed Ibrahim; Abdullah Sheikh; Roshmon Thomas Mathew; Muhammad Munir; Gamal Bekhet; El-Sayed Hemdan Eissa; Sameh A. Abdelnour; Mohamed D. Mahran (Tropical Animal Health and Production, 2026)

Assessment of space weather modeling capabilities and transition to operations - Maria M. Kuznetsova; Martin A. Reiss; Edmund Henley; Eric Adamson; Suzy Bingham; Mario M. Bisi; François-Xavier Bocquet; Laura Boucheron; Min-Yang Chou; Claudio Corti; Gian Luca Delzanno; Richard A. Fallows; et al. (Advances in Space Research, 2026)

‘Building the (Im)perfect Beast’: Strategies for Identifying Appropriate Spatial Stock Assessment Model Complexity From an International, Blinded High‐Resolution Simulation Experiment - Aaron M. Berger; Daniel R. Goethel; Simon D. Hoyle; Patrick Lynch; Caren Barceló; Alistar Dunn; Brian J. Langseth; Carolina Minte‐Vera; Jemery Day; Haikun Xu; Francisco Izquierdo; Dan Fu; et al. (Fish and Fisheries, 2026)
Despite their potential to inform sustainable regional harvest and climate‐resilient fisheries management, spatial stock assessment models remain underused for management advice. To identify barriers that inhibit broader use of these methods, we conducted a blinded international simulation experiment mimicking real‐world stock assessment development when confronting spatial complexity. Seven analyst teams built spatially aggregated and spatially explicit assessment models using data simulated from high‐resolution operating models based on Indian Ocean yellowfin tuna and Ross Sea Antarctic toothfish dynamics. Each team documented how assessment software platform, data analyses, model building approach, and diagnostics influenced model complexity and realism. A consensus emerged on key assessment building approaches: (1) conduct high‐resolution data analyses to identify appropriate spatial structure; (2) start with simplified models and incrementally add complexity; (3) iteratively evaluate diagnostics to determine necessary spatial complexity; and (4) maintain models with different spatial structures to aid interpretation. The experiment also revealed several valuable insights for parameterising assessments, including consideration of data pre‐processing with spatiotemporal models to better inform data‐sparse regions; regression trees to identify fleet and spatial structure; trade‐offs in complexity between productivity and movement dynamics to achieve tractable and stable model structures; and ensemble modelling approaches to address structural uncertainty. Our findings demonstrate that international collaborations and simulation experiments are crucial for addressing challenges in implementing spatial stock assessments and for evaluating whether their added complexity is justified given management objectives. Broader collaborations are encouraged to foster innovation in fisheries management and to help recognise the practical trade‐offs between model parsimony and complexity.

Unravelling Ovarian Cancer: an analysis of the Influence of LRP1 and PAI1 Genetic Variations - R. B. Devi Krishna; Sneha Grace Mathews; Preet Agarwal; C. Elizabeth Rani; Nandini Krishnamurthy; Sanjana Murali; A. Lohitha Rani; Leena Dennis Joseph; Banukeerthana Rajasekaran; F. Andrea Mary (Biochemical Genetics, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Organic and inorganic carbon stocks in seagrass sediments of Mauritius - Sundy Ramah; Mathew A. Vanderklift; Mark S. Wilson (Science of The Total Environment, 2026)

Urban greening and water strategies are key to adapt Australian cities to climate change and urban growth - Valentina Marchionni; Christopher Szota; Claire Farrell; Stephen J. Livesley; Kerry A. Nice; Veljko Prodanovic; Sally Thompson; Pui Kwan Cheung; Hamideh Nouri; Mathew Lipson; Brandon Winfrey (Journal of Hydrology, 2026)

Food web dynamics drive variation in Smallmouth Bass Micropterus dolomieu mercury contamination in protected Southern Appalachian streams - Zachary Winston Clark; Augustin Clark Engman; Teresa Joan Mathews; Matthew A. Kulp; Mark Quentin Wilber; Peijia Ku; Nikki Jean Jones (Hydrobiologia, 2026)

Limited site-specific blue carbon recovery following tropical seagrass restoration in Thailand - Ratchanee Kaewsrikhaw; Milica Stankovic; Pere Masqué; Mathew A. Vanderklift; Tipamat Upanoi; Anchana Prathep (Marine Environmental Research, 2026)

The influence of postfire root strength decay on shallow landslide susceptibility in western Oregon - David F. M. Sousa; Erik Fulmer; Maryn A. Sanders; Nicolas W. Mathews; Joshua J. Roering; Francis K. Rengers; Benjamin B. Mirus; William J. Burns; Michael J. Olsen; Ben A. Leshchinsky (Landslides, 2026)

Development of Indirect Tensile Strength (ITS) model and resilient modulus assessment considering moisture conditions on bituminous mixtures - A. Jegan Bharath Kumar; V. Sunitha; R. T. Arjun Siva Rathan; Samson Mathew (Innovative Infrastructure Solutions, 2026)

Unraveling breast cancer risk with a focus on menopausal status: a large case–control study - Jini Sara Jacob; Preethi Sara George; Beela Sarah Mathew; Rekha A. Nair; Aleyamma Mathew (Cancer Causes & Control, 2026)

Assessment of contaminant concentrations and nutritional value of New Caledonian seaweeds - Laura Lagourgue; Claude E. Payri; Mayalen Zubia; Vincent Robert; Matthieu Waeles; Mathew A. Vanderklift; Andy Steven; Lydiane Mattio (Marine Pollution Bulletin, 2025)

Prevention of Browning and Enhanced In Vitro Organogenesis Mediated by Ascorbic Acid in Piper sarmentosum Roxb. - Stephin S.; A. Gangaprasad; Sam P. Mathew (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2025)

Dietary co-supplementation of Pediococcus acidilactici and bergamot essential oil improves growth, immune response, and disease resistance in sea bream (Sparus aurata) - Roshmon Thomas Mathew; Yousef Ahmed Alkhamis; Ahmed Saud Alsaqufi; Abdallah Tageldein Mansour; Hesham Abdallah Hassanien; Abdullah Sheikh; Huda Ahmad Alamer; Hailah M. Almohaimeed; Ehab El-Haroun; El-Sayed Hemdan Eissa; Sameh A. Abdelnour (Aquaculture International, 2025)

Effects of quadric probiotic blend supplementation on growth, biochemical markers, organ histology, immunity, antioxidant status, and gene expression in Nile tilapia (Oreochromis niloticus) - Roshmon Thomas Mathew; Yousef Ahmed Alkhamis; Ahmed Saud Alsaqufi; Abdallah Tageldein Mansour; Ouda Nasser Aldakhillalla; Mohamed Shawky El Sayed; Layla A. Almutairi; Zulhisyam Abdul Kari; Abdelazeem M. Algammal; Helal F. Hetta; Moaheda E. H. Eissa; El-Sayed Hemdan Eissa (Aquaculture International, 2025)

Potential symbiotic effects of date palm seed extract on growth, immunity, antioxidant activities, gut microbiota, expression levels, and Vibrio parahaemolyticus resistance in Shrimp - Roshmon Thomas Mathew; Nashi K. Alqahtani; Hesham S. Ghazzawy; Ehab El-Haroun; Yousef Ahmed Alkhamis; Abdallah Tageldein Mansour; Nagarajan Ganesan; Amel M. El Asely; Layla A. Almutairi; Zulhisyam Abdul Kari; Moaheda E. H. Eissa; El-Sayed Hemdan Eissa (Frontiers in Marine Science, 2025)
Date Palm Seed Extract (DPSE) is known to possess beneficial health-promoting and growth-boosting properties, but its specific influence on whiteleg shrimp ( Litopenaeus vannamei) health and physiology has yet to be fully explored. Hence, this study examined how dietary DPSE inclusion impacted growth performance, antioxidant status, immune response, hepatic tissue health, inflammation-related gene expression, and resistance to Vibrio parahaemolyticus in shrimp. The study involved four experimental groups of shrimps that were fed diets with varying DPSE inclusions: 0 (DPSE0), 1 (DPSE1), 2 (DPSE2), and 4 (DPSE4) g/kg diet over a 70-day period. The results indicated that dietary DPSE supplementation led to significantly higher (P<0.05) concentrations of whole-body composition (crude protein, gross energy, and crude lipid) in the treated groups. Conversely, the ash content was significantly reduced (P<0.05) in all DPSE-treated shrimp groups compared to the shrimp fed the control diet. Shrimp-fed DPSE-supplemented diets showed a significantly higher total hemocyte count (THC) compared to the control group (P<0.05). The levels of immunological parameters (phagocytosis, phenoloxidase, and lysozyme) and antioxidant status (superoxide dismutase and catalase) were significantly improved with increasing dietary DPSE levels, indicating a dose-dependent effect (P<0.01). The supplementation of DPSE at 1, 2, and 4 g in shrimp diets significantly improved the mRNA expression of immune-related genes ( LGBP, PX, PPA ) and antioxidant genes ( cytMnSOD , mtMnSOD ) compared to the control group (P<0.001). Both total aerobic bacteria and total enteric bacteria were significantly reduced in all DPSE-supplemented groups (P<0.05) compared to the control diet. Dietary inclusion of DPSE improved hepatopancreas tissues and significantly increased resistance to Vibrio parahaemolyticus in shrimp. The results indicate that the dietary inclusion of DPSE can enhance the growth, disease resistance, and overall health of shrimp by regulating immune function, antioxidant status, and immune associated genes regulation. This highlights its potential for sustainable and environmentally beneficial applications in aquaculture.

Dietary pterostilbene for improving the whiteleg shrimp (Litopenaeus vannamei): In vivo and in silico insights into growth, hemolymph physiology, redox state, immune function and resistance to Vibrio parahaemolyticus - Roshmon Thomas Mathew; Nashi K. Alqahtani; Hesham S. Ghazzawy; Layla A. Almutairi; Mohammed A. Alqahtani; Yousef Ahmed Alkhamis; Abdallah Tageldein Mansour; Nagarajan Ganesan; El-Sayed Hemdan Eissa; Sameh A. Abdelnour; Zulhisyam Abdul Kari; Fatma Mahsoub (Aquaculture International, 2025)

Supplementation of multi-strain probiotics in water enhances growth, metabolic responses, immune function, growth and immunity genes, and disease resistance in Nile tilapia (Oreochromis niloticus) - Roshmon Thomas Mathew; Yousef Ahmed Alkhamis; Ahmed Saud Alsaqufi; Abdallah Tageldein Mansour; Nagarajan Ganesan; Mahmoud Mabrok; Zulhisyam Abdul Kari; Moaheda E.H. Eissa; Layla A. Almutairi; El-Sayed Hemdan Eissa (Aquaculture International, 2025)

Ecological Risk–Benefit Analysis for Assisted Colonization - Rafael D'Andrea; György Barabás; Sarah E. Dalrymple; Wendy Foden; Piero Genovesi; Meghna Krishnadas; Mathew A. Leibold; Mark A. McPeek; Axel Moehrenschlager; Jon Paul Rodriguez; H. Reşit Akçakaya (Global Change Biology, 2025)
Assisted colonization (AC), translocating a species outside its indigenous range to avoid its extinction, is one of the few conservation options for some species. It is also controversial because of the history of ecological impacts of invasive species, including the extinction of native species as a result of novel ecological interactions resulting from the introduction. Although several national and international organizations have issued guidelines related to AC, none allow case‐specific decision‐making based on risks and benefits to biodiversity. We propose a two‐pronged approach to fill this gap. The first step aims to separate clear‐cut cases of AC from those that require an in‐depth risk analysis. We propose a set of seven qualitative criteria to identify AC projects that are clearly low‐risk and high‐benefit, and therefore should not be controversial, and those that are clearly high‐risk or low‐benefit and therefore should not be attempted. This identifies only the most obvious cases, leaving out many cases to be determined through a quantitative analysis to estimate the probabilities of extirpation of the resident species because of AC, which is the second step of our approach. We propose a roadmap for developing such a system based on community ecology theory, and a framework for considering the estimated probabilities in a global context. Our framework recommends an AC project only if it would result in a larger number of globally extant species than a scenario of no action. We propose large‐scale testing of the clear‐cut approach, further development of the quantitative approach, and wide consultation for adopting international guidelines for risk assessment of AC projects.

Impact of an Adapted Group Lifestyle Balance Program on Weight Loss and Physical Activity Uptake Among Adolescent Bariatric Surgery Patients - M. Misserian; F. Jackson; A. Wheelington; R. King; M. Mathew; M. Allicock; B. Cartwright; A. Chandrasekhar; D. Polavarapu; F. Qureshi; S. Barlow; S. Messiah (Journal of the Academy of Nutrition and Dietetics, 2025)

The efficacy and ecological impact of mercury sorbents on the physiology and reproductive fitness of Daphnia magna - S. Power; A. Minet; P. Ku; A. Sexton; P.G. Matson; J.P. Marquardt; Z.W. Clark; A. Johs; T.J. Mathews; L.M. Stevenson (Journal of Hazardous Materials, 2025)

Insights into airborne particulate matter: artificial intelligence-driven PM2.5 modelling in Hyderabad district, India - Nandan A K; Aneesh Mathew (Stochastic Environmental Research and Risk Assessment, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Correction to: Hip implant performance prediction by acoustic emission techniques: a review - Ampadi R. Remya; B. Vishwash; Christine Lee; P. Srinivasa Pai; Alejandro A. Espinoza Orías; Didem Ozevin; Mathew T. Mathew (Medical & Biological Engineering & Computing, 2025)

Investigation of geochemical distribution of heavy metals and their adsorption properties on River Benue sediment (Nigeria) - Mathew Imaji; Aloysius Akaangee Pam; Usman A. O. shuibu; O. W. Salawu (Journal of Sedimentary Environments, 2025)

Development of a rapid isothermal-based assay for detection of whitefly MEAM1 and MED biotypes using recombinase polymerase amplification - B. Megala Devi; Sivasudha Thilagar; A. Abdul Kader Jailani; Xavier Martini; Mathews L. Paret (Physiology and Molecular Biology of Plants, 2025)

Combining Observations and Models: A Review of the CARDAMOM Framework for Data‐Constrained Terrestrial Ecosystem Modeling - Matthew A. Worden; T. Eren Bilir; A. Anthony Bloom; Jianing Fang; Lily P. Klinek; Alexandra G. Konings; Paul A. Levine; David T. Milodowski; Gregory R. Quetin; T. Luke Smallman; Yinon M. Bar‐On; Renato K. Braghiere; et al. (Global Change Biology, 2025)
The rapid increase in the volume and variety of terrestrial biosphere observations (i.e., remote sensing data and in situ measurements) offers a unique opportunity to derive ecological insights, refine process‐based models, and improve forecasting for decision support. However, despite their potential, ecological observations have primarily been used to benchmark process‐based models, as many past and current models lack the capability to directly integrate observations and their associated uncertainties for parameterization. In contrast, data assimilation frameworks such as the CARbon DAta MOdel fraMework (CARDAMOM) and its suite of process‐based models, known as the Data Assimilation Linked Ecosystem Carbon Model (DALEC), are specifically designed for model‐data fusion. This review, motivated by a recent CARDAMOM community workshop, examines the development and applications of CARDAMOM, with an emphasis on its role in advancing ecosystem process understanding. CARDAMOM employs a Bayesian approach, using a Markov Chain Monte Carlo algorithm to enable data‐driven calibration of DALEC parameters and initial states (i.e., carbon pool sizes) through observation operators. CARDAMOM's unique ability to retrieve localized model process parameters from diverse datasets—ranging from in situ measurements to global satellite observations—makes it a highly flexible tool for analyzing spatially variable ecosystem responses to environmental change. However, assimilating these data also presents challenges, including data quality issues that propagate into model skill, as well as trade‐offs between model complexity, parameter equifinality, and predictive performance. We discuss potential solutions to these challenges, such as reducing parameter equifinality by incorporating new observations. This review also offers community recommendations for incorporating emerging datasets, integrating machine learning techniques, strengthening collaboration with remote sensing, field, and modeling communities, and expanding CARDAMOM's relevance for localized ecosystem monitoring and decision‐making. CARDAMOM enables a deep, mechanistic understanding of terrestrial ecosystem dynamics that cannot be achieved through empirical analyses of observational datasets or weakly constrained models alone.

Satellite tracking reveals sex-specific differences in the geographical and vertical habitat use of Whale sharks, Rhincodon typus, in the Eastern Indian ocean - Colby J. Bignell; Toby A. Patterson; Anthea Donovan; Mathew A. Vanderklift; Wayne Rochester; Jayson M. Semmens; Richard D. Pillans (Marine Biology, 2025)
Satellite tagging of whale sharks ( Rhincodon typus) has typically focused on juvenile males which dominate coastal aggregation sites, with limited data on the movements of females. We satellite-tagged 39 whale sharks of 3.75–9.27 m total length at Ningaloo reef between 2015 and 2018 with a roughly equivalent sex ratio (Male = 20, Female = 18, Unknown = 1).We aimed to identify differences in horizontal and vertical movements between the sexes using state-space models, kernel utilisation distributions (KUDs) and generalised additive models (GAMs). Deployment spans ranged from 9 to 340 days (mean = 132.4 ± SE = 17.9 days, N = 35) and 22 tracks exceeded 1000 km in length (mean = 2557 ± SE = 370 km, N = 35). Whale sharks spent > 90% of time in epipelagic waters ≤ 200 m and dived to a maximum depth of 1906 m. Sex-specific differences in horizontal and vertical movements were related to distinct temperature preferences. Females spent more time in offshore waters and preferred cooler Sea Surface Temperatures (SST) than males. Female movements were strongly influenced by increasing SSTs with greater space and depth use, while the space and depth use of males was more consistent with SSTs < 28 °C. We found no relationships between whale shark size and their space, depth or temperature use, though most individuals were immature (< 8 m, N = 24). The results provide novel evidence of sex-specific horizontal and vertical movements over broad geographical scales, extending current knowledge on the movement ecology and sex-specific demography of this endangered species.

Productivity Drives Leaf Mycobiome Diversity Patterns at Global and Continental Scales - Mathew A. Harris; Martin Kemler; Bernard Slippers; Nils Hassel; Joshua Tsamba; Watchara Arthan; Elizabeth A. Kellogg; Taylor AuBuchon‐Elder; Maria S. Vorontsova; Sally Archibald; Gareth P. Hempson; Caroline E. R. Lehmann; et al. (Global Ecology and Biogeography, 2025)
Aim Studies assessing large‐scale patterns of microbial diversity have predominantly focused on free‐living microorganisms, often failing to link observed patterns to established theories regarding the maintenance of global diversity patterns. We aimed to determine whether foliar fungi on two closely related grass hosts— Heteropogon contortus and Themeda triandra —display a commonly observed latitudinal gradient in species richness and determine whether host identity, energy (temperature and precipitation), climate seasonality, fire frequency and grass evolutionary history drive the observed patterns in species richness and composition. Location Paleotropical. Time Period Contemporary. Major Taxa Studied Foliar fungi. Methods Foliar fungal diversity was quantified from 201 leaf samples of T. triandra and H. contortus collected across the distributional range of these species. Mixed effects models were used to quantify patterns of diversity and their correlates among and within continents. Ordinations were used to assess drivers of composition. Results Foliar fungi displayed consistent latitudinal diversity gradients in richness. Energy was a strong driver of richness at inter‐continental and continental scales, while other factors had inconsistent impacts on richness among scales, hosts and guilds. Globally, richness was higher in regions of higher growing season temperatures and where hosts were present for longer periods. Composition was primarily structured by geographic region at the global scale, indicating that distance was a dominant driver of community composition. Within Australia, temperature and rainfall seasonality and the amount of growing season rainfall, were the dominant drivers of both richness and composition. Main Conclusions We find some support for the idea that foliar fungal species diversity is governed by the same factors as many macro‐organisms (energy availability and evolutionary history) at inter‐continental scales, but also that fungal diversity and composition in the highly seasonal continent of Australia were driven by factors that shape tropical grassy ecosystems, namely climate seasonality and fire.

Next generation Arctic vegetation maps: Aboveground plant biomass and woody dominance mapped at 30 m resolution across the tundra biome - Kathleen M. Orndahl; Logan T. Berner; Matthew J. Macander; Marie F. Arndal; Heather D. Alexander; Elyn R. Humphreys; Michael M. Loranty; Sarah M. Ludwig; Johanna Nyman; Sari Juutinen; Mika Aurela; Juha Mikola; et al. (Remote Sensing of Environment, 2025)

The combination of composted animal manure and plant growth-promoting rhizobacteria is a sustainable biofertilizer and bionematicide for grapevine (Vitis vinifera L.) cultivars - Osama M. M. Khder; Ramadan M. El-Ashry; Ahmed M. A. El-Deeb; Nahla A. Bouqellah; Mada F. Ashkan; Anas S. Dablool; Felwa A. Thagfan; Uthman B. Algopishi; Naheda M. Alshammari; Hawazen K. Al‑Gheffari; Ahmed M. Fikry; Mohamed T. El-Saadony; et al. (European Journal of Plant Pathology, 2025)
Root-knot nematodes (RKN) cause extensive damage to grapevine cultivars. RKN-resistant grapevine rootstocks remain vulnerable to biotic and abiotic stresses. This study aimed to determine the influence of composted animal manures (CAMs) [chicken manure (CM), cow manure (CowM), and sheep manure (SM)] with or without plant growth-promoting rhizobacteria (PGPR) on the population of Meloidogyne incognita , free-living nematodes (FLNs) and predaceous nematodes (PNs) residing in the soils of vineyard cultivars (Flame, Superior and Prime). The nematodes were isolated from grapevine roots and rhizosphere soils, then the absolute frequency of occurrence (FO), relative FO, prominence value (PV), and population density (PD) were assessed. The impact of CAMs and PGPR on the growth parameters, fruit output, and quality of three grapevine varieties was subsequently evaluated. Eight treatments included a control without CAMs or PGPR amendments, the CAMs alone, or CAM treatments combined with PGPR. The results showed that FLNs and PNs were more abundant in Prime than Flame or Superior cultivars when poor sandy loam soils were supplied with CAMs. Among all tested manures, CM was the best treatment as a nematicide. This was evident from the decreased numbers of M. incognita and increased numbers of FLNs and PNs in grapevine fields. Compared to the soil-applied oxamyl (a systemic nematicide), which was efficiently suppressive on M. incognita for two months, CM significantly ( P < 0.05) decreased PD of the phytonematodes for five months, improved soil structure and enhanced the soil biological activities. There were significant ( P < 0.05) increases in the number of leaves/vines by 79.9, 78.8, and 73.1%; and total fruit weight/vine by 76.9, 75.0, and 73.0% in Flame, Superior, and Prime varieties, respectively, compared to untreated vines. Regardless of the cultivar, soils amended with CM + PGPR achieved the lowest number of M. incognita among all other treatments, followed by SM + PGPR and CowM + PGPR. It was concluded that CAMs amendment, mainly CM, along with PGPR in poor sandy soils of temperate areas, is considered a sustainable approach for reducing parasitic nematodes and improving agricultural management.

Addressing global food security in Africa through training of next generation of researchers in plant pest diagnostics, in vitro culture, and clean plant production - Sadanand A. Dhekney; Simon Zebelo; Papaiah Sardaru; Purushothaman Natarajan; Stephan L. Tubene; Caleb Nindo; Lyna F. T. Mukwa; Mathews M. Dida; Moses T. Kairo (In Vitro Cellular & Developmental Biology - Plant, 2025)

The role of histological stains in aquaculture and fisheries development technology - El-Sayed Hemdan Eissa; Alkhateib Y. Gaafar; Roshmon Thomas Mathew; Eman A. Al-Shahari; Ekemini Moses Okon; Moaheda E. H. Eissa; Yasmin M. Abd El-Aziz (Aquaculture International, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Dose response effects of dietary clove and peppermint oils on the growth performance, physio-metabolic response, feed utilization, immunity, and organ histology in African catfish (clarias gariepinus) - Roshmon Thomas Mathew; Yousef Ahmed Alkhamis; Rashid Saleh Alngada; Raed Abdul Whed; Nouh Abdulaziz Aljaafari; Sameh A. Abdelnour; El-Sayed Hemdan Eissa; Zulhisyam Abdul Kari; Moaheda E. H. Eissa; Fatma Mahsoub (Veterinary Research Communications, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Impact of ingested microplastics on phenotypic traits and biochemical parameters in Nile tilapia (Oreochromis niloticus) juvenile - Sheikh Mustafizur Rahman; Fatima Tuz Zohora; Tania Sultana Mohona; Momotaz Khanom; Md. Moshiur Rahman; Md. Golam Sarower; Muhammad Abdur Rouf; Md. Nazrul Islam; Roshmon Thomas Mathew; Yousef Ahmed Alkhamis; Yousof Naser Alrashada; Lamya Ahmed Alkeridis; et al. (Aquaculture International, 2025)

Investigating the effects of Siraitia grosvenorii fruit on growth performance, immune response, antioxidant gene expression, and resistance to Vibrio parahaemolyticus in Litopenaeus vannamei shrimp - Roshmon Thomas Mathew; Nashi Khaled Alqahtani; Yousef Ahmed Alkhamis; Rashid Saleh Alngada; Raed Abdul Whed; Nouh Abdulaziz Aljaafari; Lamya Ahmed Alkeridis; El-Sayed Hemdan Eissa; Sameh A. Abdelnour; Moaheda E. H. Eissa; Fatma Mahsoub (Aquaculture International, 2025)

Transdisciplinary Collaborations for Advancing Sustainable and Resilient Agricultural Systems - Vesna Bacheva; Imani Madison; Mathew Baldwin; Justin Baker; Mark Beilstein; Douglas F. Call; Jessica A. Deaver; Kirill Efimenko; Jan Genzer; Khara Grieger; April Z. Gu; Mehmet Mert Ilman; et al. (Global Change Biology, 2025)
Feeding the growing human population sustainably amidst climate change is one of the most important challenges in the 21st century. Current practices often lead to the overuse of agronomic inputs, such as synthetic fertilizers and water, resulting in environmental contamination and diminishing returns on crop productivity. The complexity of agricultural systems, involving plant‐environment interactions and human management, presents significant scientific and technical challenges for developing sustainable practices. Addressing these challenges necessitates transdisciplinary research, involving intense collaboration among fields such as plant science, engineering, computer science, and social sciences. Five case studies are presented here demonstrating successful transdisciplinary approaches toward more sustainable water and fertilizer use. These case studies span multiple scales. By leveraging whole‐plant signaling, reporter plants can transform our understanding of plant communication and enable efficient application of water and fertilizers. The use of new fertilizer technologies could increase the availability of phosphorus in the soil. To accelerate advancements in breeding new cultivars, robotic technologies for high‐throughput plant screening in different environments at a population scale are discussed. At the ecosystem scale, phosphorus recovery from aquatic systems and methods to minimize phosphorus leaching are described. Finally, as agricultural outputs affect all people, integration of stakeholder perspectives and needs into research is outlined. These case studies highlight how transdisciplinary research and cross‐training among biologists, engineers, and social scientists bring diverse expertise to tackling grand challenges in sustainable agriculture, driving discovery and innovation.

Bio-inspired hydrophobicity in cellulose nanopaper via thermal-induced phase separation of beeswax: A new strategy to develop sustainable food packaging materials and its service life prediction - Ajith Mathew; Aiswarya Poulose; Anmiya Peter; Hiran Mayookh Lal; Arya Uthaman; Mohamed Shuaib Mohamed Saheed; Daniel Pasquini; Yves Grohens; Deepu A. Gopakumar; Jinu Jacob George (Food Packaging and Shelf Life, 2025)

Toward an integrated pantropical ocean observing system - Gregory R. Foltz; Yassir A. Eddebbar; Janet Sprintall; Antonietta Capotondi; Sophie Cravatte; Peter Brandt; Adrienne J. Sutton; Tamaryn Morris; Juliet Hermes; Clive R. McMahon; Michael J. McPhaden; Lev B. Looney; et al. (Frontiers in Marine Science, 2025)
Global climate is regulated by the ocean, which stores, releases, and transports large amounts of mass, heat, carbon, and oxygen. Understanding, monitoring, and predicting the exchanges of these quantities across the ocean’s surface, their interactions with the atmosphere, and their horizontal and vertical pathways through the global oceans, are key for advancing fundamental knowledge and improving forecasts and longer-term projections of climate, weather, and ocean ecosystems. The existing global observing system provides immense value for science and society in this regard by supplying the data essential for these advancements. The tropical ocean observing system in particular has been developed over decades, motivated in large part by the far-reaching and complex global impacts of tropical climate variability and change. However, changes in observing needs and priorities, new challenges associated with climate change, and advances in observing technologies demand periodic evaluations to ensure that stakeholders’ needs are met. Previous reviews and assessments of the tropical observing system have focused separately on individual basins and their associated observing needs. Here we provide a broader perspective covering the tropical observing system as a whole. Common gaps, needs, and recommendations are identified, and interbasin differences driven by socioeconomic disparities are discussed, building on the concept of an integrated pantropical observing system. Finally, recommendations for improved observations of tropical basin interactions, through oceanic and atmospheric pathways, are presented, emphasizing the benefits that can be achieved through closer interbasin coordination and international partnerships.

Educating healthcare workers in snakebite management: A study to determine the effectiveness of the snake bite life support workshop - Aravind Sreekumar; Siju V. Abraham; P.C. Rajeev; Vijay Chanchal A. B; Appu Suseel; Deo Mathew; Collin R. George; Babu U. Palatty (Toxicon, 2025)

Potential of dehydroepiandrosterone and quercetin to ameliorate copper oxide nanoparticles induced hepatotoxicity in albino wistar rats - Ahmed S. Ahmed; Liju S. Mathew; Asim S. Khan; Mark M. Rohn; Omaima K. Docmac; Pallav Sengupta; Ehab M. Hantash; Rasha A. Elsisy (Journal of Molecular Histology, 2025)

Characterization, Bio-Prospection, and Comparative Metagenomics of Bacterial Communities Revealing the Predictive Functionalities in Wild and Cultured Samples of Industrially Important Red Seaweed Gracilaria dura - Doniya Elze Mathew; Aastha Soni; Asmita Dhimmar; Apexa Gajjar; Ashutosh Shankar Parab; Sumit Sudhir Phakatkar; Harshal Sahastrabudhe; Cathrine Sumathi Manohar; Pramod B. Shinde; Vaibhav A. Mantri (Current Microbiology, 2025)

4-octyl itaconate improves water quality, growth, immunity, blood parameters, and disease resistance of Nile tilapia (Oreochromis niloticus) infected with Aeromonas hydrophila - Roshmon Thomas Mathew; Yousef Ahmed Alkhamis; Rashid Saleh Alngada; Raed Abdul Whed; Nouh Abdulaziz Aljaafari; El-Sayed Hemdan Eissa; Abdelazeem M. Algammal; Mohammad Bodrul Munir; Moaheda E. H. Eissa; Sameh A. Abdelnour (Aquaculture International, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Ecosystems managed for wildlife and livestock: Contrasting herbivore impacts in a heavily grazed African savanna - Michael D. Voysey; Sally Archibald; Mathew A. Harris; Gareth P. Hempson; Michelle Greve (Journal of Arid Environments, 2024)

The Escalating threat of climate change-driven diseases in fish: Evidence from a global perspective – A literature review - Ekemini Moses Okon; Adeola Ayotope Oyesiji; Ezekiel Damilola Okeleye; Mercy Kanonuhwa; Norhan E. Khalifa; El-Sayed Hemdan Eissa; Roshmon Thomas Mathew; Moaheda E.H. Eissa; Mohammed A. Alqahtani; Sameh A. Abdelnour (Environmental Research, 2024)

Acute Respiratory Syndrome Mimicking Shipping Sickness in Theileria buffeli Infected Buffalo Calf - Varghese Raina; Y. Ajith; Sasi Adithya; S. Anandu; N. Athira; K. S. Athira; P. Preena; K. Vinodkumar; K. Mathew Manju; C. S. Mahima; Jose Akshaya; B. Bruce Alby; et al. (Acta Parasitologica, 2024)

Optimizing tracking and completion of follow-up colonoscopy after abnormal stool tests at health systems participating in the Centers for Disease Control and Prevention’s Colorectal Cancer Control Program - Sujha Subramanian; Florence K. L. Tangka; Sonja Hoover; Anjali Mathews; Diana Redwood; Lauren Smayda; Esmeralda Ruiz; Rosario Silva; Victoria Brenton; Jane A. McElroy; Brooke Lusk; Susan Eason (Cancer Causes & Control, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Biodistribution and toxic potential of silver nanoparticles when introduced to the female rat reproductive tract - Nathan A. Koonce; Ammu Mathew; Ioana-Mihaela Popescu; Kelly Davis; Doug Wagner; Gokulan Kuppan; Mugimane Manjanatha; Julian E.A. Leakey; Anil K. Patri (NanoImpact, 2024)

Using Reported Intake and Skin Carotenoid Status to Understand Adolescents’ Perceptions About the Adequacy of Their Fruit and Vegetable Intake Characterized by the Stages of Change Transtheoretical Model - M. Badolato; K. Shelnutt; L. House; A. Mathews (Journal of the Academy of Nutrition and Dietetics, 2024)

Sunfish as zooplankton control agents to improve yields of wastewater-cultivated algae - Chase J. Rakowski; Mathew A. Leibold; Schonna R. Manning (Journal of Applied Phycology, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Development, Pharmacokinetics and Antimalarial Evaluation of Dose Flexible 3D Printlets of Dapsone for Pediatric Patients - Adnan A. Khan; Tahir Khuroo; Eman M Mohamed; Sathish Dharani; Kayalar Canberk; Xiaoyu Zhang; Lamba Omar Sangaré; Mathew A. Kuttolamadom; Allison C. Rice-Ficht; Ziyaur Rahman (AAPS PharmSciTech, 2024)

Design and Evaluation of Microemulsion-Based Drug Delivery Systems for Biofilm-Based Infection in Burns - Avirup Biswas; Jesil Mathew A; Shaila Angela Lewis; Selvaraj Raja; Arpita Paul; Kajal Ghosal; Syed Mahmood; Mohd Danish Ansari (AAPS PharmSciTech, 2024)
Normal skin is the first line of defense in the human body. A burn injury makes the skin susceptible to bacterial infection, thereby delaying wound healing and ultimately leading to sepsis. The chances of biofilm formation are high in burn wounds due to the presence of avascular necrotic tissue. The most common pathogen to cause burn infection and biofilm is Pseudomonas aeruginosa. The purpose of this study was to create a microemulsion (ME) formulation for topical application to treat bacterial burn infection. In the present study, tea tree oil was used as the oil phase, Tween 80 and transcutol were used as surfactants, and water served as the aqueous phase. Pseudo ternary phase diagrams were used to determine the design space. The ranges of components as suggested by the design were chosen, optimization of the microemulsion was performed, and in vitro drug release was assessed. Based on the characterization studies performed, it was found that the microemulsion were formulated properly, and the particle size obtained was within the desired microemulsion range of 10 to 300 nm. The I release study showed that the microemulsion followed an immediate release profile. The formulation was further tested based on its ability to inhibit biofilm formation and bacterial growth. The prepared microemulsion was capable of inhibiting biofilm formation. Graphical Abstract

Ecological impacts and management strategies of pesticide pollution on aquatic life and human beings - Synan F. AbuQamar; Mohamed T. El-Saadony; Samar S. Alkafaas; Mohamed I. Elsalahaty; Sara S. Elkafas; Betty T. Mathew; Amal N. Aljasmi; Hajar S. Alhammadi; Heba M. Salem; Taia A. Abd El-Mageed; Rashed A. Zaghloul; Walid F.A. Mosa; et al. (Marine Pollution Bulletin, 2024)

Exterior weak-axis beam-to-column bolted connections between GFRP I-shaped pultruded profiles using stainless steel cleats - Ajith Mathew; José A. Gonilha; Yashida Nadir; Yuyi Ye (Engineering Structures, 2024)

Bluish-white Light-emitting 2D Sheets of Lead-free Perovskite Cesium Titanium Bromide (CsTiBr3) by a Two-stage Deposition Technique - K A Benazeera Beegum; Saranya Sasi; Christeena Thomas; Alex Mathew; Reshmi Raman (Journal of Fluorescence, 2024)

Editorial: Marine Biotechnology and Bioproducts session of the 13th Asia-Pacific Marine Biotechnology Conference (13th APMBC) and 5th Australia New Zealand Marine Biotechnology Society Conference (5th ANZMBS) - Michael A. Packer; Jianguang Qin; Mathew Cumming (Frontiers in Marine Science, 2024)

Exercise protects the hypothalamus morphology from the deleterious effects of high sucrose diet consumption - Ahmed S. Ahmed; Liju S. Mathew; Marwa M. Mona; Omaima K. Docmac; Hoda A. Ibrahim; Amira M. Elshamy; Ehab M. Hantash; Rasha A. Elsisy (Journal of Molecular Histology, 2024)

Cannabis use in Parkinson’s disease: Patient access to medical cannabis and physician perspective on product safety - Symone T. Griffith; Kendra D. Conrow; Michael Go; Mindy L. McEntee; Raminta Daniulaityte; Majia H. Nadesan; Mathew R. Swinburne; Holly A. Shill; Maxwell C.K. Leung (NeuroToxicology, 2024)

Long-Term Follow-Up of Cerebral Aneurysms Completely Occluded at 6 Months After Intervention with the Woven EndoBridge (WEB) Device: a Retrospective Multicenter Observational Study - Kareem El Naamani; Panagiotis Mastorakos; Nimer Adeeb; Mathews Lan; James Castiglione; Omaditya Khanna; Jose Danilo Bengzon Diestro; Rachel M. McLellan; Mahmoud Dibas; Justin E. Vranic; Assala Aslan; Hugo H. Cuellar-Saenz; et al. (Translational Stroke Research, 2024)

Heliophysics Great Observatories and international cooperation in Heliophysics: An orchestrated framework for scientific advancement and discovery - Larry Kepko; Rumi Nakamura; Yoshifumi Saito; Angelos Vourlidas; Matthew G.G.T. Taylor; Cristina H. Mandrini; Xóchitl Blanco-Cano; Dibyendu Chakrabarty; Ioannis A. Daglis; Clezio Marcos De Nardin; Anatoli Petrukovich; Minna Palmroth; et al. (Advances in Space Research, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Novel community data in ecology-properties and prospects - Florian Hartig; Nerea Abrego; Alex Bush; Jonathan M. Chase; Gurutzeta Guillera-Arroita; Mathew A. Leibold; Otso Ovaskainen; Loïc Pellissier; Maximilian Pichler; Giovanni Poggiato; Laura Pollock; Sara Si-Moussi; et al. (Trends in Ecology & Evolution, 2024)

Biometeorological analysis on the molecular incidence of babesiosis and ehrlichiosis in dogs - Y. Ajith; Sasi Adithya; Varuna P. Panicker; N. Athira; V. Beena; M. Saifudeen Safeer; P. Preena; A. R. Nisha; C. Divya; S. G. Sangeetha; C. G. Umesh; R. C. Sundararajan; et al. (Theoretical and Applied Climatology, 2024)

Classification of circular polarization Stokes profiles in a sunspot using k-means clustering - Rohan Eugene Louis; Shibu K. Mathew; A. Raja Bayanna (Advances in Space Research, 2024)

Isolation of intake mediated effects demonstrate that the phenomic benefits of dietary omega-3 are nominal to Atlantic salmon when reared in a challenging (hypoxic) environment - Brett D. Glencross; Alex Berry; Ben Clokie; Ernst Hevroy; David Huyben; Laura Martinez-Rubio; Chessor A. Mathew; Pedro Munoz; Simon MacKenzie; Rod W. Wilson (Aquaculture, 2024)

A conditional mutation in a wheat (Triticum aestivum L.) gene regulating root morphology - Deying Zeng; Brett Ford; Jaroslav Doležel; Miroslava Karafiátová; Mathew J. Hayden; Tina M. Rathjen; Timothy S. George; Lawrie K. Brown; Peter R. Ryan; Filomena A. Pettolino; Ulrike Mathesius; Emmanuel Delhaize (Theoretical and Applied Genetics, 2024)
Key message Characterisation and genetic mapping of a key gene defining root morphology in bread wheat. Abstract Root morphology is central to plants for the efficient uptake up of soil water and mineral nutrients. Here we describe a conditional mutant of hexaploid wheat ( Triticum aestivum L.) that when grown in soil with high Ca 2+ develops a larger rhizosheath accompanied with shorter roots than the wild type. In wheat, rhizosheath size is a reliable surrogate for root hair length and this was verified in the mutant which possessed longer root hairs than the wild type when grown in high Ca 2+ soil. We named the mutant Stumpy and showed it to be due to a single semi-dominant mutation. The short root phenotype at high Ca 2+ was due to reduced cellular elongation which might also explain the long root hair phenotype. Analysis of root cell walls showed that the polysaccharide composition of Stumpy roots is remodelled when grown at non-permissive (high) Ca 2+ concentrations. The mutation mapped to chromosome 7B and sequencing of the 7B chromosomes in both wild type and Stumpy identified a candidate gene underlying the Stumpy mutation. As part of the process to determine whether the candidate gene was causative, we identified wheat lines in a Cadenza TILLING population with large rhizosheaths but accompanied with normal root length. This finding illustrates the potential of manipulating the gene to disconnect root length from root hair length as a means of developing wheat lines with improved efficiency of nutrient and water uptake. The Stumpy mutant will be valuable for understanding the mechanisms that regulate root morphology in wheat.

In Vitro and In Vivo testing of 3D-Printed Amorphous Lopinavir Printlets by Selective Laser Sinitering: Improved Bioavailability of a Poorly Soluble Drug - Canberk Kayalar; Nada Helal; Eman M. Mohamed; Sathish Dharani; Tahir Khuroo; Mathew A. Kuttolamadom; Ziyaur Rahman; Mansoor A. Khan (AAPS PharmSciTech, 2024)

Remedial effectiveness of a pond biomanipulation: Habitat value and concentrations of polychlorinated biphenyls in fish - Rebecca A. Efroymson; Mark J. Peterson; R. Trent Jett; Natalie A. Griffiths; Evin T. Carter; Allison M. Fortner; Christopher R. DeRolph; Peijia Ku; Paul G. Matson; Rachel M. Pilla; Teresa J. Mathews (Journal of Hazardous Materials, 2024)

Land use types determine environmental heterogeneity and aquatic insect diversity in Amazonian streams - Ana Paula Justino Faria; Raphael Ligeiro; Lenize B. Calvão; Xingli Giam; Mathew A. Leibold; Leandro Juen (Hydrobiologia, 2024)

Simulation of the effect of pulsatile flow on flow features dynamics during abrupt contraction into two parallel rectangular jets - Ayodeji A. Ala; Bin Ye; John Njoroge; Mathew Jayeola (Annals of Nuclear Energy, 2024)

Land surface and air temperature dynamics: The role of urban form and seasonality - Marzie Naserikia; Melissa A. Hart; Negin Nazarian; Benjamin Bechtel; Mathew Lipson; Kerry A. Nice (Science of The Total Environment, 2023)

Blue carbon assessments of seagrass and mangrove ecosystems in South and Southeast Asia: Current progress and knowledge gaps - Milica Stankovic; Amrit Kumar Mishra; Yusmiana P. Rahayu; Jonathan Lefcheck; Daniel Murdiyarso; Daniel A. Friess; Marko Corkalo; Teodora Vukovic; Mathew A. Vanderklift; Syed Hilal Farooq; Juan Diego Gaitan-Espitia; Anchana Prathep (Science of The Total Environment, 2023)

Unifying the validation of ambient solar wind models - Martin A. Reiss; Karin Muglach; Richard Mullinix; Maria M. Kuznetsova; Chiu Wiegand; Manuela Temmer; Charles N. Arge; Sergio Dasso; Shing F. Fung; José Juan González-Avilés; Siegfried Gonzi; Lan Jian; et al. (Advances in Space Research, 2023)

Simulations of ocean deoxygenation in the historical era: insights from forced and coupled models - Yohei Takano; Tatiana Ilyina; Jerry Tjiputra; Yassir A. Eddebbar; Sarah Berthet; Laurent Bopp; Erik Buitenhuis; Momme Butenschön; James R. Christian; John P. Dunne; Matthias Gröger; Hakase Hayashida; et al. (Frontiers in Marine Science, 2023)
Ocean deoxygenation due to anthropogenic warming represents a major threat to marine ecosystems and fisheries. Challenges remain in simulating the modern observed changes in the dissolved oxygen (O 2 ). Here, we present an analysis of upper ocean (0-700m) deoxygenation in recent decades from a suite of the Coupled Model Intercomparison Project phase 6 (CMIP6) ocean biogeochemical simulations. The physics and biogeochemical simulations include both ocean-only (the Ocean Model Intercomparison Project Phase 1 and 2, OMIP1 and OMIP2) and coupled Earth system (CMIP6 Historical) configurations. We examine simulated changes in the O 2 inventory and ocean heat content (OHC) over the past 5 decades across models. The models simulate spatially divergent evolution of O 2 trends over the past 5 decades. The trend (multi-model mean and spread) for upper ocean global O 2 inventory for each of the MIP simulations over the past 5 decades is 0.03 ± 0.39×1014 [mol/decade] for OMIP1, −0.37 ± 0.15×10 14 [mol/decade] for OMIP2, and −1.06 ± 0.68×10 14 [mol/decade] for CMIP6 Historical, respectively. The trend in the upper ocean global O 2 inventory for the latest observations based on the World Ocean Database 2018 is −0.98×10 14 [mol/decade], in line with the CMIP6 Historical multi-model mean, though this recent observations-based trend estimate is weaker than previously reported trends. A comparison across ocean-only simulations from OMIP1 and OMIP2 suggests that differences in atmospheric forcing such as surface wind explain the simulated divergence across configurations in O 2 inventory changes. Additionally, a comparison of coupled model simulations from the CMIP6 Historical configuration indicates that differences in background mean states due to differences in spin-up duration and equilibrium states result in substantial differences in the climate change response of O 2 . Finally, we discuss gaps and uncertainties in both ocean biogeochemical simulations and observations and explore possible future coordinated ocean biogeochemistry simulations to fill in gaps and unravel the mechanisms controlling the O 2 changes.

Fluid migration pathways to groundwater in mature oil fields: Exploring the roles of water injection/production and oil-well integrity in California, USA - Peter B. McMahon; Mathew K. Landon; Michael J. Stephens; Kim A. Taylor; Janice M. Gillespie; Tracy A. Davis; David H. Shimabukuro (Science of The Total Environment, 2023)

Advanced oxidation process (AOP) combined biological process for wastewater treatment: A review on advancements, feasibility and practicability of combined techniques - A. Babu Ponnusami; Sanyukta Sinha; Hridya Ashokan; Mathew V Paul; Sai Prashant Hariharan; J. Arun; K.P. Gopinath; Quynh Hoang Le; Arivalagan Pugazhendhi (Environmental Research, 2023)

Little change in surface sediment carbon stock following seagrass restoration in Shark Bay, Western Australia - Yusmiana P. Rahayu; Gary A. Kendrick; Matthew W. Fraser; Mathew A. Vanderklift (Estuarine, Coastal and Shelf Science, 2023)

Algal blooms in a river-dominated estuary and nearshore region of Florida, USA: the influence of regulated discharges from water control structures on hydrologic and nutrient conditions - E. J. Phlips; S. Badylak; A. L. Mathews; E. C. Milbrandt; L. R. Montefiore; E. S. Morrison; N. Nelson; B. Stelling (Hydrobiologia, 2023)
Flow-regulated discharges of water from control structures into estuaries result in hydrologic and water chemistry conditions that impact spatial and temporal variability in the structure and biomass of phytoplankton communities, including the potential for harmful algal blooms (HABs). The relationships between regulated Caloosahatchee River (i.e., C-43 Canal) discharges and phytoplankton communities in the Caloosahatchee Estuary and adjacent nearshore regions on the southwest coast of Florida were investigated during two study periods, 2009–2010 and 2018–2019. During periods of low to moderate discharge rates, when mesohaline conditions predominated in the estuary, and water residence times were comparatively long, major blooms of the HAB dinoflagellate species Akashiwo sanguinea were observed in the estuary. Periods of high discharge were characterized by comparatively low phytoplankton biomass in the estuary and greater influence of a wide range of freshwater taxa in the upper reaches. By contrast, intense blooms of the toxic dinoflagellate Karenia brevis in the nearshore region outside of the estuary were observed during high discharge periods in 2018–2019. The latter events were significantly associated with elevated levels of nitrogen in the estuary compared to lower average concentrations in the 2009–2010 study period. The relationships observed in this study provide insights into the importance of managing regulated discharge regimes to minimize adverse impacts of HABs on the health of the estuary and related coastal environments.

Vascular senescence and leak are features of the early breakdown of the blood–brain barrier in Alzheimer’s disease models - Ka Ka Ting; Paul Coleman; Hani Jieun Kim; Yang Zhao; Jocelyne Mulangala; Ngan Ching Cheng; Wan Li; Dilini Gunatilake; Daniel M. Johnstone; Lipin Loo; G. Gregory Neely; Pengyi Yang; et al. (GeroScience, 2023)
Alzheimer’s disease (AD) is an age-related disease, with loss of integrity of the blood–brain barrier (BBB) being an early feature. Cellular senescence is one of the reported nine hallmarks of aging. Here, we show for the first time the presence of senescent cells in the vasculature in AD patients and mouse models of AD. Senescent endothelial cells and pericytes are present in APP/PS1 transgenic mice but not in wild-type littermates at the time of amyloid deposition. In vitro, senescent endothelial cells display altered VE-cadherin expression and loss of cell junction formation and increased permeability. Consistent with this, senescent endothelial cells in APP/PS1 mice are present at areas of vascular leak that have decreased claudin-5 and VE-cadherin expression confirming BBB breakdown. Furthermore, single cell sequencing of endothelial cells from APP/PS1 transgenic mice confirms that adhesion molecule pathways are among the most highly altered pathways in these cells. At the pre-plaque stage, the vasculature shows significant signs of breakdown, with a general loss of VE-cadherin, leakage within the microcirculation, and obvious pericyte perturbation. Although senescent vascular cells were not directly observed at sites of vascular leak, senescent cells were close to the leak area. Thus, we would suggest in AD that there is a progressive induction of senescence in constituents of the neurovascular unit contributing to an increasing loss of vascular integrity. Targeting the vasculature early in AD, either with senolytics or with drugs that improve the integrity of the BBB may be valid therapeutic strategies.

Evaluating Participant Recipe Changes in a Healthy Meal Kit Intervention for Families with Low Income - E. McNulty; K. Chambers; R. Zambrano; I. Ramirez; A. Mitchell; L. House; A. Mathews; K. Shelnutt (Journal of the Academy of Nutrition and Dietetics, 2023)

Evaluation of nutraceutical property of extruded breakfast cereal produced from blends of malted finger millet (Eleusine coracana) and watermelon (Citrullus lanatus) seed flour - Joseph Oghenewogaga Owheruo; Great Iruoghene Edo; Beatrice Olawumi Ifesan; Mathew Kolawole Bolade; Babawade A. Origbemisoye; Patrick Othuke Akpoghelie; Joy Johnson Agbo (Vegetos, 2023)

Adherence to a Mediterranean-style Diet Is Associated with Decreased Depression and Anxiety Severity Regardless of Food Security Status: a Cross-sectional Study of College Freshmen - M. Alshahwan; A. Mathews; A. Ahrens; E. Triplett; L. LaMontagne; J. Doty; J. Colee (Journal of the Academy of Nutrition and Dietetics, 2023)

Higher Fat Intake Within a Vegan Diet Increases Skin Carotenoid Status in Patients at Risk for Cardiovascular Disease Participating in a Culinary Medicine Randomized Crossover Trial - A. Krenek; A. Courville; S. Chung; M. Aggarwal; A. Mathews (Journal of the Academy of Nutrition and Dietetics, 2023)

Adolescents’ Knowledge of Myplate as It Relates to Their Consumption of Fruits, Vegetables, and Whole Grains - M. Badolato; A. Mathews; K. Shelnutt; L. House; K. Chambers; J. Colee (Journal of the Academy of Nutrition and Dietetics, 2023)

The production-protection nexus: How political-economic processes influence prospects for transformative change in human-wildlife interactions - Robert Fletcher; Kate Massarella; Katia M.P.M.B. Ferraz; Wilhelm A. Kiwango; Sanna Komi; Mathew B. Mabele; Silvio Marchini; Anja Nygren; Laila T. Sandroni; Peter S. Alagona; Alex McInturff (Global Environmental Change, 2023)

Prenatal ambient air pollutant mixture exposure and neurodevelopment in urban children in the Northeastern United States - Yueh-Hsiu Mathilda Chiu; Ander Wilson; Hsiao-Hsien Leon Hsu; Harris Jamal; Nicole Mathews; Itai Kloog; Joel Schwartz; David C. Bellinger; Naim Xhani; Robert O. Wright; Brent A. Coull; Rosalind J. Wright (Environmental Research, 2023)

Combining hydro-acoustics and hydraulic modeling for evaluating fish entrainment risk - Weiwei Yao; David Z. Zhu; Mathew T. Langford; James A. Crossman; Pengcheng Li; Alf Leake; Eric Parkinson (Ecological Engineering, 2023)

Performance evaluation and yield optimization of L-glutaminase free L-asparaginase from seaweed-associated bacteria - Doniya Elze Mathew; Anjana K. Vala; Ramalingam Dineshkumar; Jayashree Niharika; Ravindra Pal Singh; Pramod B. Shinde; Vaibhav A. Mantri (Bioresource Technology Reports, 2023)

Potential utility of industrially unwanted constituent under the framework of waste to wealth: Edible salt from commercial marine red seaweed Kappaphycus alvarezii (Doty) L.M. Liao - Bhagirath Rakhasiya; Shanmugam Munisamy; Doniya Elze Mathew; Srinu Tothadi; Anshul Yadav; Vaibhav A. Mantri (Bioresource Technology Reports, 2023)

Peroxisomal KAT2 (3-ketoacyl-CoA thiolase 2) gene has a key role in gingerol biosynthesis in ginger (Zingiber officinale Rosc.) - S. Sreeja; M. R. Shylaja; P. A. Nazeem; Deepu Mathew (Journal of Plant Biochemistry and Biotechnology, 2023)

John squire and endothelial glycocalyx structure: an unfinished story - Kenton P. Arkill; C. Charles Michel; Elizabeth V. M. Rider; Elise A. Wood; Mathew O. Small; Jennifer L. E. Brown; Abigail L. Kinnaird (Journal of Muscle Research and Cell Motility, 2023)
John Squire did not only produce leading works in the muscle field, he also significantly contributed to the vascular permeability field by ultrastructural analysis of the endothelial glycocalyx. Presented here is a review of his involvement in the field by his main collaborator C.C. Michel and his last postdoctoral researcher KP Arkill. We end on a reinterpretation of his work that arguably links to our current understanding of endothelial glycocalyx structure and composition predicting 6 glycosaminoglycans fibres per syndecan core protein, only achieved in the endothelium by dimerization.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Preparation and Characterization of 3D-Printed Dose-Flexible Printlets of Tenofovir Disoproxil Fumarate - Canberk Kayalar; Ziyaur Rahman; Eman M. Mohamed; Sathish Dharani; Tahir Khuroo; Nada Helal; Mathew A. Kuttolamadom; Mansoor A. Khan (AAPS PharmSciTech, 2023)

Seascape configuration influences big blue octopus (Octopus cyanea) catches: Implications for a sustainable fishery - Mathew O. Silas; Mary A. Kishe; Masumbuko R. Semba; Bigeyo N. Kuboja; Benjamin Ngatunga; Said S. Mgeleka; Hans W. Linderholm; Martin Dahl; Martin Gullström (Fisheries Research, 2023)

Post-fire and harvest legacy on soil carbon and microbial communities in boreal forest soils - Charlotte E. Norris; Sylvie A. Quideau; Se-Woung Oh; Mathew J.B. Swallow; Barbara E. Kishchuk (Forest Ecology and Management, 2023)

Isotopic niche of New Jersey terrapins suggests intraspecific resource partitioning, and little variability following a major hurricane - Mathew J. Denton; Kristen M. Hart; John Wnek; Sarah A. Moss; Harold W. Avery (Hydrobiologia, 2023)
Diamondback terrapins ( Malaclemys terrapin ) are sexually dimorphic generalist turtles that inhabit salt marshes and estuaries along the Atlantic and Gulf coasts of the United States. On October 29th, 2012, Hurricane Sandy made landfall in New Jersey, USA, directly impacting terrapin populations inhabiting central and southern Barnegat Bay. To examine potential food web mediated impacts to the terrapin population and their foraging dynamics we examined carbon and nitrogen stable isotope values collected from terrapin tissues (2011, 2015, 2019) and resource taxa (2015, 2019) within Barnegat Bay. Isotopic analysis revealed that mature females had lower carbon and higher nitrogen values than immature females and males with almost no isotopic niche overlap, whereas males and immature females had statistically similar values with overlapping niches. Terrapins and resources collected from island habitats contained higher carbon and nitrogen values than those from mainland habitats, with little overlap in niche between habitats. There were no significant temporal variations detected in either carbon or nitrogen values from terrapins between years, or within each habitat pre- and post-Hurricane Sandy. These findings suggest long-term terrapin foraging dynamics have remained relatively stable, signifying resilience to disturbance events within the study site.

3D bioprinted scaffolds for diabetic wound-healing applications - Katie Glover; Essyrose Mathew; Giulia Pitzanti; Erin Magee; Dimitrios A. Lamprou (Drug Delivery and Translational Research, 2023)
The treatment strategy required for the effective healing of diabetic foot ulcer (DFU) is a complex process that is requiring several combined therapeutic approaches. As a result, there is a significant clinical and economic burden associated in treating DFU. Furthermore, these treatments are often unsuccessful, commonly resulting in lower-limb amputation. The use of drug-loaded scaffolds to treat DFU has previously been investigated using electrospinning and fused deposition modelling (FDM) 3D printing techniques; however, the rapidly evolving field of bioprinting is creating new opportunities for innovation within this research area. In this study, 3D-bioprinted scaffolds with different designs have been fabricated for the delivery of an antibiotic (levoflocixin) to DFU. The scaffolds were fully characterised by a variety of techniques (e.g. SEM, DSC/TGA, FTIR, and mechanical characterisation), demonstrating excellent mechanical properties and providing sustained drug release for 4 weeks. This proof of concept study demonstrates the innovative potential of bioprinting technologies in fabrication of antibiotic scaffolds for the treatment of DFU. Graphical abstract

Optimization of FDM 3D printing process parameters to produce haemodialysis curcumin-loaded vascular grafts - Sara Basile; Essyrose Mathew; Ida Genta; Bice Conti; Rossella Dorati; Dimitrios A. Lamprou (Drug Delivery and Translational Research, 2023)
3D printing has provided a new prospective in the manufacturing of personalized medical implants, including fistulas for haemodialysis (HD). In the current study, an optimized fused modelling deposition (FDM) 3D printing method has been validated, for the first time, to obtain cylindrical shaped fistulas. Printing parameters were evaluated for the manufacturing of fistulas using blank and 0.25% curcumin-loaded filaments that were produced by hot melt extrusion (HME). Four different fistula types have been designed and characterized using a variety of physicochemical characterization methods. Each design was printed three times to demonstrate printing process accuracy considering outer and inner diameter, wall thickness, width, and length. A thermoplastic polyurethane (TPU) biocompatible elastomer was chosen, showing good mechanical properties with a high elastic modulus and maximum elongation, as well as stability at high temperatures with less than 0.8% of degradation at the range between 25 and 250 °C. Curcumin release profile has been evaluated in a saline buffer, obtaining a low release (12%) and demonstrating drug could continue release for a longer period, and for as long as grafts should remain in patient body. Possibility to produce drug-loaded grafts using one-step method as well as 3D printing process and TPU filaments containing curcumin printability has been demonstrated. Graphical abstract

Long-term solar variability: ISWAT S1 cluster review for COSPAR space weather roadmap - Alexei A. Pevtsov; Dibyendu Nandy; Ilya Usoskin; Alexander A. Pevtsov; Claudio Corti; Laure Lefèvre; Mathew Owens; Gang Li; Natalie Krivova; Chitradeep Saha; Barbara Perri; Allan S. Brun; et al. (Advances in Space Research, 2023)

Towards a global Fishing Vessel Ocean Observing Network (FVON): state of the art and future directions - Cooper Van Vranken; Julie Jakoboski; John W. Carroll; Christopher Cusack; Patrick Gorringe; Naoki Hirose; James Manning; Michela Martinelli; Pierluigi Penna; Mathew Pickering; A. Miguel Piecho-Santos; Moninya Roughan; et al. (Frontiers in Marine Science, 2023)
Ocean observations are the foundation of our understanding of ocean processes. Improving these observations has critical implications for our ability to sustainably derive food from the ocean, predict extreme weather events that take a toll on human life, and produce the goods and services that are needed to meet the needs of a vast and growing population. While there have been great leaps forward in sustained operational monitoring of our oceans there are still key data gaps which result in sub-optimal ocean management and policy decisions. The global fishing industry represents a vast opportunity to create a paradigm shift in how ocean data are collected: the spatio-temporal extent of ocean data gaps overlaps significantly with fishers’ activities; fishing vessels are suitable platforms of opportunity to host communications and sensor equipment; and many fishing vessels effectively conduct a depth-profile through the water column in the course of normal fishing activities, representing a powerful subsurface data collection opportunity. Fishing vessel-collected ocean data can complement existing ocean observing networks by enabling the cost-effective collection of vast amounts of subsurface ocean information in data-sparse regions. There is an emerging global network of fishing vessels participating in collaborative efforts to collect oceanographic data accelerated by innovations in enabling technologies. While there are clear opportunities that arise from partnering with fishing vessels, there are also challenges ranging from geographic and cultural differences in fleets, fishing methods and practices, data processing and management for heterogeneous data, as well as long term engagement of the fishers. To advance fishing vessel-based ocean observation on a global scale, the Fishing Vessel Ocean Observing Network (FVON) aims to maximize data value, establish best practices around data collection and management, and facilitate observation uptake. FVON’s ultimate goals are to foster collaborative fishing vessel-based observations, democratize ocean observation, improve ocean predictions and forecasts, promote sustainable fishing, and power a data-driven blue economy.

Genome‐wide variant analyses reveal new patterns of admixture and population structure in Australian dingoes - Kylie M. Cairns; Mathew S. Crowther; Heidi G. Parker; Elaine A. Ostrander; Mike Letnic (Molecular Ecology, 2023)
Admixture between species is a cause for concern in wildlife management. Canids are particularly vulnerable to interspecific hybridisation, and genetic admixture has shaped their evolutionary history. Microsatellite DNA testing, relying on a small number of genetic markers and geographically restricted reference populations, has identified extensive domestic dog admixture in Australian dingoes and driven conservation management policy. But there exists a concern that geographic variation in dingo genotypes could confound ancestry analyses that use a small number of genetic markers. Here, we apply genome‐wide single‐nucleotide polymorphism (SNP) genotyping to a set of 402 wild and captive dingoes collected from across Australia and then carry out comparisons to domestic dogs. We then perform ancestry modelling and biogeographic analyses to characterise population structure in dingoes and investigate the extent of admixture between dingoes and dogs in different regions of the continent. We show that there are at least five distinct dingo populations across Australia. We observed limited evidence of dog admixture in wild dingoes. Our work challenges previous reports regarding the occurrence and extent of dog admixture in dingoes, as our ancestry analyses show that previous assessments severely overestimate the degree of domestic dog admixture in dingo populations, particularly in south‐eastern Australia. These findings strongly support the use of genome‐wide SNP genotyping as a refined method for wildlife managers and policymakers to assess and inform dingo management policy and legislation moving forwards.

Toward an understanding of civic engagement capacities within a municipal civic participation system - Melissa A. Mathews (The Social Science Journal, 2023)

Progesterone-stimulated endometrial cell conditioned media increases in vitro produced bovine embryo blastocyst formation - Mary A. Oliver; Katie D. Peterson; Sadikshya Bhandari; Rebecca R. Payton; J. Lannett Edwards; Daniel J. Mathew (Animal Reproduction Science, 2023)

Genetic basis of ecologically relevant body shape variation among four genera of cichlid fishes - Leah DeLorenzo; Destiny Mathews; A. Allyson Brandon; Mansi Joglekar; Aldo Carmona Baez; Emily C. Moore; Patrick J. Ciccotto; Natalie B. Roberts; Reade B. Roberts; Kara E. Powder (Molecular Ecology, 2023)
Divergence in body shape is one of the most widespread and repeated patterns of morphological variation in fishes and is associated with habitat specification and swimming mechanics. Such ecological diversification is the first stage of the explosive adaptive radiation of cichlid fishes in the East African Rift Lakes. We use two hybrid crosses of cichlids ( Metriaclima sp . × Aulonocara sp. and Labidochromis sp . × Labeotropheus sp., >975 animals total) to determine the genetic basis of body shape diversification that is similar to benthic‐pelagic divergence across fishes. Using a series of both linear and geometric shape measurements, we identified 34 quantitative trait loci (QTL) that underlie various aspects of body shape variation. These QTL are spread throughout the genome, each explaining 3.2–8.6% of phenotypic variation, and are largely modular. Further, QTL are distinct both between these two crosses of Lake Malawi cichlids and compared to previously identified QTL for body shape in fishes such as sticklebacks. We find that body shape is controlled by many genes of small effect. In all, we find that convergent body shape phenotypes commonly observed across fish clades are most likely due to distinct genetic and molecular mechanisms.

Growth conditions impact particulate absorption and pigment concentrations in two common bloom forming cyanobacterial species - Laura T. Kelly; Lisa Reed; Jonathan Puddick; Ian Hawes; Brendan J. Hicks; Mathew G. Allan; Moritz K. Lehmann; Susanna A. Wood (Harmful Algae, 2023)

Differential methylation between sex in adult green sea turtle skin biopsies - Benjamin Mayne; Walter Mustin; Vandanaa Baboolal; Francesca Casella; Katia Ballorain; Mathieu Barret; Mathew A. Vanderklift; Anton D. Tucker; Oliver Berry (Frontiers in Marine Science, 2023)
In marine turtles, the sex of hatchlings is determined by their egg incubation temperature. Global warming may increase the extinction risk by skewing hatchling sex ratios. Assessment of this risk at the population level requires the identification of sex in hatchlings and juveniles. However, available methods are typically lethal, highly invasive, or difficult to conduct at a large scale. Changes in DNA methylation, an epigenetic modification, have been characterized as part of sex differentiation pathways in some species with environmentally determined sex, but so far not in marine turtles. Neither have epigenetic biomarkers for sex been developed into rapid assays suited to research on wildlife. In this study, we aimed to develop a rapid, minimally invasive, and inexpensive method to identify the sex of marine turtles. We used reduced representation bisulfite sequencing DNA methylation data from adult green sea turtle ( Chelonia mydas ) skin biopsies to identify 16 genomic regions exhibiting differential methylation between males and females (adjusted p-value < 0.01). We designed methylation sensitive qPCR assays for these regions and tested their capacity to identify the sex of turtles ranging in age between 3-34 years. The qPCR assay identified the correct sex in turtles > 17 years. However, the sex of younger turtles could not be accurately identified. This suggests the sex differences distinguishable by the assay were adult specific, reflecting the training data on which the sex-specific regions were identified, and likely linked to late-stage ontogenetic changes associated with sexual maturity. Epigenetic biomarkers are a promising tool for wildlife research because they can be minimally invasive and high throughput. Future research into sex-specific differentially methylated regions in hatchlings and juveniles should be based on genome-wide DNA methylation data from a wider age range, which includes hatchlings.

Unraveling the Molecular Basis of Bacillus Megaterium Interactions in Rice for Plant Growth Promotion Through Proteomics and Gene Expression - S. R. Prabhukarthikeyan; C. Parameswaran; Shraddha Bhaskar Sawant; U. Keerthana; Manoj K. Yadav; S. Raghu; Mathew S. Baite; Arabinda Mahanty; P. Panneerselvam; A. Anandan; P. C. Rath (Journal of Plant Growth Regulation, 2023)

Development of DNA barcode-based PCR methodology to distinguish two sympatric species viz. Phlebotomus argentipes and Phlebotomus colabaensis (Diptera: Psychodidae: Phlebotominae) - P. A. Fathima; Harish Kumar Shah; P. M. Ajithlal; Jessu Mathew; N. Pradeep Kumar; Ashwani Kumar; Prasanta Saini (International Journal of Tropical Insect Science, 2023)

Geothermal energy production adversely affects a sensitive indicator species within sagebrush ecosystems in western North America - Peter S. Coates; Brian G. Prochazka; Shawn T. O'Neil; Sarah C. Webster; Shawn Espinosa; Mark A. Ricca; Steven R. Mathews; Michael Casazza; David J. Delehanty (Biological Conservation, 2023)

The relationship between single muscle fibre and voluntary rate of force development in young and old males - Benjamin E. Dalton; Nicole Mazara; Mathew I. B. Debenham; Derek P. Zwambag; Alex M. Noonan; Erin Weersink; Stephen H. M. Brown; Geoffrey A. Power (European Journal of Applied Physiology, 2023)

Total plasma magnesium, zinc, copper and selenium concentrations in obese patients before and after bariatric surgery - Stephen J. Hierons; Anthony Catchpole; Kazim Abbas; Wingzou Wong; Mathew S. Giles; Glenn V. Miller; Ramzi A. Ajjan; Alan J. Stewart (BioMetals, 2023)
Obesity enhances the risk of type-2 diabetes, cardiovascular disease and inflammatory conditions and often leads to metal dyshomeostasis, which contributes to the negative health aspects associated with the disease. In severe cases, bariatric surgery can be recommended to achieve sustained weight loss and improvement in health. Here, magnesium, zinc, copper and selenium concentrations were examined in 24 obese patients (7 males; 17 females) before and 9 months after undergoing Roux-en-Y gastric bypass surgery. All patients lost weight over this period, with the mean BMI reducing from 51.2±7.1 kg/m 2 to 37.2±5.5 kg/m 2 . Moreover, whole-blood glycated haemoglobin (HbA1c), as a marker of average glycaemia, was also measured and a correlative analysis of this parameter with metal concentrations performed. Significant alterations in the plasma concentrations of magnesium, zinc (both increased by 13.2% and 25.2% respectively) and copper (decreased by 7.9%) were observed over this period (plasma selenium concentration was unchanged), with BMI values correlating with plasma magnesium (p = 0.004) and zinc (p = 0.022) concentrations. At 9 months post-surgery, an increase in mean zinc/copper ratio was observed (0.86±0.29 compared to 0.63±0.14 pre-surgery). Comparison of whole-blood HbA1c concentrations pre- and post-surgery revealed a reduction from 6.50±1.28% pre-surgery to 5.51±0.49% post-surgery. Differences in plasma HbA1c and magnesium at either pre- and post-surgery correlated significantly, as did HbA1c and magnesium levels when pre- and post-surgery values were analysed together. Collectively, this work reveals that bariatric surgery, in conjunction with lifestyle/dietary changes, lead to improvements in the nutritional status of magnesium, zinc and copper. Furthermore, the observed improvements in magnesium and zinc were associated with weight loss and in the case of magnesium, to better glycaemic control.

Global net biome CO 2 exchange predicted comparably well using parameter–environment relationships and plant functional types - Caroline A. Famiglietti; Matthew Worden; Gregory R. Quetin; T. Luke Smallman; Uma Dayal; A. Anthony Bloom; Mathew Williams; Alexandra G. Konings (Global Change Biology, 2023)
Accurate estimation and forecasts of net biome CO 2 exchange (NBE) are vital for understanding the role of terrestrial ecosystems in a changing climate. Prior efforts to improve NBE predictions have predominantly focused on increasing models' structural realism (and thus complexity), but parametric error and uncertainty are also key determinants of model skill. Here, we investigate how different parameterization assumptions propagate into NBE prediction errors across the globe, pitting the traditional plant functional type (PFT)‐based approach against a novel top‐down, machine learning‐based “environmental filtering” (EF) approach. To do so, we simulate these contrasting methods for parameter assignment within a flexible model–data fusion framework of the terrestrial carbon cycle (CARDAMOM) at a global scale. In the PFT‐based approach, model parameters from a small number of select locations are applied uniformly within regions sharing similar land cover characteristics. In the EF‐based approach, a pixel's parameters are predicted based on underlying relationships with climate, soil, and canopy properties. To isolate the role of parametric from structural uncertainty in our analysis, we benchmark the resulting PFT‐based and EF‐based NBE predictions with estimates from CARDAMOM's Bayesian optimization approach (whereby “true” parameters consistent with a suite of data constraints are retrieved on a pixel‐by‐pixel basis). When considering the mean absolute error of NBE predictions across time, we find that the EF‐based approach matches or outperforms the PFT‐based approach at 55% of pixels—a narrow majority. However, NBE estimates from the EF‐based approach are susceptible to compensation between errors in component flux predictions and predicted parameters can align poorly with the assumed “true” values. Overall, though, the EF‐based approach is comparable to conventional approaches and merits further investigation to better understand and resolve these limitations. This work provides insight into the relationship between terrestrial biosphere model performance and parametric uncertainty, informing efforts to improve model parameterization via PFT‐free and trait‐based approaches.

Natural organic matter flocculation behavior controls lead phosphate particle aggregation by mono- and divalent cations - Juntao Zhao; Riya A. Mathew; David S. Yang; Peter G. Vekilov; Yandi Hu; Stacey M. Louie (Science of The Total Environment, 2023)

Sea swimming and snorkeling in tropical coastal blue spaces and mental well-being: Findings from Indonesian island communities during the COVID-19 pandemic - Carya Maharja; Radisti A. Praptiwi; Bethany R. Roberts; Karyn Morrissey; Mathew P. White; Nuzulia M. Sari; Fauzan Cholifatullah; Jito Sugardjito; Lora E. Fleming (Journal of Outdoor Recreation and Tourism, 2023)

Development of SpCas9-expressing bovine mammary epithelial cell lines - Alexander J. Trevarton; Emily R. Mears; Janelle Moody; Thomas J. Lopdell; Thaize Q. Chometon; John A. Taylor; Carol J. Wang; Mathew D. Littlejohn; Russell G. Snell (In Vitro Cellular & Developmental Biology - Animal, 2023)

Increasing intention to reduce fossil fuel use: a protection motivation theory-based experimental study - Emily J. Kothe; Mathew Ling; Barbara A. Mullan; Joshua J. Rhee; Anna Klas (Climatic Change, 2023)
Reducing individual fossil fuel use is an important component of climate change mitigation, but motivating behaviour change to achieve this is difficult. Protection motivation theory (PMT) is a psychological framework that outlines the conditions under which people are more likely to be persuaded to take a specific response or action. This experimental study investigated the impact six different protection motivation theory-based messages had on intention to reduce fossil fuel use in a sample 3803 US adults recruited via Amazon Mechanical (MTurk). Only messages targeting self-efficacy and response efficacy increased intention to reduce fossil fuel use relative to the control message. However, only the self-efficacy message had an impact on its target construct (i.e. self-efficacy). As such, the mechanism for action for the response efficacy message is unclear. Furthermore, while the current study demonstrates that many of the PMT-related messages did not achieve changes in intention, this it is still possible that messages targeting these constructs could still lead to changes in intention in other modalities and when other message content is used. Given the urgency of responding to climate change, the potential for additive benefits of combining effective PMT-based messages should be considered irrespective of their mechanism as should research focused on how to effectively target other key PMT constructs.

A Multicontinuum-Theory-Based Approach to the Analysis of Fiber-Reinforced Polymer Composites with Degraded Stiffness and Strength Properties Due to Moisture Absorption - Evan Anderson; Budi Gunawan; James Nicholas; Mathew Ingraham; Bernadette A. Hernandez-Sanchez (Journal of Marine Science and Engineering, 2023)
Marine energy generation technologies such as wave and tidal power have great potential in meeting the need for renewable energy in the years ahead. Yet, many challenges remain associated with marine-based systems because of the corrosive environment. Conventional materials like metals are subject to rapid corrosive breakdown, crippling the lifespan of structures in such environments. Fiber-reinforced polymer composites offer an appealing alternative in their strength and corrosion resistance, but can experience degradation of mechanical properties as a result of moisture absorption. An investigation is conducted to test the application of a technique for micromechanical analysis of composites, known as multicontinuum theory and demonstrated in past works, as a mechanism for predicting the effects of prolonged moisture absorption on the performance of fiber-reinforced composites. Experimental tensile tests are performed on composite coupons with and without prolonged exposure to a salt water solution to obtain stiffness and strength properties. Multicontinuum theory is applied in conjunction with micromechanical modeling to deduce the effects of moisture absorption on the behavior of constituent materials within the composites. The results are consistent with experimental observations when guided by known mechanisms and trends from previous studies, indicating multicontinuum theory as a potentially effective tool in predicting the long-term performance of composites in marine environments.

ASPECT Score and Its Application to Vasospasm in Aneurysmal Subarachnoid Haemorrhage: a Case–Control Study - Melissa Bautista; Rebecca Burger; Ian A. Anderson; Ryan K. Mathew (Translational Stroke Research, 2023)
Delayed cerebral ischaemia (DCI) is a significant complication of aneurysmal subarachnoid haemorrhage (aSAH) and is strongly associated with poorer outcome. The Alberta Stroke Program Early Computer Tomography (ASPECT) score is an established scoring tool, used in acute ischaemic stroke, to quantify early ischaemic changes on CT head scans. We aim to identify if ASPECT scoring correlates with functional outcome in DCI following aSAH. Retrospective case–control study. Inclusion criteria: admission to the Department of Neurosurgery at Leeds Teaching Hospitals NHS Trust (a tertiary neurosurgical centre in the United Kingdom) between 2014 and 2018, with a diagnosis of anterior circulation aneurysmal subarachnoid haemorrhage; as confirmed by initial CT scan and subsequent CT angiography or catheter digital subtraction angiography. Cases were those who developed DCI ( n = 43) and controls were randomly selected from those who did not develop DCI ( n = 46) but otherwise met the same inclusion criteria. The primary outcome measure was Glasgow Outcome Score (GOS): assessed at discharge and 3 months. ASPECT scores were calculated from non-contrast CT head scans by three researchers blinded to each other and clinical outcome. Spearman’s rank correlation was used to calculate correlation between ASPECT scores and GOS. ASPECT score positively correlated with GOS in the cases both at discharge (Spearman rho 0.436, p = 0.003) and at 3 months (Spearman rho 0.431, p = 0.004). When corrected for Fisher grading, the adjusted odds ratio of having a high GOS with a low ASPECT score at discharge was OR 0.74 (95% CI 0.61–0.94, p = 0.003), and 3 months OR 0.73 (95% CI 0.59–0.91, p = 0.005). ASPECT score significantly correlates with clinical outcome in DCI post aSAH, even after correcting for Fisher grade. ASPECT scoring may identify patients at risk of poor outcome following DCI and represents a quick and reliable tool that aids in clinical decision-making and prognostication.

Evaluation of the forecast skill of North American Multi‐Model Ensemble for monthly and seasonal precipitation forecasts over Iran - Amin Shirvani; Willem A. Landman; Mathew Barlow; Andrew Hoell (International Journal of Climatology, 2023)
North American Multi‐Model Ensemble (NMME) precipitation forecast skill over Iran is evaluated using Taylor diagrams and ranked probability skill scores (RPSS) as determined over a 29‐year test period (1991–2019). The forecast skill for both monthly (October through June for lead‐times of 0.5–3.5 months) and seasonal (October–December [OND], January–March [JFM], and April–June [AMJ] for lead‐times of 1.5–3.5 months) timescales is evaluated using six NMME models as well as multi‐model ensemble means (MMM). The latest versions of these models for forecasting Iran's precipitation have not been evaluated thus far. The Global Precipitation Climatology Center (GPCC) version 2020 dataset is used to verify the models. Among individual NMME models, Geophysical Fluid Dynamics Laboratory‐Seamless System for Prediction and Earth System Research (GFDL‐SPEAR) has generally the highest forecast skill. Both Taylor diagrams and RPSS of most of the models have indicated that the highest forecast skill is found for the month of November such that the Pearson correlation for both SPEAR and MMM is statistically significant for all lead‐times. For both monthly and seasonal timescales, the temporal Pearson correlation (TPC) between the observed and forecasts of the MMM is higher than the TPC of the individual models. The spatial Pearson correlation (SPC) and normalized centred root mean square error (NCRMSE) of the SPEAR is close to MMM, but the normalized standard deviation (NSD) of the SPEAR is closer to one compared to the MMM for months from November to March and two seasons (OND and JFM seasons). The MMM precipitation forecasts are underestimated over the northern regions and Zagros mountains for JFM and OND seasons for both 1.5‐ and 2.5‐month lead‐times. The degree to which the forecast skill of MMM is dependent on the El Niño–Southern Oscillation (ENSO) connections with precipitation over Iran is examined. Significant Spearman correlations between simultaneous observed Niño3.4 index and Iran precipitation are found for OND, but not for JFM and AMJ. The MMM reproduces the observed ENSO teleconnections to the tropical Pacific in OND, consistent with forecast skill in that season. However, the MMM also produces forecast skill in JFM and AMJ when the ENSO influence is marginal, showing that ENSO is not the only source of skill in the models.

Effects of radiation exposure on brain health: a state of the art and new challenges - Jayalakshmi Jayan; Harsha Roshi; Fathima Farzana Perumbilly Ashraf; Parvathy G. Nair; Aparna Vijayakumar; Aathira Sujathan Nair; Leena K. Pappachen; Mohamed A. Abdelgawad; Della Grace Thomas Parambi; Lotfi Aleya; Bijo Mathew (Environmental Science and Pollution Research, 2022)

Geochemical evolution of structure-bedding controlled hydrothermal dolomites of the Kinta Valley, Western Malaysia - P. Xin Hui; R. Nagarajan; Mu. Ramkumar; T. F. Ng; Nur I. Taib; M. J. Mathew; B. Sautter; N. A. Siddiqui; M. C. Poppelreiter (Carbonates and Evaporites, 2022)
Study of secondary dolomitization and documentation of the evolution of basinal fluids and host rock, especially that of fine-grained deepwater carbonate mudstone are of interest toward of reservoir characterization. From this perspective, field characteristics in relation to mineralogy, petrography and geochemistry of the Paleaozoic carbonates of the Kinta Valley, Peninsular Malaysia, were investigated and documented. A total of 33 samples were collected across the various degree of dolomitization and analyzed for their petrographic properties ( n = 55), while mineralogical and geochemical compositions ( n = 33) were analyzed using XRD, ICP and ICPMS analysis, respectively. These analyses were performed to elucidate the diagenetic events, episodic dolomitization and development of fluid evolution as a function of regional tectono-thermal events during the Permian to Cenozoic. It is interpreted that the host calcareous mudstones (HCMs) were deposited in oxygenated, open marine seawaters. The studied samples retain the original seawater characteristics despite negligible, minor alterations of REE characteristics due to diagenesis and detrital input. Though the concentrations and trends of REEs of the dolomitic facies are modified to a certain extent, their affinities with HCMs are preserved. Enrichments of Mg, Mn, Na and depletion of Sr are linked to the effect of dolomitization under the open system of diagenesis. The redox conditions fluctuated to show distinct, recognizable variations between different dolomite phases. The MREE enrichments with other trace elements such as Mn, Fe and low Sr content indicate the association of diagenetic fluids with deep-circulating crustal hydrothermal fluids. Hydrothermal influence has been recorded along the fractures, which might have originated from the sub-surface litho units and facilitated episodic dolomitization, especially during significant tectono-thermal events. This study affirms that the occurrence, geochemical and mineralogical evolution of the dolomites of the Kinta Valley were controlled by magmatic events, whereas the intensity of replacement dolomitization was controlled by host rock texture, varied bulk chemistry of host rock, circulating fluid and temperature.

A 10-miRNA risk score-based prediction model for pathological complete response to neoadjuvant chemotherapy in hormone receptor-positive breast cancer - Chang Gong; Ziliang Cheng; Yaping Yang; Jun Shen; Yingying Zhu; Li Ling; Wanyi Lin; Zhigang Yu; Zhihua Li; Weige Tan; Chushan Zheng; Wenbo Zheng; et al. (Science China Life Sciences, 2022)

Paleodepositional and Hydrocarbon Source-Rock Characteristics of the Sonari Succession (Paleocene), Barmer Basin, NW India: Implications from Petrography and Geochemistry - Vikram P. Singh; Bhagwan D. Singh; Runcie P. Mathews; Alpana Singh; Vinod A. Mendhe; Subhashree Mishra; Mollika Banerjee (Natural Resources Research, 2022)

Integrating blue: How do we make nationally determined contributions work for both blue carbon and local coastal communities? - Amrit Melissa Dencer-Brown; Robyn Shilland; Daniel Friess; Dorothée Herr; Lisa Benson; Nicholas J. Berry; Miguel Cifuentes-Jara; Patrick Colas; Ellyn Damayanti; Elisa López García; Marina Gavaldão; Gabriel Grimsditch; et al. (Ambio, 2022)
Blue Carbon Ecosystems (BCEs) help mitigate and adapt to climate change but their integration into policy, such as Nationally Determined Contributions (NDCs), remains underdeveloped. Most BCE conservation requires community engagement, hence community-scale projects must be nested within the implementation of NDCs without compromising livelihoods or social justice. Thirty-three experts, drawn from academia, project development and policy, each developed ten key questions for consideration on how to achieve this. These questions were distilled into ten themes, ranked in order of importance, giving three broad categories of people , policy & finance , and science & technology . Critical considerations for success include the need for genuine participation by communities, inclusive project governance, integration of local work into national policies and practices, sustaining livelihoods and income (for example through the voluntary carbon market and/or national Payment for Ecosystem Services and other types of financial compensation schemes) and simplification of carbon accounting and verification methodologies to lower barriers to entry.

Assessing neophobia and exploration while accounting for social context: an example application in scimitar-horned oryx - Katherine Mertes; Catherine A. Ressijac; Rosana N. Moraes; Lacey F. Hughey; Luisa H. Porto Alegre; Megan Horning; Tara Buk; Arielle Harwood; Lawrence Layman; Christopher Mathews; Morgan Vance; Dolores Reed; et al. (Mammalian Biology, 2022)
Spatial neophobia and exploration are often assessed in nonhuman animals by measuring behavioral responses to novel environments. These traits may especially affect the performance of individuals translocated to novel environments for conservation purposes. Here, we present methods to administer and analyze a minimally invasive novel environment test that accounts for the social context of focal individuals. We used an aerial platform to capture video footage of a captive herd of scimitar-horned oryx ( Oryx dammah ) entering an unfamiliar enclosure. We analyzed footage for seven individually identifiable oryx, scoring their behavioral responses (i.e., latency to enter the enclosure, and movement and posture after entering the enclosure) and social context (i.e., relative position and number of nearby animals). We performed a principal components analysis (PCA) to explore individual traits and responses, and used generalized linear mixed models (GLMMs) to determine the effect of individual traits and social context on individual posture and movement behaviors. Both PCA and GLMMs supported our expectation that social context affects individual behavior: high neighbor density and relative position were negatively related to individual movement, and variation in social context was positively related with head-up postures and movement. Oryx were well differentiated along two principal components that reflected (1) vigilance or caution, and (2) changing social context and age. These methods provide a framework for assessing individual responses to a novel environment in a group setting, which can inform reintroduction and wildlife management efforts, while minimizing interference with animal behavior and management operations.

Social integration of translocated wildlife: a case study of rehabilitated and released elephant calves in northern Kenya - Shifra Z. Goldenberg; Stephen M. Chege; Nelson Mwangi; Ian Craig; David Daballen; Iain Douglas-Hamilton; Nadine Lamberski; Moses Lenaipa; Reuben Lendira; Colman Lesowapir; Lekilia P. Lokooria; Mathew Mutinda; et al. (Mammalian Biology, 2022)
Conservation translocations have the potential to strengthen populations of threatened and endangered species, but facilitating integration of translocated individuals with resident populations remains a substantial challenge. Developing functional social relationships like cooperative partnerships or establishing clear dominance hierarchies may be critical to integration of released individuals. Developing such relationships has not received much attention in translocation research, especially for long-lived, socially complex animals for which establishment and navigation of social environments is often a lengthy process that requires sustained monitoring to understand. Here, we present a case study of the social associations of African savannah elephant ( Loxodonta africana ) calves that have been rehabilitated and released into a fenced wildlife sanctuary in northern Kenya with a resident population of elephants. We use focal follows of interactions pre-release and GPS tracking post-release to quantify social associations of calves with each other and with resident elephants at the release site. We demonstrate how this approach supports translocation monitoring by capturing temporal trends in social patterns within and between release cohorts and among released elephants and wild elephants already resident at the site during a transitional soft release period. Our results show that initial post-release social behavior of rehabilitated calves is related to histories of interaction with familiar individuals and cohort membership and that released calves increased their associations with residents over time. This information provides new behavioral insights for guiding elephant release projects, like the strength of relationships within and among release cohorts, the time to integration with the resident population, and the occurrence and increased incidence of societal fission–fusion. Further, this study provides an example of the utility of animal behavior research to achieve and assess progress towards conservation objectives, and to develop monitoring tools for conservation managers.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

A Guide to International Climate Mitigation Policy and Finance Frameworks Relevant to the Protection and Restoration of Blue Carbon Ecosystems - Mathew A. Vanderklift; Dorothée Herr; Catherine E. Lovelock; Daniel Murdiyarso; Jacqueline L. Raw; Andrew D. L. Steven (Frontiers in Marine Science, 2022)
The protection, management and restoration of vegetated ecosystems on land and in the ocean (‘natural climate solutions’) can be a useful strategy for reducing net greenhouse gas emissions to help limit global warming. Their potential contribution to reducing net emissions has led to the development of policies and financial incentives for their protection and restoration. These have in turn created a set of expectations among some stakeholders, and interest in expanding these to encompass other ecosystems. However, there are specific rules about how abatement is calculated in international policy and climate finance, and the frameworks and terminology associated with them are often complex. This can be a barrier to stakeholders who want to leverage the potential of natural climate solutions, sometimes leading to incongruence between realised and anticipated benefits. In this article, we attempt to outline some of the key international policy and carbon market frameworks for coastal ‘blue carbon’ ecosystems, and the extent to which different ecosystems are accommodated. Currently, among the coastal ecosystems, only mangrove forests, seagrass meadows, and tidal marshes are typically considered in international policy and carbon market frameworks. The defining feature of these ecosystems is that the foundation species are plants that grow in sediment (soil). They are the only coastal ecosystems currently included in IPCC guidelines for national greenhouse gas inventories, and in compliance and voluntary carbon markets. There is interest in potentially including other marine ecosystems, such as kelp forests and unvegetated tidal flats, into carbon accounting frameworks, but there are unresolved questions about whether sequestration and storage of carbon by these ecosystems meets the rigorous standards required. Voluntary carbon markets have greater flexibility than mechanisms linked to national greenhouse gas inventories, and so might be early implementers of expanding methods to include other ecosystems. Incorporating coastal ecosystems into national greenhouse gas inventory is a useful action countries can take that will likely help generate incentives for protection and restoration of these important ecosystems.

A Sensitive Spectrofluorimetric Method for Curcumin Analysis - Anne Boyina Sravani; Elizabeth Mary Mathew; Vivek Ghate; Shaila A Lewis (Journal of Fluorescence, 2022)
Curcumin (CUR), a natural polyphenolic compound extracted from the rhizomes of Curcuma longa , is used as a pharmaceutical agent, spice in food, and as a dye. Currently, CUR is being investigated for cancer treatment in Phase-II clinical trials. CUR also possesses excellent activities like anti-inflammatory, anti-microbial, and anti-oxidant, therefore quality control is crucial. The present research work was to develop a new, simple, validated and time-saving rapid 96-well plate spectrofluorimetric method for the determination of CUR. The developed method was compared with routinely used high performance liquid chromatography (HPLC) technique. The developed method were found to be linear in the concentration range of 15 to 3900 ng/mL with R 2 ≥ 0.9983 for spectrofluorimetric and 50-7500 ng/mL with R 2 ≥ 0.9999 for HPLC method. Accuracy, intraday and interday precision was adequate, with RSD lower than the suggested limits. The limits for the detection and the quantification of CUR were 7 and 15 ng/mL for spectrofluorimetric, and 25 and 50 ng/mL for HPLC respectively. The Bland-Altman analysis demonstrated the similarities between the two methods. The 96-well plate method was successfully applied to determine CUR in solid lipid nanoparticles (SLNs) and chitosan nanoparticles (Chi-NPs). The developed spectrofluorimetric method can hence serve as a possible replacement for the HPLC method for the quantification of CUR in healthcare and food products.

Coconut Sugar- a Potential Storehouse of Nutritive Metabolites, Novel Bio-products and Prospects - K. B. Hebbar; S. V. Ramesh; D. K. Ghosh; P. P. Shameena Beegum; R. Pandiselvam; M. R. Manikantan; A. C. Mathew (Sugar Tech, 2022)

Stable isotope composition of multiple tissues and individual amino acids reveals dietary variation among life stages in green turtles (Chelonia mydas) at Ningaloo Reef - Jessica L. Stubbs; Andrew T. Revill; Richard D. Pillans; Mathew A. Vanderklift (Marine Biology, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Epiphytism, diseases and grazing in seaweed aquaculture: A comprehensive review - Durga Prasad Behera; Kapilkumar N. Ingle; Doniya Elze Mathew; Asmita Dhimmar; Harshal Sahastrabudhe; Sunil Kumar Sahu; M. Gobala Krishnan; Pramod. B. Shinde; M. Ganesan; Vaibhav. A. Mantri (Reviews in Aquaculture, 2022)
Seaweeds are macroscopic forms of phylogenetically diverse assemblage of marine algae that grow in oceans, thriving among profoundly harsh environmental conditions. They are cultivated in many maritime nations primarily for edible applications; besides hydrocolloid extraction is the second largest domain of utility for this renewable biomass. The farming practices have been traditionally evolved in different Southeast Asian countries. Nevertheless, advancement in the knowledge about their life‐history traits and control over reproduction has paved ways for commencement of large‐scale commercial farming. Food and Agriculture Organisation of United Nations reported the availability of 35.8 million tons of seaweed biomass globally of which 97% accounted for farming. Although cultivation is on the rise due to relevant to social gains, epiphytic infestation, diseases and grazing have been identified as leading causes that result in substantially lower yield, deteriorated quality of product and skewed economics. Epiphytes may considerably impact the interaction of seaweed hosts with other beneficial communities also. Epidemiological studies in natural seaweed populations are scarce and this makes the understanding of the cross‐talk involving host specificity, and their role obscure. An overview of the diversity of epiphytes, understanding of mechanism of action, factors responsible, chemistry behind their interaction will help in deciphering the solutions to overcome infestation. A comprehensive report of seaweed epiphytism, diseases and grazing from the aspects of host–epiphyte interaction and their resultant consequences is presented along with the studies on economic impacts. The role of multi‐omics approaches in delineating seaweed epiphytic interactions is also included.

Immunoinformatics prediction of potential immunodominant epitopes from human coronaviruses and association with autoimmunity - Shilu Mathew; Aisha D. Fakhroo; Maria Smatti; Asmaa A. Al Thani; Hadi M. Yassine (Immunogenetics, 2022)

Glyphosate residues alter the microbiota of a perennial weed with a minimal indirect impact on plant performance - S. Ramula; S. A. Mathew; A. Kalske; R. Nissinen; K. Saikkonen; M. Helander (Plant and Soil, 2022)
Purpose In cold climates, glyphosate residues may linger in soils, with effects on plant–microbe interactions and, consequently, plant performance. Here, we explore the influence of glyphosate residues on the endophytic microbiota (bacteria and fungi) and performance of the perennial nitrogen-fixing weed Lupinus polyphyllus . Methods In a common garden, we grew plants from six populations of L. polyphyllus in glyphosate-treated or untreated control soils, with or without additional phosphorus. We sampled plant microbiota (leaves, roots, nodules) and assessed plant performance based on six traits: height, retrogression probability (i.e. shrinkage), biomass, root:shoot ratio, nodule number, and nodule viability. Results The richness of plant endophytic microbial communities was determined by soil phosphorus level rather than by glyphosate treatment. However, for bacteria, the composition of these communities differed between glyphosate-treated and control soils across plant tissue types; no difference was observed for fungi. The plant bacterial communities in both soil types were dominated by potential nitrogen-fixing bacteria belonging to family Bradyrhizobiaceae, and particularly so in glyphosate-treated soils. Overall, though, these changes in plant bacterial communities had a minor effect on plant performance: the only difference we detected was that the probability of retrogression was occasionally higher in glyphosate-treated soils than in control soils. Conclusion Our findings indicate that glyphosate-based herbicides, when applied at the recommended frequency and concentration, may not have critical effects on the growth of short-lived weeds after the safety period has passed; however, the endophytic microbiota of such weeds may experience longer-lasting shifts in community structure.

Effectiveness of Site-Specific Management Practices on the Amelioration of Soil Acidity in the Coconut Growing Entisol and Ultisol of Humid Tropics - Jeena Mathew; A. Abdul Haris; S. Indhuja; V. Krishnakumar; K. M. Nair; Ravi Bhat; K. S. Anil Kumar (Journal of Soil Science and Plant Nutrition, 2022)

Predator complementarity dampens variability of phytoplankton biomass in a diversity‐stability trophic cascade - Chase J. Rakowski; Caroline E. Farrior; Schonna R. Manning; Mathew A. Leibold (Ecology, 2021)
Trophic cascades – indirect effects of predators that propagate down through food webs – have been extensively documented in many ecosystem types. It has also been shown that predator diversity can mediate these trophic cascades and, separately, that herbivore biomass can influence the stability of primary producers. However, whether predator diversity can cause cascading effects on the stability of lower trophic levels has not yet been studied. We conducted a laboratory microcosm experiment and a field mesocosm experiment manipulating the presence and coexistence of two heteropteran predators and measuring their effects on zooplankton herbivores and phytoplankton basal resources. We predicted that if the predators partitioned their zooplankton prey, for example by size, then the co‐presence of the predators would reduce zooplankton prey mass and lead to (1) increased biomass of, and (2) decreased temporal variability of phytoplankton basal resources. We present evidence that the predators partitioned their zooplankton prey, leading to a synergistic suppression of zooplankton. In turn, this enhanced zooplankton suppression led to only a weak, non‐significant increase in the central tendency of phytoplankton biomass, but significantly reduced its variability. Our results demonstrate that predator diversity may indirectly stabilize basal resource biomass via a “diversity‐stability trophic cascade,” seemingly dependent on predator complementarity, even when there is no significant classic trophic cascade altering the central tendency of biomass. Therefore predator diversity, especially if correlated with diversity of prey use, could play a role in regulating ecosystem stability. This link between predator diversity and producer stability has implications for conservation and for potential biological control methods to improve crop yield reliability.

Top predator introduction changes the effects of spatial isolation on freshwater community structure - Rodolfo Mei Pelinson; Mathew A. Leibold; Luis Schiesari (Ecology, 2021)
Current conceptual metacommunity models predict that the consequences of local selective pressures on community structure increase with spatial isolation when species favored by local conditions also have higher dispersal rates. This appears to be the case of freshwater insects in the presence of fish. The introduction of predatory fish can produce trophic cascades in freshwater habitats because fish tend to prey upon intermediate predatory taxa, such as predatory insects, indirectly benefiting herbivores and detritivores. Similarly, spatial isolation can limit dispersal and colonization rates of predatory insects more strongly than of herbivores and detritivores, thus generating similar cascading effects. Here we tested the hypothesis that the effect of introduced predatory fish on insect community structure increases with spatial isolation by conducting a field experiment in artificial ponds that manipulated the presence/absence of fish (the redbreast tilapia) at three different distances from a source wetland. Our results showed that fish have direct negative effects on the abundance of predatory insects but probably have variable net effects on the abundance of herbivores and detritivores because the direct negative effects of predation by fish may offset indirect positive ones. Spatial isolation also resulted in indirect positive effects on the abundance of herbivores and detritivores but this effect was stronger in the absence rather than in the presence of fish so that insect communities diverged more strongly between fish and fishless ponds at higher spatial isolation. We argue that an important additional mechanism, ignored in our initial hypothesis, was that as spatial isolation increases fish predation pressure upon herbivores and detritivores increases due to the relative scarcity of predatory insects, thus dampening the positive effect that spatial isolation confers to lower trophic levels. Our results highlight the importance of considering interspecific variation in dispersal and multiple trophic levels to better understand the processes generating community and metacommunity patterns.

Evaluation of the Effectiveness of Newer Helmet Designs with Emergent Shell and Padding Technologies Versus Older Helmet Models for Preserving White Matter Following a Season of High School Football - Jed A. Diekfuss; Weihong Yuan; Jonathan A. Dudley; Christopher A. DiCesare; Matthew B. Panzer; Thomas M. Talavage; Eric Nauman; Scott Bonnette; Alexis B. Slutsky-Ganesh; Joseph Clark; Manish Anand; Mekibib Altaye; et al. (Annals of Biomedical Engineering, 2021)

Understanding Local Perceptions of the Drivers/Pressures on the Coastal Marine Environment in Palawan, Philippines - John Roderick V. Madarcos; Lota A. Creencia; Bethany R. Roberts; Mathew P. White; Johana Nayoan; Karyn Morrissey; Lora E. Fleming (Frontiers in Marine Science, 2021)
The Philippines, as a tropical archipelagic country, is particularly vulnerable to environmental changes affecting coastal and marine settings. However, there are limited studies investigating how these changes are perceived by the local populations who depend directly on the marine environment for their livelihoods, health, and well-being, and who are the most vulnerable to such changes. To explore these issues, we conducted an in-home face-to-face structured survey in 10 coastal communities in Palawan, Philippines ( n = 431). As part of the survey, respondents were asked to comment on how important they believed a list of 22 drivers/pressures (e.g., “land-use change”) were in affecting their local marine environment. Statistical analysis of this list using Exploratory Factor Analysis suggested the 22 drivers/pressures could be categorized into 7 discrete groups (or in statistical terms “factors”) of drivers/pressures (e.g., “urbanization,” “unsustainable fishing practices” etc.). We then used ordinary least squared regression to identify similarities and differences between the perspectives within and across communities, using various socio-demographic variables. Results suggested that among the seven identified factors, four were perceived by the local communities as making the marine environment worse, two were perceived as having no impact, and one was perceived to be making the marine environment better. Perceptions differed by gender, education, ethnicity, and study site. A subsequent survey with 16 local coastal resource management experts, suggested that public perceptions of the most critical drivers/pressures were broadly consistent with those of this expert group. Our findings highlight how aware local coastal communities are of the drivers/pressures underpinning the threats facing their livelihoods, health, and well-being. Ultimately, this information can support and inform decisions for the management of local marine resources.

Growth, mortality, exploitation rate and recruitment pattern of Octopus cyanea (Mollusca: Cephalopoda) in the WIO region: A case study from the Mafia Archipelago, Tanzania - Mathew O. Silas; Mary A. Kishe; Johnson G. Mshana; Masumbuko L. Semba; Said S. Mgeleka; Bigeyo N. Kuboja; Benjamin P. Ngatunga; Muhaji A. Chande; Patroba Matiku (Western Indian Ocean Journal of Marine Science, 2021)
Octopus cyanea is a commercially important cephalopod in the Western Indian Ocean (WIO) region, but scientific information to inform management strategies for the species is limited. A study was conducted in 2014, 2015, 2017 and 2018 to investigate biological parameters including growth, mortality, exploitation rates and recruitment patterns in the sea around Mafia Archipelago, Tanzania. Virtual population analysis (VPA) indicated differential mortality between two sampling sites; the lowest and highest fishing mortality of F = 1.5yr-1 and F = 2.7yr-1 were observed in Bwejuu (Dorsal mantle length, DMT = 18-20 cm) and Jibondo (DMT = 8-12 cm) fishing villages, respectively. The maximum exploitation rate (Emax), which gives the maximum relative yield per recruit, was estimated at 0.380 and 0.379 for Jibondo and Bwejuu, respectively. The exploitation rates E 0.5, which corresponded to 50% of the unexploited stock relative biomass per recruit, were estimated at 0.248 for Jibondo and 0.247 for Bwejuu. These values differ greatly from the exploitation rates of 0.53 and 0.41 for Jibondo and Bwejuu, respectively, suggesting that the stock of O. cyanea is probably being overfished both in terms of yield per recruit and biomass per recruit. The stock-recruit pattern was observed to be continuous year-round, with the peak being between May and July. Since the peak in recruitment of both areas coincides with the south-east monsoon (SE Monsoon) and the level of maximum sustainable yield has been overshot, it is recommended that management plans are implemented that will reduce effort while increasing biomass, for example, implementing temporal octopus fishery closures at a village level.

Protective effect of (+)–catechin against lipopolysaccharide-induced inflammatory response in RAW 264.7 cells through downregulation of NF-κB and p38 MAPK - M. A. Sunil; V. S. Sunitha; Prasanthkumar Santhakumaran; Mohind C. Mohan; Midhun Sebastian Jose; E. K. Radhakrishnan; Jyothis Mathew (Inflammopharmacology, 2021)

A Critical Re-Examination of the Factors Influencing Determination of Organic Matter in Soils - Annie Joy; Benny Mathews Abraham; A. Sridharan (Geotechnical and Geological Engineering, 2021)

Coral reef resilience differs among islands within the Gulf of Mannar, southeast India, following successive coral bleaching events - K. Diraviya Raj; Greta S. Aeby; G. Mathews; Gareth J. Williams; Jamie M. Caldwell; R. L. Laju; M. Selva Bharath; P. Dinesh Kumar; A. Arasamuthu; N. Gladwin Gnana Asir; Lisa M. Wedding; Andrew J. Davies; et al. (Coral Reefs, 2021)

Taphonomy of an excavated striped hyena (Hyaena hyaena) den in Arabia: implications for paleoecology and prehistory - Mathew Stewart; Eric Andrieux; Richard Clark-Wilson; Nils Vanwezer; James Blinkhorn; Simon J. Armitage; Abdulaziz al Omari; Badr Zahrani; Mesfer Alqahtani; Mahmoud Al-Shanti; Iyad Zalmout; Yahya S. A. Al-Mufarreh; et al. (Archaeological and Anthropological Sciences, 2021)
Studies of modern carnivore accumulations of bone (i.e., neo-taphonomy) are crucial for interpreting fossil accumulations in the archaeological and paleontological records. Yet, studies in arid regions have been limited in both number and detailed taphonomic data, prohibiting our understanding of carnivore bone-accumulating and -modifying behavior in dry regions. Here, we present a taphonomic analysis of an impressive carnivore-accumulated bone assemblage from the Umm Jirsan lava tube in the Harrat Khaybar region, Saudi Arabia. The size and composition of the bone accumulation, as well as the presence of hyena skeletal remains and coprolites, suggest that the assemblage was primarily accumulated by striped hyena ( Hyaena hyaena ). Our findings (1) identify potentially useful criteria for distinguishing between accumulations generated by different species of hyenas; (2) emphasize the need for neo-taphonomic studies for capturing the full variation in carnivore bone-accumulating and modifying behavior; (3) suggest that under the right settings, striped hyena accumulations can serve as good proxies for (paleo)ecology and livestock practices; and (4) highlight the potential for future research at Umm Jirsan, as well as at the numerous nearby lava tube systems. We encourage continued neo-taphonomic efforts in regions important in human prehistory, particularly in arid zones, which have received little research attention.

Regeneration responses in black ash (Fraxinus nigra) wetlands: implications for forest diversification to address emerald ash borer (Agrilus planipennis) - Marcella A. Windmuller-Campione; Matthew B. Russell; Robert A. Slesak; Mathew Lochner (New Forests, 2021)

Wide variability among the ‘Mauritius’ somaclones demonstrates somaclonal variation as a promising improvement strategy in pineapple (Ananas comosus L.) - Lalit Dhurve; K. Ajith Kumar; Jyothi Bhaskar; A. Sobhana; Rose Mary Francies; Deepu Mathew (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Epidemiological, molecular, and clinical features of rotavirus infections among pediatrics in Qatar - Shilu Mathew; Khalid Al Ansari; Asmaa A. Al Thani; Hassan Zaraket; Hadi M. Yassine (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Biodiversity and antimicrobial potential of bacterial endophytes from halophyte Salicornia brachiata - Sanju Singh; Vishal A. Ghadge; Pankaj Kumar; Doniya Elze Mathew; Asmita Dhimmar; Harshal Sahastrabudhe; Yedukondalu Nalli; Mina R. Rathod; Pramod B. Shinde (Antonie van Leeuwenhoek, 2021)

A comparative assessment of nutrient partitioning in healthy and root (wilt) disease affected coconut palms grown in an Entisol of humid tropical Kerala - Jeena Mathew; A. Abdul Haris; Ravi Bhat; V. Krishna Kumar; K. Muralidharan; K. Susan John; U. Surendran (Trees, 2021)

Hypoxia and standing balance - Mathew I. B. Debenham; Janelle N. Smuin; Tess D. A. Grantham; Philip N. Ainslie; Brian H. Dalton (European Journal of Applied Physiology, 2021)

Spatial population genomics of a recent mosquito invasion - Thomas L. Schmidt; Tom Swan; Jessica Chung; Stephan Karl; Samuel Demok; Qiong Yang; Matt A Field; Mutizwa Odwell Muzari; Gerhard Ehlers; Mathew Brugh; Rodney Bellwood; Peter Horne; et al. (Molecular Ecology, 2021)
Population genomic approaches can characterize dispersal across a single generation through to many generations in the past, bridging the gap between individual movement and intergenerational gene flow. These approaches are particularly useful when investigating dispersal in recently altered systems, where they provide a way of inferring long‐distance dispersal between newly established populations and their interactions with existing populations. Human‐mediated biological invasions represent such altered systems which can be investigated with appropriate study designs and analyses. Here we apply temporally restricted sampling and a range of population genomic approaches to investigate dispersal in a 2004 invasion of Aedes albopictus (the Asian tiger mosquito) in the Torres Strait Islands (TSI) of Australia. We sampled mosquitoes from 13 TSI villages simultaneously and genotyped 373 mosquitoes at genome‐wide single nucleotide polymorphisms (SNPs): 331 from the TSI, 36 from Papua New Guinea (PNG) and four incursive mosquitoes detected in uninvaded regions. Within villages, spatial genetic structure varied substantially but overall displayed isolation by distance and a neighbourhood size of 232–577. Close kin dyads revealed recent movement between islands 31–203 km apart, and deep learning inferences showed incursive Ae. albopictus had travelled to uninvaded regions from both adjacent and nonadjacent islands. Private alleles and a co‐ancestry matrix indicated direct gene flow from PNG into nearby islands. Outlier analyses also detected four linked alleles introgressed from PNG, with the alleles surrounding 12 resistance‐associated cytochrome P450 genes. By treating dispersal as both an intergenerational process and a set of discrete events, we describe a highly interconnected invasive system.

Long-Term Acoustic Monitoring Reveals Site Fidelity, Reproductive Migrations, and Sex Specific Differences in Habitat Use and Migratory Timing in a Large Coastal Shark (Negaprion acutidens) - Richard D. Pillans; Wayne Rochester; Russell C. Babcock; Damian P. Thomson; Michael D. E. Haywood; Mathew A. Vanderklift (Frontiers in Marine Science, 2021)
Knowledge of the movement patterns of the lemon shark Negaprion acutidens is poor in contrast to the allopatric N. brevirostis . Using acoustic telemetry, we investigated daily (diel and tidal) and seasonal patterns in residency, fidelity, home range, habitat preference, and migratory patterns along the Ningaloo coast, Australia. Thirty eight adult N. acutidens were monitored for up 6.1 years (mean 2.5 y) with 19 animals detected for more than 3 years and 5 for more than 5 y. Approximately 50% of the tagged animals remained within 10 km of their tagging location for more than 12 months (average core home range of 1.7 km 2 ). Surprisingly, residency of adults was greater than juveniles in this known nursery area. Adults showed a strong preference for lagoon habitats and moved into shallow nearshore habitats at high tide and at night. During winter months, female sharks shifted their core home range 0.45 km further offshore into deeper lagoon areas, a shift which is likely due to behavioral thermoregulation. Space use by males and females within core areas was asynchronous indicating sexual segregation by resident sharks. Both resident and non-resident sharks were detected up to 140 km away. These highly directional (southerly) and rapid movements (140 km in 2 days) were largely correlated with the parturition and mating periods with males departing 1–2 months earlier than females. In females, periodicity of migrations was variable with evidence of annual and biannual patterns. Negaprion acutidens are highly susceptible to over-fishing and movement data are essential to quantify spatio-temporal overlap with fisheries and assist with developing spatially explicit stock assessment models.

Are physiological and behavioural responses to stressors displayed concordantly by wild urban rodents? - Loren L. Fardell; Miguel A. Bedoya-Pérez; Christopher R. Dickman; Mathew S. Crowther; Chris R. Pavey; Edward J. Narayan (The Science of Nature, 2021)
Understanding wild animal responses to stressors underpins effective wildlife management. In order for responses to stressors to be correctly interpreted, it is critical that measurements are taken on wild animals using minimally invasive techniques. Studies investigating wild animal responses to stressors often measure either a single physiological or behavioural variable, but whether such responses are comparable and concordant remains uncertain. We investigated this question in a pilot study that measured responses of wild-caught urban brown and black rats ( Rattus norvegicus , Rattus rattus ) to fur-based olfactory cues from a predator, the domestic cat ( Felis catus ); a novel herbivore, the koala ( Phascolarctos cinereus ); and a familiar herbivore and competitor, the common brushtail possum ( Trichosurus vulpecula ). Physiological responses, measured by assaying faecal glucocorticoid metabolites, were compared to behavioural responses observed via video recordings. We found that physiological and behavioural responses to stressors were expressed concordantly. There was no sizeable physiological response observed, and the behavioural response when considered across the night was negligible. However, the behavioural response to the predator and competitor cues changed across the observation period, with activity increasing with increasing hours of exposure. Our results indicate that responses of wild rodents to cues are nuanced, with stress responses modulated by behaviour changes that vary over time according to the severity of the perceived threat as animals gather further information. If the physiological response alone had been assessed, this moderated response may not have been evident, and in terms of wildlife management, vital information would have been lost.

Immersion challenge of naïve Atlantic salmon with cultured Nolandella sp. and Pseudoparamoeba sp. did not increase the severity of Neoparamoeba perurans ‐induced amoebic gill disease (AGD) - Chloe J. English; Natasha A. Botwright; Mark B. Adams; Andrew C. Barnes; James W. Wynne; Paula C. Lima; Mathew T. Cook (Journal of Fish Diseases, 2021)
Amoebic gill disease (AGD) is one of the main health issues impacting farmed Atlantic salmon. Neoparamoeba perurans causes AGD; however, a diversity of other amoeba species colonizes the gills and there is little understanding of whether they are commensal or potentially involved in different stages of gill disease development. Here, we conduct in vivo challenges of naïve Atlantic salmon with cultured Nolandella sp. and Pseudoparamoeba sp. to investigate their pathogenicity to Atlantic salmon gills. Additionally, we assessed whether the presence of Nolandella sp. and Pseudoparamoeba sp. influences the onset and/or severity of N. perurans ‐induced AGD. All three strains attached and multiplied on the gills according to qPCR analysis. Furthermore, minor gross gill lesions and histological changes were observed post‐exposure. While N. perurans was found associated with classical AGD lesions, Nolandella sp. and Pseudoparamoeba sp. were not found associated with lesion sites and these lesions did not meet the expected composite of histopathological changes for AGD. Moreover, the presence of these non‐ N. perurans species did not significantly increase the severity of AGD. This trial provides evidence that cultured Nolandella sp. and Pseudoparamoeba sp. do not induce AGD and do not influence the severity of AGD during the early stages of development.

A global analysis of complexity–biodiversity relationships on marine artificial structures - Elisabeth M. A. Strain; Peter D. Steinberg; Maria Vozzo; Emma L. Johnston; Marco Abbiati; Moises A. Aguilera; Laura Airoldi; J. David Aguirre; Gail Ashton; Maritina Bernardi; Paul Brooks; Benny K. K. Chan; et al. (Global Ecology and Biogeography, 2021)
Aim Topographic complexity is widely accepted as a key driver of biodiversity, but at the patch‐scale, complexity–biodiversity relationships may vary spatially and temporally according to the environmental stressors complexity mitigates, and the species richness and identity of potential colonists. Using a manipulative experiment, we assessed spatial variation in patch‐scale effects of complexity on intertidal biodiversity. Location 27 sites within 14 estuaries/bays distributed globally. Time period 2015–2017. Major taxa studied Functional groups of algae, sessile and mobile invertebrates. Methods Concrete tiles of differing complexity (flat; 2.5‐cm or 5‐cm complex) were affixed at low–high intertidal elevation on coastal defence structures, and the richness and abundance of the colonizing taxa were quantified after 12 months. Results The patch‐scale effects of complexity varied spatially and among functional groups. Complexity had neutral to positive effects on total, invertebrate and algal taxa richness, and invertebrate abundances. However, effects on the abundance of algae ranged from positive to negative, depending on location and functional group. The tidal elevation at which tiles were placed accounted for some variation. The total and invertebrate richness were greater at low or mid than at high intertidal elevations. Latitude was also an important source of spatial variation, with the effects of complexity on total richness and mobile mollusc abundance greatest at lower latitudes, whilst the cover of sessile invertebrates and sessile molluscs responded most strongly to complexity at higher latitudes. Conclusions After 12 months, patch‐scale relationships between biodiversity and habitat complexity were not universally positive. Instead, the relationship varied among functional groups and according to local abiotic and biotic conditions. This result challenges the assumption that effects of complexity on biodiversity are universally positive. The variable effect of complexity has ramifications for community and applied ecology, including eco‐engineering and restoration that seek to bolster biodiversity through the addition of complexity.

Power Outages and Community Health: a Narrative Review - Joan A. Casey; Mihoka Fukurai; Diana Hernández; Satchit Balsari; Mathew V. Kiang (Current Environmental Health Reports, 2020)

Seminal fluid protein divergence among populations exhibiting postmating prezygotic reproductive isolation - Martin D. Garlovsky; Caroline Evans; Mathew A. Rosenow; Timothy L. Karr; Rhonda R. Snook (Molecular Ecology, 2020)
Despite holding a central role in fertilization, reproductive traits often show elevated rates of evolution and diversification. The rapid evolution of seminal fluid proteins (Sfps) within populations is predicted to cause mis‐signalling between the male ejaculate and the female during and after mating resulting in postmating prezygotic (PMPZ) isolation between populations. Crosses between Drosophila montana populations show PMPZ isolation in the form of reduced fertilization success in both noncompetitive and competitive contexts. Here we test whether male ejaculate proteins produced in the accessory glands or ejaculatory bulb differ between populations using liquid chromatography tandem mass spectrometry. We find more than 150 differentially abundant proteins between populations that may contribute to PMPZ isolation, including a number of proteases, peptidases and several orthologues of Drosophila melanogaster Sfps known to mediate fertilization success. Males from the population that elicit the stronger PMPZ isolation after mating with foreign females typically produced greater quantities of Sfps. The accessory glands and ejaculatory bulb show enrichment for different gene ontology (GO) terms and the ejaculatory bulb contributes more differentially abundant proteins. Proteins with a predicted secretory signal evolve faster than nonsecretory proteins. Finally, we take advantage of quantitative proteomics data for three Drosophila species to determine shared and unique GO enrichments of Sfps between taxa and which potentially mediate PMPZ isolation. Our study provides the first high‐throughput quantitative proteomic evidence showing divergence of reproductive proteins between populations that exhibit PMPZ isolation.

Spatial and temporal patterns of lateralization in a parrot species complex - Mathew L. Berg; Sarah A. Micallef; Justin R. Eastwood; Raoul F. H. Ribot; Andrew T. D. Bennett (Evolutionary Ecology, 2020)

Temporal stability vs. community matrix measures of stability and the role of weak interactions - Amy L. Downing; Craig Jackson; Claire Plunkett; Jayne Ackerman Lockhart; Shannon M. Schlater; Mathew A. Leibold (Ecology Letters, 2020)
Relationships between different measures of stability are not well understood in part because empiricists and theoreticians tend to measure different aspects and most studies only explore a single form of stability. Using time‐series data from experimental plankton communities, we compared temporal stability typically measured by empiricists (coefficient of variation in biomass) to stability measures typically measured by theoreticians derived from the community matrix (asymptotic resilience, initial resilience and intrinsic stochastic invariability) using first‐order multivariate autoregressive models (MAR). Community matrices were also used to derive estimates of interaction strengths between plankton groups. We found no relationship between temporal stability and stability measures derived from the community matrix. Weaker interaction strengths were generally associated with higher stability for community matrix measures of stability, but were not consistently associated with higher temporal stability. Temporal stability and stability measures derived from the community matrix stability appear to represent different aspects of stability reflecting the multi‐dimensionality of stability.

Using Propagules to Restore Coastal Marine Ecosystems - Mathew A. Vanderklift; Christopher Doropoulos; Daniel Gorman; Inês Leal; Antoine J. P. Minne; John Statton; Andrew D. L. Steven; Thomas Wernberg (Frontiers in Marine Science, 2020)

Oleoyl alanine (HU595): a stable monomethylated oleoyl glycine interferes with acute naloxone precipitated morphine withdrawal in male rats - Samantha M. Ayoub; Reem Smoum; Mathew Farag; Harkirat Atwal; Stephen A. Collins; Erin M. Rock; Cheryl L. Limebeer; Fabiana Piscitelli; Fabio Arturo Iannotti; Aron H. Lichtman; Francesco Leri; Vincenzo Di Marzo; et al. (Psychopharmacology, 2020)

Antibacterial Potential and Apoptosis Induction by Pigments from the Endophyte Burkholderia sp. WYAT7 - A. Ashitha; E. K. Radhakrishnan; Jyothis Mathew (Current Microbiology, 2020)

How Does the Landscape Affect Metacommunity Structure? A Quantitative Review for Lentic Environments - Mauricio Almeida-Gomes; Francisco Valente-Neto; Eduardo O. Pacheco; Carolina C. Ganci; Mathew A. Leibold; Adriano S. Melo; Diogo B. Provete (Current Landscape Ecology Reports, 2020)

Near real-time mapping of air temperature at high spatiotemporal resolutions in Tasmania, Australia - Mathew A. Webb; Darren Kidd; Budiman Minasny (Theoretical and Applied Climatology, 2020)

Eroding islands of Gulf of Mannar, Southeast India: a consequence of long-term impact of coral mining and climate change - N. Gladwin Gnana Asir; P. Dinesh Kumar; A. Arasamuthu; G. Mathews; K. Diraviya Raj; T. K. Ashok Kumar; Deepak S. Bilgi; J. K. Patterson Edward (Natural Hazards, 2020)

Hip implant performance prediction by acoustic emission techniques: a review - Ampadi R. Remya; B. Vishwash; Christine Lee; P. Srinivasa Pai; Alejandro A. Espinoza Orías; Didem Ozevin; Mathew T. Mathew (Medical & Biological Engineering & Computing, 2020)

Formulation Optimization of Selective Laser Sintering 3D-Printed Tablets of Clindamycin Palmitate Hydrochloride by Response Surface Methodology - Eman M. Mohamed; Sogra F. Barakh Ali; Ziyaur Rahman; Sathish Dharani; Tanil Ozkan; Mathew A. Kuttolamadom; Mansoor A. Khan (AAPS PharmSciTech, 2020)

Changes in future rainfall extremes over Northeast Bangladesh: A Bayesian model averaging approach - Abul Basher; A. K. M. Saiful Islam; Mathew A. Stiller‐Reeve; Pao‐Shin Chu (International Journal of Climatology, 2020)
In this paper, we used a Bayesian model averaging (BMA) approach to analyse the changes in rainfall extremes in the periods 2041–2070 and 2071–2099 over northeast Bangladesh as a consequence of climate change. Climate change over this region could potentially impact agricultural production, water resources management, and the overall economy of the country. We used six regional climate models (RCMs) over the Coordinated Regional Downscaling Experiment South Asia domain. We used one medium stabilization scenario (RCP4.5) and one high‐emission scenario (RCP8.5) for projecting the extreme rainfall indices. A multi‐model ensemble mean was generated using the BMA approach. The BMA mean is a weighted average related to each RCM's predictive skill during the training period. Most of the rainfall extremes are expected to increase in both pre‐monsoon (March–May) and monsoon (June–September) seasons in the future compared with baseline (1976–2005). The average pre‐monsoon rainfall of the study area is projected to increase by 12.93 and 18.42% under RCP4.5 and 18.18 and 23.85% under RCP8.5 for the periods 2041–2070 and 2071–2099, respectively. The average monsoon rainfall of the study area is projected to increase by 4.96 and 2.27% under RCP4.5 and 6.56 and 6.40% under RCP8.5 for the periods 2041–2070 and 2071–2099, respectively. All the extreme indices except consecutive wet day are expected to change significantly at the 95% confidence level during the pre‐monsoon season. The study area will potentially be subjected to more frequent floods in the future both in pre‐monsoon and monsoon seasons as a consequence of climate change. Notably, the intensity and the magnitude of flash flooding in the pre‐monsoon season are expected to increase more in the future because the increase in extreme indices is more significant during that season.

Considerations for Soluble Protein Biomarker Blood Sample Matrix Selection - Joel A. Mathews; Yan G. Ni; Connie Wang; Jon E. Peterson; Chad Ray; Xuemei Zhao; Daoyu Duan; Sara Hamon; John Allinson; Martha Hokom; Greta Wegner (The AAPS Journal, 2020)

Enhanced In Vitro Shoot Multiplication of Piper sarmentosum by Suppression of Apical Dominance - S. Stephin; A. Gangaprasad; Sam P. Mathew; S. Muthukrishnan (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2020)

Plant uptake of nitrogen and phosphorus among grassland species affected by drought along a soil available phosphorus gradient - Pierre Mariotte; Tom Cresswell; Mathew P. Johansen; Jennifer J. Harrison; Claudia Keitel; Feike A. Dijkstra (Plant and Soil, 2020)

Characterising the biophysical, economic and social impacts of soil carbon sequestration as a greenhouse gas removal technology - Alasdair J. Sykes; Michael Macleod; Vera Eory; Robert M. Rees; Florian Payen; Vasilis Myrgiotis; Mathew Williams; Saran Sohi; Jon Hillier; Dominic Moran; David A. C. Manning; Pietro Goglio; et al. (Global Change Biology, 2020)
To limit warming to well below 2°C, most scenario projections rely on greenhouse gas removal technologies (GGRTs); one such GGRT uses soil carbon sequestration (SCS) in agricultural land. In addition to their role in mitigating climate change, SCS practices play a role in delivering agroecosystem resilience, climate change adaptability and food security. Environmental heterogeneity and differences in agricultural practices challenge the practical implementation of SCS, and our analysis addresses the associated knowledge gap. Previous assessments have focused on global potentials, but there is a need among policymakers to operationalise SCS. Here, we assess a range of practices already proposed to deliver SCS, and distil these into a subset of specific measures. We provide a multidisciplinary summary of the barriers and potential incentives towards practical implementation of these measures. First, we identify specific practices with potential for both a positive impact on SCS at farm level and an uptake rate compatible with global impact. These focus on: (a) optimising crop primary productivity (e.g. nutrient optimisation, pH management, irrigation); (b) reducing soil disturbance and managing soil physical properties (e.g. improved rotations, minimum till); (c) minimising deliberate removal of C or lateral transport via erosion processes (e.g. support measures, bare fallow reduction); (d) addition of C produced outside the system (e.g. organic manure amendments, biochar addition); (e) provision of additional C inputs within the cropping system (e.g. agroforestry, cover cropping). We then consider economic and non‐cost barriers and incentives for land managers implementing these measures, along with the potential externalised impacts of implementation. This offers a framework and reference point for holistic assessment of the impacts of SCS. Finally, we summarise and discuss the ability of extant scientific approaches to quantify the technical potential and externalities of SCS measures, and the barriers and incentives to their implementation in global agricultural systems.

Positive Ecological Interactions and the Success of Seagrass Restoration - Stephanie R. Valdez; Y. Stacy Zhang; Tjisse van der Heide; Mathew A. Vanderklift; Flavia Tarquinio; Robert J. Orth; Brian R. Silliman (Frontiers in Marine Science, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

A method to investigate neonicotinoid resistance in mites - Paul A. Umina; Aston Arthur; Mathew Binns; James Maino (Experimental and Applied Acarology, 2019)

Urbanization impacts apex predator gene flow but not genetic diversity across an urban‐rural divide - Daryl R. Trumbo; Patricia E. Salerno; Kenneth A. Logan; Mathew W. Alldredge; Roderick B. Gagne; Christopher P. Kozakiewicz; Simona Kraberger; Nicholas M. Fountain‐Jones; Meggan E. Craft; Scott Carver; Holly B. Ernest; Kevin R. Crooks; et al. (Molecular Ecology, 2019)
Apex predators are important indicators of intact natural ecosystems. They are also sensitive to urbanization because they require broad home ranges and extensive contiguous habitat to support their prey base. Pumas ( Puma concolor ) can persist near human developed areas, but urbanization may be detrimental to their movement ecology, population structure, and genetic diversity. To investigate potential effects of urbanization in population connectivity of pumas, we performed a landscape genomics study of 130 pumas on the rural Western Slope and more urbanized Front Range of Colorado, USA. Over 12,000 single nucleotide polymorphisms (SNPs) were genotyped using double‐digest, restriction site‐associated DNA sequencing (ddRADseq). We investigated patterns of gene flow and genetic diversity, and tested for correlations between key landscape variables and genetic distance to assess the effects of urbanization and other landscape factors on gene flow. Levels of genetic diversity were similar for the Western Slope and Front Range, but effective population sizes were smaller, genetic distances were higher, and there was more admixture in the more urbanized Front Range. Forest cover was strongly positively associated with puma gene flow on the Western Slope, while impervious surfaces restricted gene flow and more open, natural habitats enhanced gene flow on the Front Range. Landscape genomic analyses revealed differences in puma movement and gene flow patterns in rural versus urban settings. Our results highlight the utility of dense, genome‐scale markers to document subtle impacts of urbanization on a wide‐ranging carnivore living near a large urban center.

Corrigendum: Severe Continental-Scale Impacts of Climate Change Are Happening Now: Extreme Climate Events Impact Marine Habitat Forming Communities Along 45% of Australia's Coast - Russell C. Babcock; Rodrigo H. Bustamante; Elizabeth A. Fulton; Derek J. Fulton; Michael D. E. Haywood; Alistair James Hobday; Robert Kenyon; Richard James Matear; Eva E. Plagányi; Anthony J. Richardson; Mathew A. Vanderklift (Frontiers in Marine Science, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Severe Continental-Scale Impacts of Climate Change Are Happening Now: Extreme Climate Events Impact Marine Habitat Forming Communities Along 45% of Australia’s Coast - Russell C. Babcock; Rodrigo H. Bustamante; Elizabeth A. Fulton; Derek J. Fulton; Michael D. E. Haywood; Alistair James Hobday; Robert Kenyon; Richard James Matear; Eva E. Plagányi; Anthony J. Richardson; Mathew A. Vanderklift (Frontiers in Marine Science, 2019)

Understanding the Land Carbon Cycle with Space Data: Current Status and Prospects - Jean-François Exbrayat; A. Anthony Bloom; Nuno Carvalhais; Rico Fischer; Andreas Huth; Natasha MacBean; Mathew Williams (Surveys in Geophysics, 2019)

Seagrass restoration in Gulf of Mannar, Tamil Nadu, Southeast India: a viable management tool - J. K. Patterson Edward; K. Diraviya Raj; G. Mathews; P. Dinesh Kumar; A. Arasamuthu; Nisha D’ Souza; Deepak S. Bilgi (Environmental Monitoring and Assessment, 2019)

Psidium guajava Leaf Extracts and Their Quercetin Protect HepG2 Cell Lines Against CCL4 Induced Cytotoxicity - K. Vijayakumar; R. L. Rengarajan; R. Radhakrishnan; Shilu Mathew; Ishtiaq Qadri; A. Vijaya Anand (Indian Journal of Clinical Biochemistry, 2019)

The effects of oral nicotine administration and abstinence on sleep in male C57BL/6J mice - Hunter L. Mathews; Jerry A. Stitzel (Psychopharmacology, 2019)

Blood Biochemical Reference Intervals for Free-Ranging Olive Baboons (Papio anubis) in Kenya - Mathew Mutinda; Margaret C. Crofoot; Jennifer C. Kishbaugh; Lee-Ann C. Hayek; Dawn Zimmerman; Devin A. Tunseth; Suzan Murray (International Journal of Primatology, 2019)

Key colonist pools and habitat filters mediate the composition of fiddler crab–associated bacterial communities - Catalina Cuellar‐Gempeler; Mathew A. Leibold (Ecology, 2019)
The diversity and composition of local communities depends strongly on the pool of species that have been able to colonize that community from elsewhere. Typically this is thought to depend on a larger regional species pool that is subject to local environmental constraints that act as “filters.” Often, however, colonists arrive from multiple sources that differ in habitat conditions and have therefore already experienced distinct “prefiltering.” Consequently, it is the interaction of species from these distinct pools that determine the composition of local communities. This interaction is particularly important when certain colonist pools provide keystone species with disproportionate roles on community assembly. We propose to identify these key colonist pools and their interaction with local habitat filters by quantifying community‐level responses to colonist pool manipulation. We tested this framework to assess the contribution of surface and burrow sediment bacteria to bacterial communities associated with the fiddler crab, Uca panacea . In a mesocosm experiment, we combined normal and autoclaved surface and burrow sediment in a factorial experimental design, and we evaluated the community‐level responses of carapace and gut microbial assemblages to sediment treatments with next‐generation sequencing of the 16S rRNA gene. Results from carapace bacterial communities indicate that burrow sediments contribute most recruits, but surface sediments provide a few key colonizers that become established in the carapace community. In contrast, the composition of gut‐associated microbial communities responded only to surface bacteria manipulation, despite being highly dissimilar from the community composition in both the surface and burrow source pools. These results suggest that assembly in the gut depends primarily on colonization from the surface sediment and regulation by habitat filtering. For fiddler crab–associated bacteria, we can conclude that key colonist pools and habitat filters regulate the influence of multiple colonist pools. Incorporating and distinguishing the contribution of multiple sources of species, rather than a single regional species pool, may better explain community dynamics in many systems, especially those with weak habitat filters.

Transcriptome profiling of four candidate milk genes in milk and tissue samples of temperate and tropical cattle - Olanrewaju B. Morenikeji; Mabel O. Akinyemi; Mathew Wheto; Olawale J. Ogunshola; Adebanjo A. Badejo; Clifford A. Chineke (Journal of Genetics, 2019)

Plumage coloration follows Gloger's rule in a ring species - Raoul F. H. Ribot; Mathew L. Berg; Emanuel Schubert; John A. Endler; Andrew T. D. Bennett (Journal of Biogeography, 2019)
Aim Animal coloration is expected to differ between populations in different habitats according to Gloger's rule, with darker animals found in more humid, vegetated or warmer environments. Yet despite considerable support across the globe, the mechanisms behind this biogeographical rule are currently still unclear. Exploiting a ring species with plumage coloration from crimson to pale yellow, we test Gloger's rule and the mechanisms behind phenotypic divergence. Location South‐eastern Australia. Major taxa studied Crimson rosellas ( Platycercus elegans ). Methods We combined three modelling approaches (spatial regression; random decision forest species distribution and conditional inference tree) to test the association between 10 environmental variables (based on long‐term climate data and remotely sensed reflectance of the land) and plumage coloration across the distribution of P. elegans . We also took in‐situ measurements of background coloration of dominant vegetation to examine the relationship between (a) background coloration measured locally and remotely, (b) P. elegans coloration and (c) known differences in visual sensitivity of the subspecies using species‐specific visual models. Results On both a continental and a local scale, the distribution of yellow‐red plumage coloration was strongly predicted by average rainfall, summer temperature and the Earth's reflectance between 620–670 nm. Remotely sensed radiance measures correlated strongly and positively with reflectance of the leaves of the dominant tree species at sites across the P. elegans distribution. Visual modelling indicated that differences in background colour could affect signalling efficacy in dim‐light conditions. Main conclusions Our study shows that the highly variable plumage coloration conforms to Gloger's rule, and indicates that background coloration of the vegetation and thermoregulation are likely to be important mechanisms. Our results also show that Gloger's rule can explain variation in pigmentary systems other than melanin, and highlight that selection from environmental variation could be an important force behind the geographic diversity found in ring species.

Increased Soil Frost Versus Summer Drought as Drivers of Plant Biomass Responses to Reduced Precipitation: Results from a Globally Coordinated Field Experiment - Hugh A. L. Henry; Mehdi Abedi; Concepción L. Alados; Karen H. Beard; Lauchlan H. Fraser; Anke Jentsch; Juergen Kreyling; Andrew Kulmatiski; Eric G. Lamb; Wei Sun; Mathew R. Vankoughnett; Susanna Venn; et al. (Ecosystems, 2018)

Coated-Platelet Trends Predict Short-Term Clinical OutcomeAfter Subarachnoid Hemorrhage - Bappaditya Ray; Vijay M. Pandav; Eleanor A. Mathews; David M. Thompson; Lance Ford; Lori K. Yearout; Bradley N. Bohnstedt; Shuchi Chaudhary; George L. Dale; Calin I. Prodan (Translational Stroke Research, 2018)

Assessing climatic trends of extreme rainfall indices over northeast Bangladesh - Md. Abul Basher; Mathew Alexander Stiller-Reeve; A. K. M. Saiful Islam; Scott Bremer (Theoretical and Applied Climatology, 2018)

Antagonism Against Fish Pathogens by Cellular Components/Preparations of Bacillus coagulans (MTCC-9872) and It’s In Vitro Probiotic Characterisation - Sebastian J. Midhun; Sahadevan Neethu; A. Vysakh; E. K. Radhakrishnan; Mathew Jyothis (Current Microbiology, 2018)

Electro-Fenton oxidation of para-aminosalicylic acid: degradation kinetics and mineralization pathway using Pt/carbon-felt and BDD/carbon-felt cells - Nihal Oturan; Charuvila T. Aravindakumar; Hugo Olvera-Vargas; Mathew M. Sunil Paul; Mehmet A. Oturan (Environmental Science and Pollution Research, 2018)

Factors influencing property selection for conservation revolving funds - Mathew J. Hardy; James A. Fitzsimons; Sarah A. Bekessy; Ascelin Gordon (Conservation Biology, 2018)
Finding sustainable ways to increase the amount of private land protected for biodiversity is challenging for many conservation organizations. In some countries, organizations use revolving‐fund programs, whereby land is purchased and then sold to conservation‐minded owners under condition they enter into a conservation covenant or easement. The sale proceeds are used to purchase, protect, and sell additional properties, incrementally increasing the amount of protected private land. Because the effectiveness of this approach relies on selecting appropriate properties, we explored factors currently considered by practitioners and how these are integrated into decision making. We conducted exploratory, semistructured interviews with managers from each of the 5 major revolving funds in Australia. Responses indicated although conservation factors are important, financial and social factors are also highly influential. A major determinant was whether the property could be resold within a reasonable period at a price that replenishes the fund. To facilitate resale, often selected properties include the potential for the construction of a dwelling. Practitioners face with clear trade‐offs between conservation, financial, amenity, and other factors in selecting properties and 3 main challenges: recovering the costs of acquisition, protection, and resale; reselling the property; and meeting conservation goals. Our findings suggest the complexity of these decisions may constrain revolving‐fund effectiveness. Drawing from participant responses, we identified potential strategies to mitigate these risks, such as providing adequate recreational space without jeopardizing ecological assets. We suggest managers could benefit from a shared‐learning and adaptive approach to property selection given the commonalities between programs. Understanding how practitioners deal with complex decisions in the implementation of revolving funds helps identify future research to improve the performance of this conservation tool.

Synergist induced susceptibility of tobacco caterpillar, Spodoptera litura (Fabricius) from Kerala, India exposed to conventional insecticides - Sreelakshmi Pattapu; Thomas Biju Mathew; A. Josephrajkumar; Ambily Paul (Phytoparasitica, 2018)

Integrating community assembly and biodiversity to better understand ecosystem function: the Community Assembly and the Functioning of Ecosystems ( CAFE ) approach - Katherine H. Bannar‐Martin; Colin T. Kremer; S.K. Morgan Ernest; Mathew A. Leibold; Harald Auge; Jonathan Chase; Steven A.J. Declerck; Nico Eisenhauer; Stanley Harpole; Helmut Hillebrand; Forest Isbell; Thomas Koffel; et al. (Ecology Letters, 2018)
The research of a generation of ecologists was catalysed by the recognition that the number and identity of species in communities influences the functioning of ecosystems. The relationship between biodiversity and ecosystem functioning ( BEF ) is most often examined by controlling species richness and randomising community composition. In natural systems, biodiversity changes are often part of a bigger community assembly dynamic. Therefore, focusing on community assembly and the functioning of ecosystems ( CAFE ), by integrating both species richness and composition through species gains, losses and changes in abundance, will better reveal how community changes affect ecosystem function. We synthesise the BEF and CAFE perspectives using an ecological application of the Price equation, which partitions the contributions of richness and composition to function. Using empirical examples, we show how the CAFE approach reveals important contributions of composition to function. These examples show how changes in species richness and composition driven by environmental perturbations can work in concert or antagonistically to influence ecosystem function. Considering how communities change in an integrative fashion, rather than focusing on one axis of community structure at a time, will improve our ability to anticipate and predict changes in ecosystem function.

Testing the keystone community concept: effects of landscape, patch removal, and environment on metacommunity structure - Emlyn J. Resetarits; Sara E. Cathey; Mathew A. Leibold (Ecology, 2018)
Although the influence of regional processes on local patches is well studied, the influence of local patches and their spatial arrangement on regional processes is likely to be complex. One interesting idea is the keystone community concept ( KCC ); this posits that there may be some patches that have a disproportionately large effect on the metacommunity compared to other patches. We experimentally test the KCC by using replicate protist microcosm metacommunities with single‐patch removals. Removing single patches had no effect on average community richness, evenness and biomass of our metacommunities, but did cause metacommunities to be assembled significantly less by local environmental conditions and more by spatial effects related to stochastic factors. Overall our results show that local patch removal can have large regional effects on structural processes, but indicate that more experiments are needed to find evidence of keystone communities.

A comparative proteome assay on the quality of yardlong bean pods as influenced by the organic and inorganic nourishment systems - Deepthi K. Kumar; Deepu Mathew; P. A. Nazeem; P. S. Abida; C. George Thomas (Acta Physiologiae Plantarum, 2017)

Emerging Technologies and Synergies for Airborne and Space-Based Measurements of Water Vapor Profiles - Amin R. Nehrir; Christoph Kiemle; Mathew D. Lebsock; Gottfried Kirchengast; Stefan A. Buehler; Ulrich Löhnert; Cong-Liang Liu; Peter C. Hargrave; Maria Barrera-Verdejo; David M. Winker (Surveys in Geophysics, 2017)
A deeper understanding of how clouds will respond to a warming climate is one of the outstanding challenges in climate science. Uncertainties in the response of clouds, and particularly shallow clouds, have been identified as the dominant source of the discrepancy in model estimates of equilibrium climate sensitivity. As the community gains a deeper understanding of the many processes involved, there is a growing appreciation of the critical role played by fluctuations in water vapor and the coupling of water vapor and atmospheric circulations. Reduction of uncertainties in cloud-climate feedbacks and convection initiation as well as improved understanding of processes governing these effects will result from profiling of water vapor in the lower troposphere with improved accuracy and vertical resolution compared to existing airborne and space-based measurements. This paper highlights new technologies and improved measurement approaches for measuring lower tropospheric water vapor and their expected added value to current observations. Those include differential absorption lidar and radar, microwave occultation between low-Earth orbiters, and hyperspectral microwave remote sensing. Each methodology is briefly explained, and measurement capabilities as well as the current technological readiness for aircraft and satellite implementation are specified. Potential synergies between the technologies are discussed, actual examples hereof are given, and future perspectives are explored. Based on technical maturity and the foreseen near-mid-term development path of the various discussed measurement approaches, we find that improved measurements of water vapor throughout the troposphere would greatly benefit from the combination of differential absorption lidar focusing on the lower troposphere with passive remote sensors constraining the upper-tropospheric humidity.

Indigenous arthropod natural enemies of the invasive brown marmorated stink bug in North America and Europe - Paul K. Abram; Kim A. Hoelmer; Angelita Acebes-Doria; Heather Andrews; Elizabeth H. Beers; J. Christopher Bergh; Ric Bessin; David Biddinger; Paul Botch; Matthew L. Buffington; Mary L. Cornelius; Elena Costi; et al. (Journal of Pest Science, 2017)

Water Content Ratio: An Effective Substitute for Liquidity Index for Prediction of Shear Strength of Clays - Beshy Kuriakose; Benny Mathews Abraham; A. Sridharan; Babu T. Jose (Geotechnical and Geological Engineering, 2017)

Generic hierarchy of sandstone facies quality and static connectivity: an example from the Middle-Late Miocene Miri Formation, Sarawak Basin, Borneo - Numair A. Siddiqui; Abdul Hadi A. Rahman; Chow W. Sum; Manoj J. Mathew; Muhammad Hassaan; David Menier (Arabian Journal of Geosciences, 2017)

Genomic epidemiology of Cryptococcus yeasts identifies adaptation to environmental niches underpinning infection across an African HIV / AIDS cohort - Mathieu Vanhove; Mathew A. Beale; Johanna Rhodes; Duncan Chanda; Shabir Lakhi; Geoffrey Kwenda; Sile Molloy; Natasha Karunaharan; Neil Stone; Thomas S. Harrison; Tihana Bicanic; Matthew C. Fisher (Molecular Ecology, 2017)
Emerging infections caused by fungi have become a widely recognized global phenomenon and are causing an increasing burden of disease. Genomic techniques are providing new insights into the structure of fungal populations, revealing hitherto undescribed fine‐scale adaptations to environments and hosts that govern their emergence as infections. Cryptococcal meningitis is a neglected tropical disease that is responsible for a large proportion of AIDS ‐related deaths across Africa; however, the ecological determinants that underlie a patient's risk of infection remain largely unexplored. Here, we use genome sequencing and ecological genomics to decipher the evolutionary ecology of the aetiological agents of cryptococcal meningitis, Cryptococcus neoformans and Cryptococcus gattii , across the central African country of Zambia. We show that the occurrence of these two pathogens is differentially associated with biotic (macroecological) and abiotic (physical) factors across two key African ecoregions, Central Miombo woodlands and Zambezi Mopane woodlands. We show that speciation of Cryptococcus has resulted in adaptation to occupy different ecological niches, with C. neoformans found to occupy Zambezi Mopane woodlands and C. gattii primarily recovered from Central Miombo woodlands. Genome sequencing shows that C. neoformans causes 95% of human infections in this region, of which over three‐quarters belonged to the globalized lineage VNI . We show that VNI infections are largely associated with urbanized populations in Zambia. Conversely, the majority of C. neoformans isolates recovered in the environment belong to the genetically diverse African‐endemic lineage VNB , and we show hitherto unmapped levels of genomic diversity within this lineage. Our results reveal the complex evolutionary ecology that underpins the reservoirs of infection for this, and likely other, deadly pathogenic fungi.

Community assembly and the functioning of ecosystems: how metacommunity processes alter ecosystems attributes - Mathew A. Leibold; Jonathan M. Chase; S. K. Morgan Ernest (Ecology, 2017)
Recent work linking community structure and ecosystem function has primarily focused on the effects of local species richness but has neglected the dispersal‐dependent processes of community assembly that are ultimately involved in determining community structure and its relation to ecosystems. Here we combine simple consumer‐resource competition models and metacommunity theory with discussion of case studies to outline how spatial processes within metacommunities can alter community assembly and modify expectations about how species diversity and composition influence ecosystem attributes at local scales. We argue that when community assembly is strongly limited by dispersal, this can constrain ecosystem functioning by reducing positive selection effects (reducing the probability of the most productive species becoming dominant) even though it may often also enhance complementarity (favoring combinations of species that enhance production even though they may not individually be most productive). Conversely, excess dispersal with strong source‐sink relations among heterogeneous habitats can reduce ecosystem functioning by swamping local filters that would normally favor better‐suited species. Ecosystem function is thus most likely maximized at intermediate levels of dispersal where both of these effects are minimized. In this scenario, we find that the selection effect is maximized, while complementarity is often reduced and local diversity may often be relatively low. Our synthesis emphasizes that it is the entire set of community assembly processes that affect the functioning of ecosystems, not just the part that determines local species richness.

Estimating work and home population using lidar-derived building volumes - Yun Zhao; Gustavo A. Ovando-Montejo; Amy E. Frazier; Adam J. Mathews; K. Colton Flynn; Emily A. Ellis (International Journal of Remote Sensing, 2017)

Humpback whales interfering when mammal‐eating killer whales attack other species: Mobbing behavior and interspecific altruism? - Robert L. Pitman; Volker B. Deecke; Christine M. Gabriele; Mridula Srinivasan; Nancy Black; Judith Denkinger; John W. Durban; Elizabeth A. Mathews; Dena R. Matkin; Janet L. Neilson; Alisa Schulman‐Janiger; Debra Shearwater; et al. (Marine Mammal Science, 2017)
Humpback whales ( Megaptera novaeangliae ) are known to interfere with attacking killer whales ( Orcinus orca ). To investigate why, we reviewed accounts of 115 interactions between them. Humpbacks initiated the majority of interactions (57% vs . 43%; n = 72), although the killer whales were almost exclusively mammal‐eating forms ( MEKW s, 95%) vs . fish‐eaters (5%; n = 108). When MEKW s approached humpbacks ( n = 27), they attacked 85% of the time and targeted only calves. When humpbacks approached killer whales ( n = 41), 93% were MEKW s, and ≥87% of them were attacking or feeding on prey at the time. When humpbacks interacted with attacking MEKW s, 11% of the prey were humpbacks and 89% comprised 10 other species, including three cetaceans, six pinnipeds, and one teleost fish. Approaching humpbacks often harassed attacking MEKW s (≥55% of 56 interactions), regardless of the prey species, which we argue was mobbing behavior. Humpback mobbing sometimes allowed MEKW prey, including nonhumpbacks, to escape. We suggest that humpbacks initially responded to vocalizations of attacking MEKW s without knowing the prey species targeted. Although reciprocity or kin selection might explain communal defense of conspecific calves, there was no apparent benefit to humpbacks continuing to interfere when other species were being attacked. Interspecific altruism, even if unintentional, could not be ruled out.

Herbivory enhances the diversity of primary producers in pond ecosystems - Mathew A. Leibold; Spencer R. Hall; Val H. Smith; David A. Lytle (Ecology, 2017)
Diversity of primary producer is often surprisingly high, despite few limiting factors such as nutrients and light to facilitate species coexistence. In theory, the presence of herbivores could increase the diversity of primary producers, resolving this “paradox of the plankton.” Little experimental evidence supports this natural enemies hypothesis, but previous tests suffer from several deficiencies. Previous experiments often did not allow for multigeneration effects; utilized low diversity assemblages of herbivores; and limited opportunities for new primary producer and herbivore species to colonize and undergo species sorting that favors some species over others. Using pond plankton, we designed a mesocosm experiment that overcame these problems by allowing more time for interactions over multiple generations, openness to allow new colonists, and manipulated higher diversity of primary producers and grazers than have previous studies. With this design, the presence of zooplankton grazers doubled phytoplankton richness. The additional phytoplankton species in grazed mesocosms were larger, and therefore likely more grazer resistant. Furthermore, phytoplankton richness in grazed mesocosms was similar to that observed in natural ponds whereas it was much lower in mesocosms without grazers. However, stoichiometric imbalance caused by variation in nitrogen : phosphorus ratios and light supply did not alter phytoplankton richness. Therefore, grazers enhanced primary producer richness more strongly than ratios of nutrient supply (even though both grazing and ratios of resource supply altered composition of primary producer assemblages). Taken together, these experimental and field data show that grazing from a diverse assemblage of herbivores greatly elevated richness of phytoplankton producers in pond ecosystems.

The influence of vegetation and soil characteristics on active‐layer thickness of permafrost soils in boreal forest - James P. Fisher; Cristian Estop‐Aragonés; Aaron Thierry; Dan J. Charman; Stephen A. Wolfe; Iain P. Hartley; Julian B. Murton; Mathew Williams; Gareth K. Phoenix (Global Change Biology, 2016)
Carbon release from thawing permafrost soils could significantly exacerbate global warming as the active‐layer deepens, exposing more carbon to decay. Plant community and soil properties provide a major control on this by influencing the maximum depth of thaw each summer (active‐layer thickness; ALT ), but a quantitative understanding of the relative importance of plant and soil characteristics, and their interactions in determine ALT s, is currently lacking. To address this, we undertook an extensive survey of multiple vegetation and edaphic characteristics and ALT s across multiple plots in four field sites within boreal forest in the discontinuous permafrost zone ( NWT , Canada). Our sites included mature black spruce, burned black spruce and paper birch, allowing us to determine vegetation and edaphic drivers that emerge as the most important and broadly applicable across these key vegetation and disturbance gradients, as well as providing insight into site‐specific differences. Across sites, the most important vegetation characteristics limiting thaw (shallower ALT s) were tree leaf area index ( LAI ), moss layer thickness and understory LAI in that order. Thicker soil organic layers also reduced ALT s, though were less influential than moss thickness. Surface moisture (0–6 cm) promoted increased ALT s, whereas deeper soil moisture (11–16 cm) acted to modify the impact of the vegetation, in particular increasing the importance of understory or tree canopy shading in reducing thaw. These direct and indirect effects of moisture indicate that future changes in precipitation and evapotranspiration may have large influences on ALT s. Our work also suggests that forest fires cause greater ALT s by simultaneously decreasing multiple ecosystem characteristics which otherwise protect permafrost. Given that vegetation and edaphic characteristics have such clear and large influences on ALT s, our data provide a key benchmark against which to evaluate process models used to predict future impacts of climate warming on permafrost degradation and subsequent feedback to climate.

Relating fish health and reproductive metrics to contaminant bioaccumulation at the Tennessee Valley Authority Kingston coal ash spill site - Brenda M. Pracheil; S. Marshall Adams; Mark S. Bevelhimer; Allison M. Fortner; Mark S. Greeley; Cheryl A. Murphy; Teresa J. Mathews; Mark J. Peterson (Ecotoxicology, 2016)

Compensatory dynamics stabilize aggregate community properties in response to multiple types of perturbations - Bryan L. Brown; Amy L. Downing; Mathew A. Leibold (Ecology, 2016)
Compensatory dynamics are an important suite of mechanisms that can stabilize community and ecosystem attributes in systems subject to environmental fluctuations. However, few experimental investigations of compensatory dynamics have addressed these mechanisms in systems of real‐world complexity, and existing evidence relies heavily on correlative analyses, retrospective examination, and experiments in simple systems. We investigated the potential for compensatory dynamics to stabilize plankton communities in plankton mesocosm systems of real‐world complexity. We employed four types of perturbations including two types of nutrient pulses, shading, and acidification. To quantify how communities responded to these perturbations, we used a measure of community‐wide synchrony combined with spectral analysis that allowed us to assess timescale‐specific community dynamics, for example, whether dynamics were synchronous at some timescales but compensatory at others. The 150‐d experiment produced 32‐point time series of all zooplankton taxa in the mesocosms. We then used those time series to evaluate total zooplankton biomass as an aggregate property and to evaluate community dynamics. For three of our four perturbation types, total zooplankton biomass was significantly less variable in systems with environmental variation than in constant environments. For the same three perturbation types, community‐wide synchrony was much lower in fluctuating environments than in the constant environment, particularly at longer timescales (periods ≈ 60 d). Additionally, there were strong negative correlations between population temporal variances and the level of community‐wide synchrony. Taken together, these results strongly imply that compensatory interactions between species stabilized total biomass in response to perturbations. Diversity did not differ significantly across either treatments or perturbation types, thus ruling out several classes of mechanisms driven by changes in diversity. We also used several pieces of secondary evidence to evaluate the particular mechanism behind compensatory responses since a wide variety of mechanisms are hypothesized to produce compensatory dynamics. We concluded that fluctuation dependent endogenous cycles that occur as a consequence of consumer–resource interactions in competitive communities were the most likely explanation for the compensatory dynamics observed in our experiment. As with our previous work, scale‐dependent dynamics were also a key to understanding compensatory dynamics in these experimental communities.

Is conservation agriculture ‘climate-smart’ for maize farmers in the highlands of Tanzania? - Anthony A. Kimaro; Mathew Mpanda; Janie Rioux; Ermias Aynekulu; Samuel Shaba; Margaret Thiong’o; Paul Mutuo; Sheila Abwanda; Keith Shepherd; Henry Neufeldt; Todd S. Rosenstock (Nutrient Cycling in Agroecosystems, 2016)

Intravesical PAC1 Receptor Antagonist, PACAP(6–38), Reduces Urinary Bladder Frequency and Pelvic Sensitivity in NGF-OE Mice - Beatrice M. Girard; Susan E. Malley; Morgan M. Mathews; Victor May; Margaret A. Vizzard (Journal of Molecular Neuroscience, 2016)

Cranial Shape and the Modularity of Hybridization in Dingoes and Dogs; Hybridization Does Not Spell the End for Native Morphology - William C. H. Parr; Laura A. B. Wilson; Stephen Wroe; Nicholas J. Colman; Mathew S. Crowther; Mike Letnic (Evolutionary Biology, 2016)

Age-dependent motor unit remodelling in human limb muscles - Mathew Piasecki; Alex Ireland; David A. Jones; Jamie S. McPhee (Biogerontology, 2016)

Local-scale spatial modelling for interpolating climatic temperature variables to predict agricultural plant suitability - Mathew A. Webb; Andrew Hall; Darren Kidd; Budiman Minansy (Theoretical and Applied Climatology, 2016)

Taxonomy of prokaryotic viruses: update from the ICTV bacterial and archaeal viruses subcommittee - Mart Krupovic; Bas E. Dutilh; Evelien M. Adriaenssens; Johannes Wittmann; Finn K. Vogensen; Mathew B. Sullivan; Janis Rumnieks; David Prangishvili; Rob Lavigne; Andrew M. Kropinski; Jochen Klumpp; Annika Gillis; et al. (Archives of Virology, 2016)

Comparing estimates of number of breeders N b based on microsatellites and single nucleotide polymorphism of three groups of brown trout ( Salmo trutta L.) - A. N. Linløkken; T. O. Haugen; P. K. Mathew; W. Johansen; S. Lien (Fisheries Management and Ecology, 2016)
Microsatellites (10 MS s) and single nucleotide polymorphism (3871 SNP s) were analysed in three closely related, single‐cohort groups of brown trout, Salmo trutta L. Autumn (W/0+) and subsequent year (W/1+) samples of brown trout of the same stream were retrieved using electric fishing, and one sample of artificially reared brown trout (H/1+), bred from wild parents, was collected from a hatchery. The number of breeders, N b , was estimated based on each total sample set and from subsets of loci by means of the software LDN e, and by means of Colony2, NeEstimator and ON e SAMP softwares. MS ‐based estimates were consequently higher than those based on SNP s. ML ‐Relate and Colony2 software was used to estimate putative full‐sib pairs, and there was considerable variation between methods. For monitoring species and populations, both methods are recommended, but to compare N b across samples and years, the same markers of MS s or SNP s must be used as estimates varied across markers within sample.

A randomized, placebo-controlled pilot trial of the delta opioid receptor agonist AZD2327 in anxious depression - Erica M. Richards; Daniel C. Mathews; David A. Luckenbaugh; Dawn F. Ionescu; Rodrigo Machado-Vieira; Mark J. Niciu; Wallace C. Duncan; Neal M. Nolan; Jose A. Franco-Chaves; Thomas Hudzik; Carla Maciag; Shuang Li; et al. (Psychopharmacology, 2016)

Intensification of Southern Hemisphere westerly winds 2000–1000 years ago: evidence from the subantarctic Campbell and Auckland Islands (52–50°S) - Chris S. M. Turney; Matt M c Glone; Jonathan Palmer; Christopher Fogwill; Alan Hogg; Zoë A. Thomas; Mathew Lipson; Janet M. Wilmshurst; Pavla Fenwick; Richard T. Jones; Ben Hines; Graeme F. Clark (Journal of Quaternary Science, 2016)
The Southern Ocean plays a significant role in driving global climate–ocean–carbon dynamics. Unfortunately, a relative dearth of datasets across the region limits our ability to understand past and future mechanisms of change. Here we report a new dataset from the south‐west Pacific: radiocarbon‐dated subfossil tree stumps ( Dracophyllum ) eroding out from peat exposures on Campbell and Auckland Islands (52–50°S). Dracophyllum are the southernmost growing trees in the south‐west Pacific and their growth on exposed sites and at altitude is strongly controlled by the prevailing westerly airflow, providing a unique measure of past changes in zonal wind strength. Here we demonstrate a significant collapse in the altitudinal limit of growth between approximately 2000 and 1000 years ago (hereafter 2–1 ka), consistent with other records across the Southern Hemisphere that indicate westerly airflow was significantly enhanced. Importantly, this period in the late Holocene was one of marked change across the broader region, suggesting westerly airflow played a key role in driving Southern Ocean variability at this time.

Identification and characterization of Fusarium spp. associated with root rots of field pea in North Dakota - Kishore Chittem; Febina M. Mathew; Matthew Gregoire; Robin S. Lamppa; Yen Wei Chang; Samuel G. Markell; Carl A. Bradley; Tharcisse Barasubiye; Rubella S. Goswami (European Journal of Plant Pathology, 2015)

Species sorting and patch dynamics in harlequin metacommunities affect the relative importance of environment and space - Mathew A. Leibold; Nicolas Loeuille (Ecology, 2015)
Metacommunity theory indicates that variation in local community structure can be partitioned into components including those related to local environmental conditions vs. spatial effects and that these can be quantified using statistical methods based on variation partitioning. It has been hypothesized that joint associations of community composition with environment and space could be due to patch dynamics involving colonization–extinction processes in environmentally heterogeneous landscapes but this has yet to be theoretically shown. We develop a two‐patch, type‐two, species competition model in such a “harlequin” landscape (where different patches have different environments) to evaluate how composition is related to environmental and spatial effects as a function of background extinction rate. Using spatially implicit analytical models, we find that the environmental association of community composition declines with extinction rate as expected. Using spatially explicit simulation models, we further find that there is an increase in the spatial structure with extinction due to spatial patterning into clusters that are not related to environmental conditions but that this increase is limited. Natural metacommunities often show both environment and spatial determination even under conditions of relatively high isolation and these could be more easily explained by our model than alternative metacommunity models.

Disturbance‐mediated colonization–extinction dynamics in experimental protist metacommunities - Kayoko Fukumori; George Livingston; Mathew A. Leibold (Ecology, 2015)
Colonization–extinction dynamics and species sorting among habitats determine the distribution of species within metacommunities. Theory suggests that disturbances reduce the importance of species sorting and enhance spatial patterning and stochastic effects, however this has not yet been experimentally shown. We examined how extinctions in a heterogeneous landscape of patches affects the influence of environmental, spatial, and stochastic factors on community composition in a simple two‐species, two‐habitat, protist metacommunity where each species dominates in a different habitat type. We imposed four different levels of random extinctions on local patches and monitored changes in the metacommunity through time. We found that near‐steady state patterns of community variability developed relatively rapidly (within nine colonization–extinction cycles) and that increased extinction rate produced altered patterns of community regulation by reducing environmental control and increasing spatial and stochastic effects. Our results indicate a possible explanation for the combination of environmental, spatial and stochastic effects observed in natural metacommunities.

Mouse genome annotation by the RefSeq project - Kelly M. McGarvey; Tamara Goldfarb; Eric Cox; Catherine M. Farrell; Tripti Gupta; Vinita S. Joardar; Vamsi K. Kodali; Michael R. Murphy; Nuala A. O’Leary; Shashikant Pujar; Bhanu Rajput; Sanjida H. Rangwala; et al. (Mammalian Genome, 2015)
Complete and accurate annotation of the mouse genome is critical to the advancement of research conducted on this important model organism. The National Center for Biotechnology Information (NCBI) develops and maintains many useful resources to assist the mouse research community. In particular, the reference sequence (RefSeq) database provides high-quality annotation of multiple mouse genome assemblies using a combinatorial approach that leverages computation, manual curation, and collaboration. Implementation of this conservative and rigorous approach, which focuses on representation of only full-length and non-redundant data, produces high-quality annotation products. RefSeq records explicitly link sequences to current knowledge in a timely manner, updating public records regularly and rapidly in response to nomenclature updates, addition of new relevant publications, collaborator discussion, and user feedback. Whole genome re-annotation is also conducted at least every 12–18 months, and often more frequently in response to assembly updates or availability of informative data. This article highlights key features and advantages of RefSeq genome annotation products and presents an overview of NCBI processes to generate these data. Further discussion of NCBI’s resources highlights useful features and the best methods for accessing our data.

Quantifying landscape‐level methane fluxes in subarctic Finland using a multiscale approach - Iain. P. Hartley; Timothy. C. Hill; Thomas. J. Wade; Robert. J. Clement; John. B. Moncrieff; Ana. Prieto‐Blanco; Mathias. I. Disney; Brian. Huntley; Mathew. Williams; Nicholas. J. K. Howden; Philip. A. Wookey; Robert. Baxter (Global Change Biology, 2015)
Quantifying landscape‐scale methane ( CH 4 ) fluxes from boreal and arctic regions, and determining how they are controlled, is critical for predicting the magnitude of any CH 4 emission feedback to climate change. Furthermore, there remains uncertainty regarding the relative importance of small areas of strong methanogenic activity, vs. larger areas with net CH 4 uptake, in controlling landscape‐level fluxes. We measured CH 4 fluxes from multiple microtopographical subunits (sedge‐dominated lawns, interhummocks and hummocks) within an aapa mire in subarctic Finland, as well as in drier ecosystems present in the wider landscape, lichen heath and mountain birch forest. An intercomparison was carried out between fluxes measured using static chambers, up‐scaled using a high‐resolution landcover map derived from aerial photography and eddy covariance. Strong agreement was observed between the two methodologies, with emission rates greatest in lawns. CH 4 fluxes from lawns were strongly related to seasonal fluctuations in temperature, but their floating nature meant that water‐table depth was not a key factor in controlling CH 4 release. In contrast, chamber measurements identified net CH 4 uptake in birch forest soils. An intercomparison between the aerial photography and satellite remote sensing demonstrated that quantifying the distribution of the key CH 4 emitting and consuming plant communities was possible from satellite, allowing fluxes to be scaled up to a 100 km 2 area. For the full growing season (May to October), ~ 1.1–1.4 g CH 4 m −2 was released across the 100 km 2 area. This was based on up‐scaled lawn emissions of 1.2–1.5 g CH 4 m −2 , vs. an up‐scaled uptake of 0.07–0.15 g CH 4 m −2 by the wider landscape. Given the strong temperature sensitivity of the dominant lawn fluxes, and the fact that lawns are unlikely to dry out, climate warming may substantially increase CH 4 emissions in northern Finland, and in aapa mire regions in general.

Diel bank migration of Burbot (Lota lota) - Peter A. Cott; Mathew M. Guzzo; A. J. Chapelsky; Scott W. Milne; Paul J. Blanchfield (Hydrobiologia, 2015)

New onset executive function difficulties at menopause: a possible role for lisdexamfetamine - C. Neill Epperson; Sheila Shanmugan; Deborah R. Kim; Sarah Mathews; Kathryn A. Czarkowski; Jeanette Bradley; Dina H. Appleby; Claudia Iannelli; Mary D. Sammel; Thomas E. Brown (Psychopharmacology, 2015)

Evaluation of the protective effect of Pterocarpus marsupium on acetic acid-induced ulcerative colitis in rats - Merin Maria Mathew; Nguyen Vinh Han; A. Murugesan; E. Arun Raj; K. G. Prasanth (Inflammopharmacology, 2015)

Linking place-based science to people through spatial narratives of coastal stewardship - J. Silbernagel; G. Host; C. Hagley; D. Hart; R. Axler; R. Fortner; M. Axler; V. Smith; A. Drewes; W. Bartsch; N. Danz; J. Mathews; et al. (Journal of Coastal Conservation, 2015)

Phenological decoupling of mortality from wave forcing in kelp beds - Thibaut de Bettignies; Thomas Wernberg; Paul S. Lavery; Mathew A. Vanderklift; Jim R. Gunson; Graham Symonds; Neil Collier (Ecology, 2015)
Kelps often live in a harsh hydrodynamic environment where wave‐driven dislodgement of individuals can alter the biodiversity and functioning of reef systems, and increase production in coastal ecosystems adjacent to reefs. The current paradigm is that winter storms tear kelps from reefs once hydrodynamic forces exceed attachment or tissue strength—a threshold response that implies a pulsed relationship between wave forces and dislodgement. Here, we challenge this understanding by showing how kelp phenology can decouple susceptibility to dislodgement from seasonal patterns in wave forces. We measured kelp dislodgement rates and hydrodynamic forces at nine subtidal reefs over two years ( n = 4320 kelps tagged and monitored). Contrary to expectation, we found relatively low and constant dislodgement rates for all reefs (13% ± 6% [mean per season ± SD]) in spite of a strong temporal pattern in wave action and extreme water velocities (winter peaks up to 3–4 m/s). A biomechanical model, based on the balance between kelp attachment strength and hydrodynamic drag, demonstrated that severe reduction in individual kelp size toward winter (>50% decrease in biomass for all sites) minimized drag and made the kelps less susceptible to high water velocities, allowing individuals to survive storm velocities over 3–4 m/s. We conclude that the timing of reduced susceptibility to disturbance, through the seasonal reduction of individual kelp biomass that coincides with times of highest water velocities is critical to the dynamics of kelp dislodgement and survival. We propose that phenological processes maintain many kelp beds in a higher degree of population stability and equilibrium with hydrodynamic forces than previously believed.

Striatal dopamine dynamics in mice following acute and repeated toluene exposure - Aaron K. Apawu; Tiffany A. Mathews; Scott E. Bowen (Psychopharmacology, 2015)

mGluR5 positive allosteric modulation and its effects on MK-801 induced set-shifting impairments in a rat operant delayed matching/non-matching-to-sample task - Amber L. LaCrosse; Brian T. Burrows; Rachel M. Angulo; Phoebe R. Conrad; Sarah M. Himes; Nordia Mathews; Scott A. Wegner; Sara B. Taylor; M. Foster Olive (Psychopharmacology, 2015)

Delineating dambo catenary soil-landscape units using aerial gamma-ray and terrain data: a comparison of classification approaches - Jerome S. Lugumira; David J. Brown; Philip E. Dennison; Mathew K. Hansen; Lee A. Vierling (International Journal of Remote Sensing, 2014)

Anti-inflammatory potential of β-amyrin, a triterpenoid isolated from Costus igneus - Kripa Krishnan; Limi Elizabeth Mathew; N. R. Vijayalakshmi; A. Helen (Inflammopharmacology, 2014)

Life history traits, but not phylogeny, drive compositional patterns in a butterfly metacommunity - Sandrine Pavoine; Michel Baguette; Virginie M. Stevens; Mathew A. Leibold; Camille Turlure; Michael B. Bonsall (Ecology, 2014)
Community assembly is a combination of ecological, evolutionary, and stochastic processes. Separating out the abiotic and biotic processes (such as limiting similarity or environmental filtering) from stochastic processes is central to developing a cogent approach for understanding patterns in ecological community structure and organization. Using butterfly communities in a fragmented landscape, we tested the hypothesis that local environmental filtering drives character convergences in traits of species belonging to different clades. We found that, while many traits were determined both by phylogeny and environment, trait convergence within the phylogeny was extensive and eroded the phylogenetic structure associated with habitat use. Traits associated with habitat use are shown to be only moderately phylogenetically conserved in chalk grassland butterfly assemblages, and further analysis revealed that traits associated with environmental filtering may be highly labile rather than phylogenetically conserved. In general, a significant phylogenetic signal is therefore neither sufficient to demonstrate a lack of trait convergence, nor to determine whether communities are likely to be phylogenetically structured. We conclude that explicit trait‐based approaches should be used in preference to the more indirect approach based on phylogenetic conservatism for understanding metacommunity assembly processes.

Whole-genome analyses of DS-1-like human G2P[4] and G8P[4] rotavirus strains from Eastern, Western and Southern Africa - Martin M. Nyaga; Karla M. Stucker; Mathew D. Esona; Khuzwayo C. Jere; Bakari Mwinyi; Annie Shonhai; Enyonam Tsolenyanu; Augustine Mulindwa; Julia N. Chibumbya; Hokororo Adolfine; Rebecca A. Halpin; Sunando Roy; et al. (Virus Genes, 2014)

Akashiwo sanguinea (Dinophyceae) extruding mucous from pores on the cell surface - Susan Badylak; Edward J. Phlips; A. Loren Mathews; Karen Kelley (Algae, 2014)

Development of an In Vitro Model System for Studying Bacterially Expressed dsRNA-Mediated Knockdown in Neoparamoeba genus - Paula C. Lima; Natasha A. Botwright; James O. Harris; Mathew Cook (Marine Biotechnology, 2014)

Application of the Rosner–Wei risk-prediction model to estimate sexual orientation patterns in colon cancer risk in a prospective cohort of US women - S. Bryn Austin; Mathew J. Pazaris; Esther K. Wei; Bernard Rosner; Grace A. Kennedy; Deborah Bowen; Donna Spiegelman (Cancer Causes & Control, 2014)

Performance evaluation of environmentally compatible stormwater filtration systems - M. P. Samuel; S. Senthilvel; A. C. Mathew (International Journal of Environmental Science and Technology, 2014)

Dexamphetamine effects on prepulse inhibition (PPI) and startle in healthy volunteers - Kate Chitty; Matthew A. Albrecht; Kyran Graham; Chantelle Kerr; Joseph W. Y. Lee; Rajan Iyyalol; Mathew T. Martin-Iverson (Psychopharmacology, 2014)

Effects of local negative feedbacks on the evolution of species within metacommunities - Nicolas Loeuille; Mathew A. Leibold (Ecology Letters, 2014)
Local negative feedbacks occur when the occupation of a site by a species decreases the subsequent fitness of related individuals compared to potential competitors. Such negative feedbacks can enhance diversity by changing the spatial structure of the environment. The conditions, however, involve dispersive, environmental and evolutionary processes in complex interactive ways. We introduce a model that accounts for four mechanisms: colonisation‐competition‐extinction ecological dynamics, evolutionary dynamics, local negative feedbacks and environmental averaging. Three qualitatively distinct dynamics are possible, one dominated by specialists, another dominated by generalists and an intermediate situation exhibiting taxon cycles. We discuss how metacommunity diversity, macro‐ecological patterns and environmental patterning are linked to the three qualitative dynamics. The model provides classical shapes for morph‐abundance distributions, or diversity‐area relationships. Diversity can be high when specialists dominate or when taxon cycles happen. Finally, local negative feedbacks often yield fine‐grain environments for taxon cycle dynamics and coarse‐grain environments when generalists dominate.

Neurocognitive effects of ketamine in treatment-resistant major depression: association with antidepressant response - James W. Murrough; Le-Ben Wan; Brian Iacoviello; Katherine A. Collins; Carly Solon; Benjamin Glicksberg; Andrew M. Perez; Sanjay J. Mathew; Dennis S. Charney; Dan V. Iosifescu; Katherine E. Burdick (Psychopharmacology, 2014)

Multiple diversity–stability mechanisms enhance population and community stability in aquatic food webs - Amy L. Downing; Bryan L. Brown; Mathew A. Leibold (Ecology, 2014)
Biodiversity has been shown to increase the temporal stability of community and ecosystem attributes through multiple mechanisms, but these same mechanisms make less consistent predictions about the effects of richness on population stability. The overall effects of biodiversity on population and community stability will therefore depend on the dominant mechanisms that are likely to vary with the nature of biodiversity loss and the degree of environmental variability. We conducted a mesocosm experiment in which we generated a gradient in zooplankton species richness by directly manipulating dominant species and by allowing/preventing immigration from a metacommunity. The mesocosms were maintained under either constant or variable nutrient environments. Population, community, and ecosystem data were collected for five months. We found that zooplankton population and community stability is enhanced in species‐rich communities in both constant and variable environments. Species richness increased primarily through the addition of species with low abundance. The communities that were connected to a metacommunity via immigration were the most diverse and the most stable, indicating the importance of both metacommunity dynamics and rare species for stability. We found little evidence for selection effects or overyielding as stabilizing forces. We did find support for asynchronous dynamics and statistical averaging, both of which predict destabilizing effects at the population level. We also found support for weak interactions, which predicts that both populations and communities will become more stable as richness increases. In order to understand the effects of biodiversity loss on stability, we will need to understand when different stabilizing mechanisms tend to operate but also how multiple mechanisms interact.

Genetic Diversity in Exon 2 of the Major Histocompatibility Complex Class II DQB1 Locus in Nigerian Goats - Abdulmojeed Yakubu; Adebowale E. Salako; Marcos De Donato; Michael I. Takeet; Sunday O. Peters; Mufliat A. Adefenwa; Moses Okpeku; Mathew Wheto; Brilliant O. Agaviezor; Timothy M. Sanni; Oyeyemi O. Ajayi; Gbolabo O. Onasanya; et al. (Biochemical Genetics, 2013)

The dynamics of community assembly under sudden mixing in experimental microcosms - George Livingston; Yuexin Jiang; Jeremy W. Fox; Mathew A. Leibold (Ecology, 2013)
Landscape connectivity has been shown to alter community assembly and its consequences. Here we examine how strong, sudden changes in connectivity may affect community assembly by conducting experiments on the effects of “community mixing,” situations where previously isolated communities become completely connected with consequent community reorganization. Previous theory indicates that assembly history dictates the outcome of mixing: mixing randomly assembled communities leads to a final community with random representation from the original communities, while mixing communities that were assembled via a long history of colonizations and extinctions leads to strong asymmetry, with one community dominating the other. It also predicts that asymmetry should be stronger in the presence of predators in the system. We experimentally tested and explored this theory by mixing aquatic microcosms inhabited by a complex food web of heterotrophic protists, and algae. Our results confirm the prediction that long assembly history can produce asymmetry under mixing and suggest these dynamics could be important in natural systems. However, in contrast to previous theory we also found asymmetry weaker under mixing of communities with more complex trophic structure.

A novel rearrangement of occludin causes brain calcification and renal dysfunction - Marissa A. LeBlanc; Lynette S. Penney; Daniel Gaston; Yuhao Shi; Erika Aberg; Mathew Nightingale; Haiyan Jiang; Roxanne M. Gillett; Somayyeh Fahiminiya; Christine Macgillivray; Ellen P. Wood; Philip D. Acott; et al. (Human Genetics, 2013)

Evaluation of the Hybrid III and Q-Series Pediatric ATD Upper Neck Loads as Compared to Pediatric Volunteers in Low-Speed Frontal Crashes - Thomas Seacrist; Emily A. Mathews; Sriram Balasubramanian; Matthew R. Maltese; Kristy B. Arbogast (Annals of Biomedical Engineering, 2013)

An institutional strategy to increase minority recruitment to therapeutic trials - Victoria V. Anwuri; Lannis E. Hall; Katherine Mathews; Brian C. Springer; Jennifer R. Tappenden; Dione M. Farria; Sherrill Jackson; Melody S. Goodman; Timothy J. Eberlein; Graham A. Colditz (Cancer Causes & Control, 2013)

Predation inhibits the positive effect of dispersal on intraspecific and interspecific synchrony in pond metacommunities - Jennifer G. Howeth; Mathew A. Leibold (Ecology, 2013)
Recent interest in the ecological drivers of compensatory and synchronous population dynamics has provided an improved yet incomplete understanding of local and regional population oscillations in response to variable environments. Here, we evaluate the effect of dispersal rate and spatiotemporal heterogeneity in predation by the selective planktivore, bluegill sunfish ( Lepomis macrochirus ), on local and regional dynamics of zooplankton in pond metacommunities. A metacommunity consisted of three pond mesocosm communities, one with constant presence of predators, one without predators, and one with alternating presence–absence of predators. The three communities were connected at either no, low (0.7% per day), or high (20% per day) planktonic dispersal. Results demonstrate that heterogeneous predation (1) prevents spatial synchrony among prey populations across local communities, (2) disrupts the synchronous population dynamics within communities produced by dispersal, and (3) induces local compensatory dynamics between species within communities regardless of dispersal rate. Taken together, the results emphasize that spatiotemporal heterogeneity in selective predation can inhibit both intraspecific and interspecific synchrony in metacommunities.

Hindcasting water clarity from Landsat satellite images of unmonitored shallow lakes in the Waikato region, New Zealand - Brendan J. Hicks; Glen A. Stichbury; Lars K. Brabyn; Mathew G. Allan; Salman Ashraf (Environmental Monitoring and Assessment, 2013)

Contrasting mechanisms of dislodgement and erosion contribute to production of kelp detritus - Thibaut de Bettignies; Thomas Wernberg; Paul S. Lavery; Mathew A. Vanderklift; Margaret B. Mohring (Limnology and Oceanography, 2013)
We quantified simultaneously dislodgement and erosion for a dominant kelp species ( Ecklonia radiata ) over 1 yr, and related both to potential explanatory factors (wave exposure, temperature, and kelp fecundity). Erosion was the largest contributor of detritus, accounting for 80% of annual production. Most erosion occurred as a major pulse in autumn, whereas dislodgement was a minor and constant process throughout the year. Neither erosion nor dislodgement was correlated with water velocity (as often proposed), and this finding contradicts the common assumption that high dislodgement rates during peak wave action account for the bulk of detrital production. Together with low growth, the high erosion rate led to a severe reduction of individual kelp biomass in autumn (from 600 g to 300 g fresh weight kelp −1 ), reducing drag forces on kelp thalli by ∼ 50%, likely reducing their susceptibility to dislodgement during peak wave action. Instead, a pulse of detrital production coincided with periods of peak kelp fecundity. We propose that sporogenesis weakens the tissue, making E. radiata more susceptible to erosion, and that the ensuing changes in kelp morphology decouple detrital production from the wave‐action forces.

CS1 (SLAMF7) inhibits production of proinflammatory cytokines by activated monocytes - Jong R. Kim; Nathan C. Horton; Stephen O. Mathew; Porunelloor A. Mathew (Inflammation Research, 2013)

Erratum to: QTL for yield and associated traits in the Seri/Babax population grown across several environments in Mexico, in the West Asia, North Africa, and South Asia regions - Marta S. Lopes; Matthew P. Reynolds; C. Lynne McIntyre; Ky L. Mathews; M. R. Jalal Kamali; Moussa Mossad; Yousef Feltaous; Izzat S. A. Tahir; Ravish Chatrath; Francis Ogbonnaya; Michael Baum (Theoretical and Applied Genetics, 2013)

Predictors of regional establishment success and spread of introduced non‐indigenous vertebrates - Craig R. Allen; Kristine T. Nemec; Donald A. Wardwell; Justin D. Hoffman; Mathew Brust; Karie L. Decker; Daniel Fogell; Jennifer Hogue; Aaron Lotz; Thaddeus Miller; Marcy Pummill; Luis E. Ramirez‐Yañez; et al. (Global Ecology and Biogeography, 2013)
Aim To provide the first analysis of predictors of both establishment and spread, both within and across taxa, for all vertebrate taxa within a region. We used F lorida, USA , as our study system because it has a well‐documented history of introduction and invasion, and is a hotspot for biological invasions. Location F lorida, USA. Methods We analysed non‐indigenous species ( NIS ) data from peninsular F lorida – which included both successful and unsuccessful introductions from all vertebrate classes – to determine the best predictors of both establishment and spread for fish (65 species), herpetofauna (63 species), birds (71 species) and mammals (25 species). We used 10 variables proposed to be associated with the establishment and spread of NIS : body mass, geographic origin, reproductive rate, diet generalism, native‐range size, latitude of native range, number of NIS present at date of introduction, presence of NIS congeners, morphological proximity to other NIS (in terms of body mass) and propagule pressure. A multimodel selection process was used with an information‐theoretic approach to determine the best fit models for predicting establishment and spread of NIS . We selected a priori plausible predictive models for establishment and spread. Results Large native‐range size and small body mass best predicted establishment of non‐indigenous herpetofauna. The presence of NIS congeners had the largest positive effect on the establishment of non‐indigenous fish. For mammals, the number of NIS present at the time of introduction best explained establishment. No single model best explained bird establishment. For all taxa but birds, the number of NIS present at time of introduction was included in at least one of the best‐supported models for explaining spread. Main conclusions Our analyses suggest that predictors of establishment and spread differ across vertebrate taxa at the scale studied. Most predictive variables can be interpreted as measures of competitive interactions among species.

From bonito to anchovy: a reconstruction of Turkey’s marine fisheries catches (1950-2010) - A. ULMAN; S. BEKISOGLU; M.A ZENGIN; S. KNUDSEN; V. UNAL; C. MATHEWS; S. HARPER; D. ZELLER; D. PAULY (Mediterranean Marine Science, 2013)
Turkey’s marine fisheries catches were estimated for the 1950-2010 time period using a reconstruction approach, which estimated all fisheries removals, including unreported landings, recreational landings and discards. We added these estimates to the ‘official’ data, as reported in TURKSTAT, which are also available from the United Nation’s Food and Agriculture Organization (FAO). The total reconstructed catch for the 1950-2010 time period (inclusive of the reported data) is approximately 32 million t, or 74% more than the 18.4 million t of reported data. This added approximately 13.6 million t to the reported data, consisting of 6.9 million t of unreported landings, 2.6 million t of discards, 2.4 million t of recreational catches, and 1.7 million t of subsistence catches. In 2010, total reported marine landings for Turkey were 445,680 t and the total reconstructed catch was 763,760 t, or 73% more than the reported data. The main unreported taxon by tonnage was European anchovy (Engraulis encrasicolus) due to its sheer high proportion of catch. The major reasons for underreporting include a general distrust fishers have towards the taxing system combined with inefficient fisheries monitoring and surveillance capabilities. Accounting for all fisheries components is crucial in understanding the development of fisheries resources, improving management, and reducing threats to the domestic food security of Turkey.

Application of the ELOHA Framework to Regulated Rivers in the Upper Tennessee River Basin: A Case Study - Ryan A. McManamay; Donald J. Orth; Charles A. Dolloff; David C. Mathews (Environmental Management, 2013)

Combined Effects of Soil Freezing and N Addition on Losses and Interception of N Over Winter and Summer - Mathew R. Vankoughnett; Hugh A. L. Henry (Ecosystems, 2013)

QTL for yield and associated traits in the Seri/Babax population grown across several environments in Mexico, in the West Asia, North Africa, and South Asia regions - Marta S. Lopes; Matthew P. Reynolds; C. Lynne McIntyre; Ky L. Mathews; M. R. Jalal Kamali; Moussa Mossad; Yousef Feltaous; Izzat S. A. Tahir; Ravish Chatrath; Francis Ogbonnaya; Michael Baum (Theoretical and Applied Genetics, 2013)

Agonist and antagonist binding to the nuclear vitamin D receptor: dynamics, mutation effects and functional implications - Sepideh Yaghmaei; Christopher Roberts; Rizi Ai; Mathew T Mizwicki; Chia-en A Chang (In Silico Pharmacology, 2013)
Purpose The thermodynamically favored complex between the nuclear vitamin D receptor (VDR) and 1α,25(OH) 2 -vitamin D 3 (1,25D3) triggers a shift in equilibrium to favor VDR binding to DNA, heterodimerization with the nuclear retinoid x receptor (RXR) and subsequent regulation of gene transcription. The key amino acids and structural requirements governing VDR binding to nuclear coactivators (NCoA) are well defined. Yet very little is understood about the internal changes in amino acid flexibility underpinning the control of ligand affinity, helix 12 conformation and function. Herein, we use molecular dynamics (MD) to study how the backbone and side-chain flexibility of the VDR differs when a) complexed to 1α,25(OH) 2 -vitamin D 3 (1,25D3, agonist) and (23S),25-dehydro-1α(OH)-vitamin D 3 -26,23-lactone (MK, antagonist); b) residues that form hydrogen bonds with the C25-OH (H305 and H397) of 1,25D3 are mutated to phenylalanine; c) helix 12 conformation is changed and ligand is removed; and d) x-ray water near the C1- and C3-OH groups of 1,25D3 are present or replaced with explicit solvent. Methods We performed molecular dynamic simulations on the apo- and holo-VDRs and used T-Analyst to monitor the changes in the backbone and side-chain flexibility of residues that form regions of the VDR ligand binding pocket (LBP), NCoA surface and control helix 12 conformation. Results The VDR-1,25D3 and VDR-MK MD simulations demonstrate that 1,25D3 and MK induce highly similar changes in backbone and side-chain flexibility in residues that form the LBP. MK however did increase the backbone and side-chain flexibility of L404 and R274 respectively. MK also induced expansion of the VDR charge clamp (i.e. NCoA surface) and weakened the intramolecular interaction between H305---V418 (helix 12) and TYR401 (helix 11). In VDR_FF, MK induced a generally more rigid LBP and stronger interaction between F397 and F422 than 1,25D3, and reduced the flexibility of the R274 side-chain. Lastly the VDR MD simulations indicate that R274 can sample multiple conformations in the presence of ligand. When the R274 is extended, the β-OH group of 1,25D3 lies proximal to the backbone carbonyl oxygen of R274 and the side-chain forms H-bonds with hinge domain residues. This differs from the x-ray, kinked geometry, where the side-chain forms an H-bond with the 1α-OH group. Furthermore, 1,25D3, but not MK was observed to stabilize the x-ray geometry of R274 during the > 30 ns MD runs. Conclusions The MD methodology applied herein provides an in silico foundation to be expanded upon to better understand the intrinsic flexibility of the VDR and better understand key side-chain and backbone movements involved in the bimolecular interaction between the VDR and its’ ligands.

The effects of protection from fishing on species richness: distinguishing between alternative explanations - Mathew A. Vanderklift; Russell C. Babcock; Kylie Cook (Oecologia, 2013)

PM2.5 in the central part of Upper Silesia, Poland: concentrations, elemental composition, and mobility of components - W. Rogula-Kozłowska; B. Błaszczak; S. Szopa; K. Klejnowski; I. Sówka; A. Zwoździak; M. Jabłońska; B. Mathews (Environmental Monitoring and Assessment, 2013)

Methadone Toxicity and Possible Induction and Enhanced Elimination in a Premature Neonate - Mathew George; Joseph P. Kitzmiller; Michele Burns Ewald; Katherine A. O’Donell; Melissa Lai Becter; Steve Salhanick (Journal of Medical Toxicology, 2012)

Urban parakeets in Northern Illinois: A 40-year perspective - Stephen Pruett-Jones; Christopher W. Appelt; Anna Sarfaty; Brandy Van Vossen; Mathew A. Leibold; Emily S. Minor (Urban Ecosystems, 2012)

Incident radiation and the allocation of nitrogen within A rctic plant canopies: implications for predicting gross primary productivity - Lorna E. Street; Gaius R. Shaver; Edward B. Rastetter; Mark T. van Wijk; Brooke A. Kaye; Mathew Williams (Global Change Biology, 2012)
Arctic vegetation is characterized by high spatial variability in plant functional type ( PFT ) composition and gross primary productivity ( P ). Despite this variability, the two main drivers of P in sub‐ A rctic tundra are leaf area index ( L T ) and total foliar nitrogen ( N T ). L T and N T have been shown to be tightly coupled across PFT s in sub‐Arctic tundra vegetation, which simplifies up‐scaling by allowing quantification of the main drivers of P from remotely sensed L T . Our objective was to test the L T – N T relationship across multiple Arctic latitudes and to assess L T as a predictor of P for the pan‐ A rctic. Including PFT ‐specific parameters in models of L T – N T coupling provided only incremental improvements in model fit, but significant improvements were gained from including site‐specific parameters. The degree of curvature in the L T – N T relationship, controlled by a fitted canopy nitrogen extinction co‐efficient, was negatively related to average levels of diffuse radiation at a site. This is consistent with theoretical predictions of more uniform vertical canopy N distributions under diffuse light conditions. Higher latitude sites had higher average leaf N content by mass ( N M ), and we show for the first time that L T – N T coupling is achieved across latitudes via canopy‐scale trade‐offs between N M and leaf mass per unit leaf area ( L M ). Site‐specific parameters provided small but significant improvements in models of P based on L T and moss cover. Our results suggest that differences in L T – N T coupling between sites could be used to improve pan‐Arctic models of P and we provide unique evidence that prevailing radiation conditions can significantly affect N allocation over regional scales.

Novel role of NADPH oxidase in ischemic myocardium: a study with Nox2 knockout mice - Mahesh Thirunavukkarasu; Ram Sudheer Adluri; Bela Juhasz; Samson Mathews Samuel; Lijun Zhan; Anupinder Kaur; Gautam Maulik; Juan A Sanchez; Janet Hager; Nilanjana Maulik (Functional & Integrative Genomics, 2012)

Global patterns in the impact of marine herbivores on benthic primary producers - Alistair G. B. Poore; Alexandra H. Campbell; Ross A. Coleman; Graham J. Edgar; Veijo Jormalainen; Pamela L. Reynolds; Erik E. Sotka; John J. Stachowicz; Richard B. Taylor; Mathew A. Vanderklift; J. Emmett Duffy (Ecology Letters, 2012)
Despite the importance of consumers in structuring communities, and the widespread assumption that consumption is strongest at low latitudes, empirical tests for global scale patterns in the magnitude of consumer impacts are limited. In marine systems, the long tradition of experimentally excluding herbivores in their natural environments allows consumer impacts to be quantified on global scales using consistent methodology. We present a quantitative synthesis of 613 marine herbivore exclusion experiments to test the influence of consumer traits, producer traits and the environment on the strength of herbivore impacts on benthic producers. Across the globe, marine herbivores profoundly reduced producer abundance (by 68% on average), with strongest effects in rocky intertidal habitats and the weakest effects on habitats dominated by vascular plants. Unexpectedly, we found little or no influence of latitude or mean annual water temperature. Instead, herbivore impacts differed most consistently among producer taxonomic and morphological groups. Our results show that grazing impacts on plant abundance are better predicted by producer traits than by large‐scale variation in habitat or mean temperature, and that there is a previously unrecognised degree of phylogenetic conservatism in producer susceptibility to consumption.

Assessing the effects of spatial contingency and environmental filtering on metacommunity phylogenetics - Pedro R. Peres-Neto; Mathew A. Leibold; Stéphane Dray (Ecology, 2012)
Patterns in biodiversity and species coexistence are the result of multiple interacting processes including evolutionary history, trait variation, species interactions, dispersal, environmental variation, and landscape heterogeneity. Exploring patterns of biodiversity across space is perhaps the best integrative method (in contrast to the scarcity of temporal data) to interpret the influence of these multiple and interactive effects in determining community assembly, but it is still underdeveloped. Two emerging fields, metacommunity ecology and community phylogenetics, have been making relevant, though rather independent, progress toward understanding how communities are assembled in space. Our main goals were twofold. First, we described a heuristical framework to merge these two fields into “metacommunity phylogenetics.” The main goal of this framework is to provide a way to think about how niche properties of species arranged across the environment and different spatial scales influence the process of community assembly. Second, we developed an analytical framework to link niche properties based on trait and phylogenetics to environmental and spatial variation. In order to assess the performance of the framework, we used extensive computer simulations of community assembly to show that the procedure is robust under a variety of scenarios.

Resistance exercise and aerobic exercise when paired with dietary energy restriction both reduce the clinical components of metabolic syndrome in previously physically inactive males - Jeffrey A. Potteiger; Randal P. Claytor; Mathew W. Hulver; Michael R. Hughes; Michael J. Carper; Scott Richmond; John P. Thyfault (European Journal of Applied Physiology, 2012)

Effects of agri-environment management for cirl buntings on other biodiversity - Michael A. MacDonald; Gail Cobbold; Fiona Mathews; Matthew J. H. Denny; Leila K. Walker; Philip V. Grice; Guy Q. A. Anderson (Biodiversity and Conservation, 2012)

Analysis of doramectin in the serum of repeatedly treated pastured cattle used to predict the probability of cattle fever ticks (Acari: Ixodidae) feeding to repletion - Ronald B. Davey; J. Mathews Pound; Jerome A. Klavons; Kimberly H. Lohmeyer; Jeanne M. Freeman; Pia U. Olafson (Experimental and Applied Acarology, 2012)

Genomewide linkage analysis in Costa Rican families implicates chromosome 15q14 as a candidate region for OCD - Jessica Ross; Judith Badner; Helena Garrido; Brooke Sheppard; Denise A. Chavira; Marco Grados; Jonathan M. Woo; Pamela Doo; Paula Umaña; Eduardo Fournier; Sarah Shaw Murray; Carol A. Mathews (Human Genetics, 2011)

Population growth and colonization of Steller sea lions in the Glacier Bay region of southeastern Alaska: 1970s–2009 - Elizabeth A. Mathews; Jamie N. Womble; Grey W. Pendleton; Lauri A. Jemison; John M. Maniscalco; Greg Streveler (Marine Mammal Science, 2011)
We estimated trends in numbers of Steller sea lions in the Glacier Bay region of the eastern population from the 1970s to 2009. We documented the colonization of several new haul‐outs and the transition of one haul‐out (Graves Rocks) to a rookery, assessed seasonal patterns in distribution, and compared counts from different observation platforms. Sea lions increased in the region by 8.2%/yr (95%CI = 6.4%–10.0%), with the most growth at South Marble Island in Glacier Bay (16.6%/yr, 1991–2009) and rapid growth in Cross Sound. Seasonal patterns in the distribution of sea lions were likely influenced by new breeding opportunities and the seasonal availability of prey. Factors that likely contributed to the exceptional growth include availability of new habitat following deglaciation, immigration, redistribution, decreases in mortality, and ecosystem‐level changes. The rapid increase in sea lion numbers in this region is of particular interest in light of dramatic declines in the western population and evidence that Steller sea lions from both the eastern and western populations colonized the Graves Rocks rookery. The colonization and rookery development in this dynamic area may signal the reversal of the reproductive isolation of the two populations.

Dexamphetamine effects on separate constructs in the rubber hand illusion test - Matthew A. Albrecht; Mathew T. Martin-Iverson; Greg Price; Joseph Lee; Rajan Iyyalol; Flavie Waters (Psychopharmacology, 2011)

Assessment of the effects of different concentrations of ethylenediaminetetraacetic acid (EDTA) on erythrocytic indices of Nigerian White Fulani cattle and West African Dwarf goat - Ademola A. Oyagbemi; Odunayo I. Azeez; Kehinde O. Soetan; Adewale T. Ajala; Funsho O. Olayemi; Mathew O. Oyeyemi (Tropical Animal Health and Production, 2011)

DNA repair: the culprit for tumor-initiating cell survival? - Lesley A. Mathews; Stephanie M. Cabarcas; William L. Farrar (Cancer and Metastasis Reviews, 2011)

Intracerebral source generators characterizing concentrative meditation - Christina F. Lavallee; Mathew D. Hunter; Michael A. Persinger (Cognitive Processing, 2011)

The mediating effect of childhood abuse in sexual orientation disparities in tobacco and alcohol use during adolescence: results from the Nurses’ Health Study II - Hee-Jin Jun; S. Bryn Austin; Sarah A. Wylie; Heather L. Corliss; Benita Jackson; Donna Spiegelman; Mathew J. Pazaris; Rosalind J. Wright (Cancer Causes & Control, 2010)

Metacommunity phylogenetics: separating the roles of environmental filters and historical biogeography - Mathew A. Leibold; Evan P. Economo; Pedro Peres‐Neto (Ecology Letters, 2010)
Ecology Letters (2010) Abstract Biogeographical, evolutionary and ecological processes interact to regulate patterns in metacommunities. However, as there are few quantitative methods for evaluating their joint effects, resolving this interaction is difficult. We develop a method that aims to evaluate the interaction between phylogenetic structure, historical biogeographic events and environmental filtering in driving species distributions in a large‐scale metacommunity. Using freshwater zooplankton as a case study, we contrast the phylogenetic metacommunity structure of calanoid copepods and an ecologically similar but more vagile group, daphniids, in the northeastern US. We find that legacies of historical biogeographical events have strongly constrained calanoid distributions within this area, but that adaptation to different water chemistry and lake morphology drives the metacommunity structure of daphniids. Our findings show that biogeographic history and metacommunity processes jointly regulate community structure in these lakes and suggest that this also depends on factors that affect the colonization rate of different types of organisms.

Estimating parameters of a forest ecosystem C model with measurements of stocks and fluxes as joint constraints - Andrew D. Richardson; Mathew Williams; David Y. Hollinger; David J. P. Moore; D. Bryan Dail; Eric A. Davidson; Neal A. Scott; Robert S. Evans; Holly Hughes; John T. Lee; Charles Rodrigues; Kathleen Savage (Oecologia, 2010)

Plant-soil biodiversity relationships and nutrient retention in agricultural riparian zones of the Sacramento Valley, California - Anna Young-Mathews; Steven W. Culman; Sara Sánchez-Moreno; A. Toby O’Geen; Howard Ferris; Allan D. Hollander; Louise E. Jackson (Agroforestry Systems, 2010)

Species dispersal rates alter diversity and ecosystem stability in pond metacommunities - Jennifer G. Howeth; Mathew A. Leibold (Ecology, 2010)
Metacommunity theory suggests that relationships between diversity and ecosystem stability can be determined by the rate of species dispersal among local communities. The predicted relationships, however, may depend upon the relative strength of local environmental processes and disturbance. Here we evaluate the role of dispersal frequency and local predation perturbations in affecting patterns of diversity and stability in pond plankton metacommunities. Pond metacommunities were composed of three mesocosm communities: one of the three communities maintained constant “press” predation from a selective predator, bluegill sunfish ( Lepomis macrochirus ); the second community maintained “press” conditions without predation; and the third community experienced recurrent “pulsed” predation from bluegill sunfish. The triads of pond communities were connected at either no, low (0.7%/d), or high (20%/d) planktonic dispersal. Richness and composition of zooplankton and stability of plankton biomass and ecosystem productivity were measured at local and regional spatial scales. Dispersal significantly affected diversity such that local and regional biotas at the low dispersal rate maintained the greatest number of species. The unimodal local dispersal–diversity relationship was predator‐dependent, however, as selective press predation excluded species regardless of dispersal. Further, there was no effect of dispersal on beta diversity because predation generated local conditions that selected for distinct community assemblages. Spatial and temporal ecosystem stability responded to dispersal frequency but not predation. Low dispersal destabilized the spatial stability of producer biomass but stabilized temporal ecosystem productivity. The results indicate that selective predation can prevent species augmentation from mass effects but has no apparent influence on stability. Dispersal rates, in contrast, can have significant effects on both species diversity and ecosystem stability at multiple spatial scales in metacommunities.

Evolution, Homology Conservation, and Identification of Unique Sequence Signatures in GH19 Family Chitinases - N. A. Udaya Prakash; M. Jayanthi; R. Sabarinathan; P. Kangueane; Lazar Mathew; K. Sekar (Journal of Molecular Evolution, 2010)

Harbor seal ( Phoca vitulina richardii ) decline continues in the rapidly changing landscape of Glacier Bay National Park, Alaska 1992-2008 - Jamie N. Womble; Grey W. Pendleton; Elizabeth A. Mathews; Gail M. Blundell; Natalie M. Bool; Scott M. Gende (Marine Mammal Science, 2009)

Invasive prostate cancer cells are tumor initiating cells that have a stem cell-like genomic signature - George J. Klarmann; Elaine M. Hurt; Lesley A. Mathews; Xiaohu Zhang; Maria A. Duhagon; Tashan Mistree; Suneetha B. Thomas; William L. Farrar (Clinical & Experimental Metastasis, 2009)

Pleistocene glaciation events shape genetic structure across the range of the American lobster, Homarus americanus - ELLEN L. KENCHINGTON; GARETH C. HARDING; MATHEW W. JONES; PAULO A. PRODÖHL (Molecular Ecology, 2009)
A north/south discontinuity along the northeastern coast of North America in the genetic structure of the American lobster ( Homarus americanus ) was detected using a suite of 13 microsatellite loci assessed using spatial analyses. Population genetic data laid over existing data on physiographic changes and sea‐surface temperatures were used to reconstruct the Pleistocene distribution of this species. A postglacial northern‐edge colonization model best explains the relative genetic homogeneity of the northern region compared to the southern region centred in the Gulf of Maine. Population genetic analyses identified significant structure (range of standardized theta 0–0.02) but no significant evidence for isolation by distance. The novel application of spatial genetic analyses to a marine species allowed us to interpret these results by providing a greater insight into the evolutionary factors responsible for shaping the genetic structure of this species throughout is natural range.

Methyl bromide emissions to the atmosphere from temperate woodland ecosystems - JULIA DREWER; KATE V. HEAL; KEITH A. SMITH; MATHEW R. HEAL (Global Change Biology, 2008)
The environmental importance of methyl bromide (CH 3 Br) arises from its contribution to stratospheric ozone loss processes and, as a consequence, its emissions from anthropogenic sources are subject to the Montreal Protocol. A better understanding of the natural budget of CH 3 Br is required for assessing the benefit of anthropogenic emission reductions and for understanding any potential effects of environmental change on global CH 3 Br concentrations. Measurements of CH 3 Br flux in temperate woodland ecosystems, in particular, are very sparse, yet these cover a large fraction of terrestrial land surface. Results presented here from 18 months of field measurements of CH 3 Br fluxes in four static flux chambers in a woodland in Scotland and from enclosures of rotting wood and deciduous and coniferous leaf litter suggest net emissions from temperate woodlands. Net CH 3 Br fluxes in the woodland varied between the chambers, fluctuating between net uptake and net emissions (−73 to 279 ng m −2 h −1 across 161 individual measurements), and with no strong seasonality, but with time‐averaged net emission overall [27±57 (1 SD)] ng m −2 h −1 ]. This work demonstrates that scale‐up needs to be based on sufficient individual measurements to provide a reasonably constrained estimate of the long‐term mean. Mean (±1 SD) net CH 3 Br emissions from deciduous and coniferous leaf litter were 43 (±33) ng kg −1 (dry weight) h −1 and 80 (±37) ng kg −1 (dry weight) h −1 , respectively, and ∼1–2 ng kg −1 (fresh weight) h −1 from rotting woody litter. Despite the intrinsic variability, data obtained here consistently point to the conclusion that the temperate forest soil/litter ecosystem is a net source of CH 3 Br to the atmosphere.

ENVIRONMENTAL FLUCTUATIONS INDUCE SCALE‐DEPENDENT COMPENSATION AND INCREASE STABILITY IN PLANKTON ECOSYSTEMS - Amy L. Downing; Bryan L. Brown; Elizabeth M. Perrin; Timothy H. Keitt; Mathew A. Leibold (Ecology, 2008)
The temporal stability of aggregate community and ecosystem properties is influenced by the variability of component populations, the interactions among populations, and the influence of environmental fluctuations on populations. Environmental fluctuations that enhance population variability are generally expected to destabilize community and ecosystem properties, but this will depend on the degree to which populations are synchronized in their dynamics. Here we use seminatural experimental ponds to show that reduced synchrony among zooplankton taxa increases the temporal stability of zooplankton density, abundance, and ecosystem productivity in fluctuating environments. However, asynchrony only occurs at long timescales (∼80‐day periods) and under recurring environmental perturbations. At shorter timescales (∼10‐day periods) and in constant environments, synchronous dynamics dominate. Our findings support recent theory indicating that compensatory dynamics can stabilize communities and ecosystems. They further indicate that environmental fluctuations can enhance the likelihood of long‐period asynchrony and thus stabilize community and ecosystem properties despite their short term destabilizing effects.

Positron emission tomographic studies of brain dopamine and serotonin transporters in abstinent (±)3,4-methylenedioxymethamphetamine (“ecstasy”) users: relationship to cognitive performance - Una D. McCann; Zsolt Szabo; Melin Vranesic; Michael Palermo; William B. Mathews; Hayden T. Ravert; Robert F. Dannals; George A. Ricaurte (Psychopharmacology, 2008)

The effects of water availability on root growth and morphology in an Amazon rainforest - Daniel B. Metcalfe; Patrick Meir; Luiz Eduardo O. C. Aragão; Antonio C. L. da Costa; Alan P. Braga; Paulo H. L. Gonçalves; Joao de Athaydes Silva Junior; Samuel S. de Almeida; Lorna A. Dawson; Yadvinder Malhi; Mathew Williams (Plant and Soil, 2008)

Detached kelps from distant sources are a food subsidy for sea urchins - Mathew A. Vanderklift; Thomas Wernberg (Oecologia, 2008)

Simulated glacial and interglacial vegetation across Africa: implications for species phylogenies and trans‐African migration of plants and animals - SHARON A. COWLING; PETER M. COX; CHRIS D. JONES; MARK A. MASLIN; MATHEW PEROS; STEVEN A. SPALL (Global Change Biology, 2008)
The paleoenvironmental context of plant and animal species evolution (including glacial migrations and population separations) is based on a very patchy and incomplete paleo‐phytogeographic record. It was our objective, therefore, to provide an additional source for paleovegetation comparison by presenting simulations from a state‐of‐the‐art fully coupled earth system model (HadCM3LC). We simulated potential paleovegetation distributions following pre‐Industrial and last glacial maximum (LGM) climate forcing for the continent of Africa. Our LGM simulations indicate that tropical broadleaf forest was not severely displaced by expanding grasslands within central Africa, although the outer extent of closed forest decreases, particularly in the north. Our simulations indicate that the structure of glacial forests may have been much different from today, in that LGM simulations indicate that forests were likely characterized by lower leaf area indexes, lower tree heights and lower vegetation carbon content. On the other hand, warmer interglacial climate (like our pre‐Industrial climate scenario) results in simulated expansion of tropical forest from coast to coast across central Africa that we postulate could have acted as a barrier to plant and animal species migrations. We suggest that our modeling experiments have implications for the interpretation of phylogenetic data, including that of our own species, Homo sapiens sapiens .

Planktonic dispersal dampens temporal trophic cascades in pond metacommunities - Jennifer G. Howeth; Mathew A. Leibold (Ecology Letters, 2008)
Trophic cascades, in which changes in predation affect the biomass of lower trophic levels, vary substantially in strength and incidence. Most work to explain this variation has focused on local factors and has ignored larger regional effects. To study how metacommunity dynamics can alter trophic cascades, we constructed mesocosm metacommunities consisting of three pond communities with heterogeneous levels of fish predation and examined how planktonic dispersal rate (5–140% per week) affected biomass partitioning. Two of the three communities differed continually in the occurrence of fish and supported different but constant environments in a ‘spatial trophic cascade,’ while the third community supported temporally variable fish occurrence in a ‘temporal trophic cascade.’ We find that the presence, but the not the magnitude, of dispersal dampens temporal trophic cascades through an increase in grazer biomass. In contrast, dispersal has no effect on the strength of spatial cascades due to strong sorting pressures in the communities with constant presence or absence of fish as top predators.

Characterization of a SEPT9 interacting protein, SEPT14, a novel testis-specific septin - Esther A. Peterson; Linda M. Kalikin; Jonathan D. Steels; Mathew P. Estey; William S. Trimble; Elizabeth M. Petty (Mammalian Genome, 2007)

Origin, migration and fate of newly generated neurons in the adult rodent piriform cortex - Lee A. Shapiro; Kwan L. Ng; Richard Kinyamu; Patricia Whitaker-Azmitia; Eldon E. Geisert; Mathew Blurton-Jones; Qun-Yong Zhou; Charles E. Ribak (Brain Structure and Function, 2007)

Effects of chronic alcohol exposure on dopamine uptake in rat nucleus accumbens and caudate putamen - Evgeny A. Budygin; Erik B. Oleson; Tiffany A. Mathews; Anna K. Läck; Marvin R. Diaz; Brian A. McCool; Sara R. Jones (Psychopharmacology, 2007)

Marine sponges of the Dampier Archipelago, Western Australia: patterns of species distributions, abundance and diversity - Jane Fromont; Mathew A. Vanderklift; Gary A. Kendrick (Biodiversity and Conservation, 2006)

Export of detached macroalgae from reefs to adjacent seagrass beds - Thomas Wernberg; Mathew A. Vanderklift; Jason How; Paul S. Lavery (Oecologia, 2006)

Gene Finding on the Y: Fruitful Strategy in Drosophila does not Deliver in Anopheles - Jaroslaw Krzywinski; Mathew A. Chrystal; Nora J. Besansky (Genetica, 2006)

DECLINES IN HARBOR SEAL (PHOCA VITULINA) NUMBERS IN GLACIER BAY NATIONAL PARK, ALASKA, 1992–2002 - Elizabeth A. Mathews; Grey W. Pendleton (Marine Mammal Science, 2006)
Glacier Bay National Park had one of the largest breeding aggregations of harbor seals in Alaska, and it is functionally the only marine reserve for harbor seals in Alaska; yet, numbers of seals in the Bay are declining rapidly. Understanding why seals in Glacier Bay are declining may clarify their minimal habitat needs. We estimated population trends using models that controlled for environmental and observer‐related factors. In 1992, 6,200 seals were counted on icebergs in a tidewater glacial fjord and at terrestrial sites; by 2002 only 2,550 seals were counted at these same haul‐outs. Numbers of non‐pups in the glacial fjord declined by 6.6%/yr (−39%/8 yr) in June and by 9.6%/yr (−63%/11 yr) in August and at all other haul‐outs by 14.5%/yr (−75%/10 yr) during August. In the glacial fjord the number of pups remained steady from 1994 to 1999 and made up an increasing proportion of seals counted (5.4%/yr), and the proportion of pups peaked at 34%–36%. The rapid declines do not appear to be due to changes in seal behavior or redistribution. The declines reinforce genetic evidence that harbor seals in Glacier Bay are demographically isolated from other populations and indicate that current management stocks need to be redefined. Changes in Glacier Bay's ecosystem and population demographic data from the glacial fjord suggest that interspecific competition and predation are likely factors in the declines.

HCOP: The HGNC comparison of orthology predictions search tool - Mathew W. Wright; Tina A. Eyre; Michael J. Lush; Sue Povey; Elspeth A. Bruford (Mammalian Genome, 2005)

Hydrography and water masses in the southeastern Arabian Sea during March–June 2003 - S. S. C. Shenoi; D. Shankar; G. S. Michael; J. Kurian; K. K. Varma; M. R. Ramesh Kumar; A. M. Almeida; A. S. Unnikrishnan; W. Fernandes; N. Barreto; C. Gnanaseelan; R. Mathew; et al. (Journal of Earth System Science, 2005)

Agrobacterium-mediated in vitro transformation of wood-producing stem segments in eucalypts - Antanas V. Spokevicius; Kim Van Beveren; Mathew A. Leitch; Gerd Bossinger (Plant Cell Reports, 2005)

An improved analysis of forest carbon dynamics using data assimilation - Mathew Williams; Paul A. Schwarz; Beverly E. Law; James Irvine; Meredith R. Kurpius (Global Change Biology, 2005)
There are two broad approaches to quantifying landscape C dynamics – by measuring changes in C stocks over time, or by measuring fluxes of C directly. However, these data may be patchy, and have gaps or biases. An alternative approach to generating C budgets has been to use process‐based models, constructed to simulate the key processes involved in C exchange. However, the process of model building is arguably subjective, and parameters may be poorly defined. This paper demonstrates why data assimilation (DA) techniques – which combine stock and flux observations with a dynamic model – improve estimates of, and provide insights into, ecosystem carbon (C) exchanges. We use an ensemble Kalman filter (EnKF) to link a series of measurements with a simple box model of C transformations. Measurements were collected at a young ponderosa pine stand in central Oregon over a 3‐year period, and include eddy flux and soil CO 2 efflux data, litterfall collections, stem surveys, root and soil cores, and leaf area index data. The simple C model is a mass balance model with nine unknown parameters, tracking changes in C storage among five pools; foliar, wood and fine root pools in vegetation, and also fresh litter and soil organic matter (SOM) plus coarse woody debris pools. We nested the EnKF within an optimization routine to generate estimates from the data of the unknown parameters and the five initial conditions for the pools. The efficacy of the DA process can be judged by comparing the probability distributions of estimates produced with the EnKF analysis vs. those produced with reduced data or model alone. Using the model alone, estimated net ecosystem exchange of C (NEE)=−251±197 g C m −2 over the 3 years, compared with an estimate of −419±29 g C m −2 when all observations were assimilated into the model. The uncertainty on daily measurements of NEE via eddy fluxes was estimated at 0.5 g C m −2 day −1 , but the uncertainty on assimilated estimates averaged 0.47 g C m −2 day −1 , and only exceeded 0.5 g C m −2 day −1 on days where neither eddy flux nor soil efflux data were available. In generating C budgets, the assimilation process reduced the uncertainties associated with using data or model alone and the forecasts of NEE were statistically unbiased estimates. The results of the analysis emphasize the importance of time series as constraints. Occasional, rare measurements of stocks have limited use in constraining the estimates of other components of the C cycle. Long time series are particularly crucial for improving the analysis of pools with long time constants, such as SOM, woody biomass, and woody debris. Long‐running forest stem surveys, and tree ring data, offer a rich resource that could be assimilated to provide an important constraint on C cycling of slow pools. For extending estimates of NEE across regions, DA can play a further important role, by assimilating remote‐sensing data into the analysis of C cycles. We show, via sensitivity analysis, how assimilating an estimate of photosynthesis – which might be provided indirectly by remotely sensed data – improves the analysis of NEE.

Biodiversity in metacommunities: Plankton as complex adaptive systems? - Mathew A. Leibold; Jon Norberg (Limnology and Oceanography, 2004)
One of the more intriguing and challenging developments in ecology and in limnology and oceanography is the expansion of the temporal and spatial scales that are being addressed by current work. Researchers are realizing that individual communities and ecosystems are not isolated from each other but rather that they are connected by exchanges of individuals (through dispersal) and materials (through spatial fluxes). From a conceptual perspective, there is a need to develop theories and hypotheses about the roles of these exchanges on different community and ecosystem attributes. Here we focus on the concept of metacommunities, to address how plankton communities are structured and how this may generate patterns of variation in planktonic ecosystems. Our premise is that planktonic systems can be understood in the framework of metacommunities and that the regulation of these metacommunities alter how they work as “complex adaptive systems.” We hypothesize that connectivity through dispersal of local communities that are embedded in aquatic metacommunities show a range of dynamic behaviors related to their capacity to respond adaptively to environmental change.

SNTG1, the gene encoding ?1-syntrophin: a candidate gene for idiopathic scoliosis - Stavros Bashiardes; Rose Veile; Missy Allen; Carol A. Wise; Mathew Dobbs; Jose A. Morcuende; Lazlos Szappanos; John A. Herring; Anne M. Bowcock; Michael Lovett (Human Genetics, 2004)

Serum changes in trace elements during thyroid cancers - H. Al-Sayer; T.C. Mathew; S. Asfar; M. Khourshed; A. Al-Bader; A. Behbehani; H. Dashti (Molecular and Cellular Biochemistry, 2004)

X-ray structure of methanol dehydrogenase from Paracoccus denitrificans and molecular modeling of its interactions with cytochrome c-551i - Zong-Xiang Xia; Wei-Wen Dai; Yong-Ning He; Scott A. White; F. Scott Mathews; Victor L. Davidson (JBIC Journal of Biological Inorganic Chemistry, 2003)

Genetic analysis of resistance to Type-1 Diabetes in ALR/Lt mice, a NOD-related strain with defenses against autoimmune-mediated diabetogenic stress - Clayton E. Mathews; Robert T. Graser; Rebecca J. Bagley; Jason W. Caldwell; Renhua Li; Gary A. Churchill; David V. Serreze; Edward H. Leiter (Immunogenetics, 2003)

Sources of variation in consumer-diet ?15N enrichment: a meta-analysis - Mathew A. Vanderklift; Sergine Ponsard (Oecologia, 2003)

Bacterial diversity patterns along a gradient of primary productivity - M. Claire Horner‐Devine; Mathew A. Leibold; Val H. Smith; Brendan J. M. Bohannan (Ecology Letters, 2003)
Primary productivity is a key determinant of biodiversity patterns in plants and animals but has not previously been shown to affect bacterial diversity. We examined the relationship between productivity and bacterial richness in aquatic mesocosms designed to mimic small ponds. We observed that productivity could influence the composition and richness of bacterial communities. We showed that, even within the same system, different bacterial taxonomic groups could exhibit different responses to changes in productivity. The richness of members of the Cytophaga‐Flavobacteria‐Bacteroides group exhibited a significant hump‐shaped relationship with productivity, as is often observed for plant and animal richness in aquatic systems. In contrast, we observed a significant U‐shaped relationship between richness and productivity for α ‐proteobacteria and no discernable relationship for β ‐proteobacteria. We show, for the first time, that bacterial diversity varies along a gradient of primary productivity and thus make an important step towards understanding processes responsible for the maintenance of bacterial biodiversity.

Speciation of Heavy Metals in Bed Sediments of Wetlands in Urban Coimbatore, India - M. Mathew; R. Mohanraj; P. A. Azeez; S. Pattabhi (Bulletin of Environmental Contamination and Toxicology, 2003)

Sediment Quality of Wetlands in Coimbatore, Tamilnadu, India - M. Mathew; M. Sathish Kumar; P. A. Azeez; R. Sivakumar; S. Pattabi (Bulletin of Environmental Contamination and Toxicology, 2002)

Response of Avian Communities to Historic Habitat Change in the Northern Chihuahuan Desert - A. M. Pidgeon; N. E. Mathews; R. Benoit; E. V. Nordheim (Conservation Biology, 2001)
Throughout much of the northern Chihuahuan Desert, the grasslands that were widespread at the time of European settlement have been replaced by desert shrublands. Little is known about the effects of this change on avian communities. We analyzed historic U.S. Government Land Office records to assess large‐scale changes in vegetation cover from the 1880s to the present day. We studied vegetation and avian communities in one grassland habitat type and four desert shrubland habitat types to examine (1) how breeding‐bird communities may have changed in response to habitat conversion from grassland to desert shrubland and (2) whether breeding‐bird communities differ among the four desert shrubland habitat types that compose Chihuahuan Desert scrub in this region. To estimate the characteristics of 1880s black grama ( Bouteloua eriopoda ) grassland, we focused on plots located within extensive patches of present‐day black grama and compared the avian communities found there with those in desert shrubland. Species richness was higher in desert shrubland than grassland. Among the desert shrubland habitat types, species richness was consistently highest in mesquite. Avian abundance patterns differed among the four desert shrubland habitat types. At least 30% of the avian community in each habitat pair was distinct. Conversion of grassland to shrubland in south‐central New Mexico has likely been accompanied by a major turnover in the avian community. Remaining tracts of black grama provide habitat for species that may be uniquely adapted to the northern Chihuahuan Desert and should be protected.

The Control of Biological Invasions in the World's Oceans - N. Bax; J. T. Carlton; A. Mathews‐Amos; R. L. Haedrich; F. G. Howarth; J. E. Purcell; A. Rieser; A. Gray (Conservation Biology, 2001)
The introduction of alien, or nonindigenous, animals and plants has been identified by scientists and policy makers as a major threat to biodiversity in marine ecosystems. Although government agencies have struggled to control alien species on land and freshwater for decades with mixed success, the control of alien marine species is in its infancy. Prevention of introduction and establishment must be the first priority, but many populations of alien marine species are already well established worldwide. National and international policies leave loopholes for additional invasions to occur and provide only general guidance on how to control alien species once they are established. To address this issue, a multinational group of 25 scientists and attorneys convened in 1998 to examine options for controlling established populations of alien marine species. The discussions resulted in a framework for control of alien marine species to provide decision‐making guidance to policymakers, managers, scientists, and other stakeholders. The framework consists of seven basic steps: (1) establish the nature and magnitude of the problem, (2) set objectives, (3) consider the full range of alternatives, (4) determine risk, (5) reduce risk, (6) assess benefits versus risks, and ( 7) monitor the situation. This framework can provide guidance for control efforts under the existing patchwork of national laws and can help provide a foundation for international cooperation.

The Control of Biological Invasions in the World's Oceans - N. Bax; J. T. Carlton; A. Mathews-Amos; R. L. Haedrich; F. G. Howarth; J. E. Purcell; A. Rieser; A. Gray (Conservation Biology, 2001)

Molecular cloning of CS1, a novel human natural killer cell receptor belonging to the CD2 subset of the immunoglobulin superfamily - Kent S. Boles; Porunelloor A. Mathew (Immunogenetics, 2001)

Structure of the human natural killer cell receptor 2B4 gene and identification of a novel alternative transcript - Pappanaicken R. Kumaresan; Porunelloor A. Mathew (Immunogenetics, 2000)

Polymorphism in the 2B4 gene of inbred mouse strains - Pappanaicken R. Kumaresan; Van T. Huynh; Porunelloor A. Mathew (Immunogenetics, 2000)

Plant tolerance and resistance in food webs: community-level predictions and evolutionary implications - Jonathan M. Chase; Mathew A. Leibold; Ellen Simms (Evolutionary Ecology, 2000)

Cholangiocarcinoma and liver cirrhosis in relation to changes due to thioacetamide - A. Al-Bader; T.C. Mathew; H. Abul; H. Al-Sayer; P.K. Singal; H.M. Dashti (Molecular and Cellular Biochemistry, 2000)

Molecular cloning of transmembrane and soluble forms of a novel rat natural killer cell receptor related to 2B4 - P. R. Kumaresan; S. E. Stepp; M. Bennett; V. Kumar; P. A. Mathew (Immunogenetics, 2000)

Analysis of single-nucleotide polymorphisms in the interleukin-4 receptor gene for association with inflammatory bowel disease - M. Olavesen; J. Hampe; M. M. Mirza; R. Saiz; C. M. Lewis; S. Bridger; D. Teare; D. F. Easton; T. Herrmann; G. Scott; J. Hirst; J. Sanderson; et al. (Immunogenetics, 2000)

Cloning of a new lectin-like receptor expressed on human NK cells - Kent S. Boles; Roland Barten; Pappanaicken R. Kumaresan; John Trowsdale; Porunelloor A. Mathew (Immunogenetics, 1999)

A Revised Assessment of Species Redundancy and Ecosystem Reliability - Edward B. Rastetter; Laura Gough; Anne E. Hartley; Darrell A. Herbert; Knute J. Nadelhoffer; Mathew Williams (Conservation Biology, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Selenium and Liver Cirrhosis - A. Al-Bader; H. Abul; T. Hussain; M. Al-Moosawi; T.C. Mathew; H. Dashti (Molecular and Cellular Biochemistry, 1998)

Similarity and local co-existence of species in regional biotas - MATHEW A. Leibold (Evolutionary Ecology, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

The mouse homolog of FRG1, a candidate gene for FSHD, maps proximal to the myodystrophy mutation on chromosome 8 - Prabhjit K. Grewal; Judith C. T. van Deutekom; Kate A. Mills; Richard J. L. F. Lemmers; Kathy D. Mathews; Rune R. Frants; Jane E. Hewitt (Mammalian Genome, 1997)

Studies on some trace and minor elements in blood - T. R. Mahalingam; S. Vijayalashmi; R. Krishna Prabhu; A. Thiruvengadasami; K. S. R. Murthy; Deepak Sen; C. K. Mathews; K. Radha Shanmugasundaram (Biological Trace Element Research, 1997)

Studies on some trace and minor elements in blood - T. R. Mahalingam; S. Vijayalakshmi; R. Krishna Prabhu; A. Thiruvengadasami; Ann Wilber; C. K. Mathews; K. Radha Shanmugasundaram (Biological Trace Element Research, 1997)

Studies on some trace and minor elements in blood - T. R. Mahalingam; S. Vijayalakshmi; R. Krishna Prabhu; A. Thiruvengadasami; C. K. Mathews; K. Radha Shanmugasundaram (Biological Trace Element Research, 1997)

Do nutrient-competition models predict nutrient availabilities in limnetic ecosystems? - Mathew A. Leibold (Oecologia, 1997)

Habitat use and ecological specialization within lake Daphnia populations - Alan J. Tessier; Mathew A. Leibold (Oecologia, 1997)

Nucleotide and deduced amino acid sequence of the 3? end of the BYMV-MI genome - A. Mathews; G. Dwyer; S. Wylie; M. G. K. Jones (Archives of Virology, 1995)